Transparent and translucent glass-ceramics and glasses for forming the same
Patent Information
- Application Number
- CN202611155575.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-11-25
- Filing Date
- 2025-07-18
- Publication Date
- 2026-10-13
AI Technical Summary
然而,要形成具有高强度便携式装置所需的机械特性并且还具有所需光学特性的玻璃陶瓷可能较为困难
Smart Images

Figure CN122897601A_ABST
Abstract
Description
[0001] This application is a divisional application of Chinese patent application No. 202580010832.8, filed on July 18, 2025, entitled "Transparent and translucent glass ceramics and glass for forming the thereof". Cross-references to related applications
[0002] This specification claims priority to U.S. Provisional Application Serial No. 63 / 673,413, filed July 19, 2024, entitled “Transparent and Translucent Glass-Ceramics and Precursor Glasses for Forming the Same,” and U.S. Provisional Application Serial No. 63 / 724,590, filed November 25, 2024, entitled “Transparent and Translucent Glass-Ceramics and Glasses for Forming the Same,” each of which is incorporated herein by reference. Technical Field
[0003] This specification generally relates to transparent and translucent glass ceramics and the glass used to form them, and more specifically, to transparent glass ceramics with improved optical and mechanical properties. Background Technology
[0004] There is a need for high-strength transparent and translucent materials that can be used in conjunction with, for example, portable electronic devices. Several materials are currently available on the market, such as glass, zirconium oxide, plastics, metals, and glass ceramics.
[0005] Glass-ceramics have certain advantages over other materials. However, it can be difficult to form glass-ceramics that possess both the mechanical properties required for high-strength portable devices and the necessary optical properties.
[0006] Therefore, there is a need for glass-ceramics with improved properties, glass for forming said glass-ceramics, and methods for manufacturing said glass-ceramics from glass. Summary of the Invention
[0007] The subject matter of this instruction manual can be understood in the following ways.
[0008] According to the first aspect A1, the glass-ceramic comprises: a phase combination comprising lithium disilicate (Li2Si2O5) as the main crystalline phase and a residual amorphous glass phase; and greater than 0 wt% to less than 8 wt% CaO, wherein: the ratio of Al2O3 (wt%) to Li2O (wt%) in the glass-ceramic is greater than or equal to 0 and less than 0.50; and the glass-ceramic has a transmittance of greater than 88% for light in the wavelength range of greater than or equal to 400 nm to less than or equal to 750 nm.
[0009] The second aspect A2 includes the glass-ceramic of the first aspect A1, wherein the ratio of Al2O3 (wt%) to Li2O (wt%) in the glass-ceramic is greater than or equal to 0 and less than or equal to 0.30.
[0010] The third aspect A3 includes a glass-ceramic of any one of aspects A1 to A2, wherein the ratio of Al2O3 (wt%) to Li2O (wt%) in the glass-ceramic is greater than or equal to 0 and less than or equal to 0.15.
[0011] The fourth aspect A4 includes a glass-ceramic of any one of aspects A1 to A3, wherein the ratio of Li2O (wt%) to ZrO2 (wt%) in the glass-ceramic is greater than or equal to 1.10 and less than or equal to 5.0.
[0012] The fifth aspect A5 includes a glass-ceramic of any one of aspects A1 to A4, wherein the ratio of Li2O (wt%) to the sum of Li2O (wt%), Na2O (wt%) and K2O (wt%) in the glass-ceramic is greater than or equal to 0.5 and less than or equal to 1.0.
[0013] The sixth aspect A6 includes a glass-ceramic of any one of aspects A1 to A5, wherein the phase combination comprises a subcrystalline phase, the subcrystalline phase comprising lithium metasilicate (Li2SiO3).
[0014] The seventh aspect A7 includes a glass-ceramic of any one of aspects A1 to A6, wherein the phase combination comprises a subcrystalline phase, the subcrystalline phase comprising lithium phosphate (Li3PO4).
[0015] The eighth aspect A8 includes a glass-ceramic of any one of aspects A1 to A7, wherein the glass-ceramic does not contain a lithium feldspar crystal phase.
[0016] The ninth aspect A9 includes a glass-ceramic of any one of aspects A1 to A8, wherein the phase combination comprises: lithium disilicate (Li2Si2O5) with a Rietveld parameter greater than or equal to 20 and less than or equal to 90; lithium phosphate (Li3PO4) with a Rietveld parameter greater than or equal to 0 and less than or equal to 10; and lithium metasilicate (Li2SiO3) with a Rietveld parameter greater than or equal to 0 and less than or equal to 10.
[0017] The tenth aspect A10 includes a glass-ceramic of any one of aspects A1 to A9, comprising: greater than or equal to 55% by weight and less than or equal to 80% by weight of SiO2; greater than or equal to 0% by weight and less than or equal to 6% by weight of Al2O3; greater than or equal to 7% by weight and less than or equal to 20% by weight of Li2O; greater than or equal to 1% by weight and less than or equal to 8% by weight of P2O5; greater than or equal to 0.5% by weight and less than or equal to 20% by weight of ZrO2; greater than or equal to 0% by weight and less than or equal to 5.0% by weight of Na2O; and greater than or equal to 0% by weight and less than or equal to 5.0% by weight of K2O.
[0018] The eleventh aspect A11 includes a glass-ceramic of any one of aspects A1 to A10, comprising: greater than or equal to 55% by weight and less than or equal to 80% by weight of SiO2; greater than or equal to 7% by weight and less than or equal to 20% by weight of Li2O; greater than 4% by weight and less than or equal to 15% by weight of ZrO2; greater than or equal to 1% by weight and less than or equal to 8% by weight of P2O5; greater than or equal to 0.1% by weight and less than or equal to 5% by weight of Na2O; and less than 1% by weight of K2O.
[0019] Twelfth aspect A12 includes a glass-ceramic of any one of aspects A1 to A11, which contains greater than or equal to 0% by weight and less than or equal to 3% by weight of Al2O3.
[0020] The thirteenth aspect A13 includes a glass-ceramic of any one of aspects A1 to A12, which contains more than or equal to 55% by weight and less than or equal to 72% by weight of SiO2.
[0021] The fourteenth aspect A14 includes a glass-ceramic of any one of aspects A1 to A13, which contains more than or equal to 12% by weight and less than or equal to 18% by weight of Li2O.
[0022] The fifteenth aspect A15 includes a glass-ceramic of any one of aspects A1 to A14, which contains greater than or equal to 0.1% by weight and less than or equal to 3.0% by weight of Na2O.
[0023] The sixteenth aspect A16 includes the glass-ceramic of any one of aspects A1 to A15, which contains less than or equal to 0.5 K2O.
[0024] The seventeenth aspect A17 includes a glass ceramic of any one of aspects A1 to A16, which contains more than or equal to 7% by weight and less than or equal to 12% by weight of ZrO2.
[0025] Eighteenth aspect A18 includes a glass ceramic of any one of aspects A1 to A17, which contains more than or equal to 3% by weight and less than or equal to 5% by weight of P2O5.
[0026] Nineteenth aspect A19 includes a glass-ceramic of any one of aspects A1 to A18, comprising: greater than or equal to 55% by weight and less than or equal to 80% by weight of SiO2; greater than or equal to 7% by weight and less than or equal to 20% by weight of Li2O; greater than 4% by weight and less than or equal to 15% by weight of ZrO2; greater than or equal to 1% by weight and less than or equal to 8% by weight of P2O5; greater than or equal to 0.05% by weight and less than or equal to 5% by weight of Na2O; and less than 1% by weight of K2O.
[0027] A20 includes glass-ceramics of any one of A1 to A19, wherein the ratio of the Rietwald parameter of lithium disilicate to the crystallite size (in nm) of lithium disilicate is greater than or equal to 2.75 wt% / nm.
[0028] Aspect 21 includes a glass-ceramic of any one of aspects A1 to A20, wherein the glass-ceramic has a Young's modulus greater than or equal to 100 GPa and less than or equal to 130 GPa.
[0029] The twenty-second aspect A22 includes a glass-ceramic of any one of aspects A1 to A21, wherein the glass-ceramic has a fracture toughness greater than or equal to 1.10 MPa·m prior to ion exchange strengthening. 1 / 2 And less than or equal to 2.00 MPa·m 1 / 2 .
[0030] The twenty-third aspect A23 includes a glass-ceramic of any one of aspects A1 to A22, wherein for an article thickness of less than or equal to 0.5 mm, the glass-ceramic has a transmittance of greater than 88% for light with wavelengths in the range of greater than or equal to 400 nm to less than or equal to 750 nm.
[0031] The twenty-fourth aspect A24 includes a glass-ceramic of any one of aspects A1 to A23, wherein the haze of the glass-ceramic is less than 1.0%.
[0032] The twenty-fifth aspect A25 includes a glass-ceramic of any one of aspects A1 to A24, wherein the article of said glass-ceramic has a thickness of less than or equal to 0.6 mm.
[0033] The twenty-sixth aspect A26 includes a glass-ceramic of any one of aspects A1 to A25, wherein the haze of the glass-ceramic is less than 0.4%.
[0034] The twenty-seventh aspect A27 includes a glass-ceramic of any one of aspects A1 to A25, wherein the article of said glass-ceramic has a thickness of less than or equal to 0.6 mm.
[0035] The twenty-eighth aspect A28 includes a glass-ceramic of any one of aspects A1 to A27, wherein the glass-ceramic comprises crystallites with a crystallite size greater than or equal to 10 nm and less than or equal to 100 nm.
[0036] The twenty-ninth aspect A29 includes a glass-ceramic of any one of aspects A1 to A28, further comprising: a compressive stress layer extending from the surface of the glass-ceramic to a compression depth; and a maximum center tensile strength, wherein the maximum center tensile strength is greater than 130 MPa.
[0037] Thirty aspect A30 includes a glass-ceramic of any one of aspects A1 to A29, wherein the compressive stress layer contains a surface compressive stress greater than or equal to 200 MPa and less than or equal to 650 MPa.
[0038] The thirty-first aspect A31 includes a glass-ceramic of any one of aspects A1 to A30, wherein the glass-ceramic is strengthened by ion exchange.
[0039] Aspect 32 includes a glass-ceramic of any one of aspects A1 to A31, wherein the glass-ceramic has a thickness t, and the compression depth is greater than or equal to 0.09. t is less than or equal to 0.30 t.
[0040] The thirty-third aspect A33 includes a glass-ceramic of any one of aspects A1 to A32, which has a retention strength of greater than or equal to 100 MPa for a defect depth of less than or equal to 150 µm.
[0041] Aspect 34 includes glass-ceramics of any one of aspects A1 to A33, comprising: a Young's modulus greater than or equal to 100 GPa and less than or equal to 130 GPa; and a fracture toughness greater than or equal to 1.10 MPa·m prior to ion exchange strengthening. 1 / 2 And less than or equal to 2.00 MPa·m 1 / 2The transmittance is greater than 88% for light with wavelengths in the range of 400 nm or greater to 750 nm or less; and the haze is less than 1.0%.
[0042] The thirty-fifth aspect A35 includes a glass-ceramic of any one of aspects A1 to A34, wherein, for an article thickness of less than or equal to 0.5 mm, the glass-ceramic has a transmittance of greater than 88% for light with wavelengths in the range of greater than or equal to 400 nm to less than or equal to 750 nm.
[0043] The thirty-sixth aspect A36 includes a glass-ceramic of any one of aspects A1 to A35, wherein the glass-ceramic has a haze of less than 1.0% when the article thickness is less than or equal to 0.6 mm.
[0044] The thirty-seventh aspect A37 includes a glass-ceramic of any one of aspects A1 to A36, which contains a maximum central tensile strength of 130 MPa or less than or equal to 250 MPa.
[0045] The thirty-eighth aspect A38 includes a glass-ceramic of any one of aspects A1 to A37, wherein the maximum central tensile strength is greater than 220 MPa.
[0046] The thirty-ninth aspect A39 includes a glass-ceramic of any one of aspects A1 to A38, wherein the haze is less than or equal to 0.30%.
[0047] Fortieth aspect A40 includes glass-ceramics of any one of aspects A1 to A39, wherein the fracture toughness is greater than or equal to 1.2 MPa·m. 1 / 2 .
[0048] Forty-one aspect A41 includes a glass-ceramic of any one of aspects A1 to A40, wherein the transmittance for light with wavelengths in the range of greater than or equal to 400 nm to less than or equal to 750 nm is greater than 90%.
[0049] Aspect 42 includes a glass-ceramic of any one of aspects A1 to A41, wherein the Young's modulus is greater than or equal to 105 GPa and less than or equal to 130 GPa.
[0050] Aspect 43 includes an electronic device comprising a cover substrate comprising a glass-ceramic material of any one of aspects A1 to A42.
[0051] According to aspect 44 A44, the glass or glass-ceramic comprises: greater than or equal to 55 wt% and less than or equal to 80 wt% of SiO2; greater than or equal to 7 wt% and less than or equal to 20 wt% of Li2O; greater than or equal to 1 wt% and less than or equal to 8 wt% of P2O5; greater than or equal to 0.05 wt% and less than or equal to 5.0 wt% of Na2O; greater than or equal to 0.5 wt% and less than or equal to 20 wt% of ZrO2; greater than or equal to 1 wt% and less than 4 wt% of CaO; and less than 1 wt% of K2O, wherein the ratio of Al2O3 (wt%) to Li2O (wt%) in the glass or glass-ceramic is greater than or equal to 0 and less than 0.20.
[0052] Aspect 45 includes the glass or glass-ceramic of aspect A44, which contains greater than or equal to 0% by weight and less than or equal to 3% by weight of Al2O3.
[0053] Aspect 46 includes a glass or glass-ceramic of any one of aspects A44 to A45, wherein the ratio of Al2O3 (wt%) to Li2O (wt%) in the glass or glass-ceramic is greater than or equal to 0 and less than 0.15.
[0054] Aspect 47 includes a glass or glass-ceramic of any one of aspects A44 to A46, wherein the ratio of Li2O (wt%) to ZrO2 (wt%) in the glass or glass-ceramic is greater than or equal to 1.20 and less than or equal to 5.
[0055] Aspect 48 includes a glass or glass-ceramic of any one of aspects A44 to A47, wherein the ratio of Li2O (wt%) to the sum of Li2O (wt%), Na2O (wt%) and K2O (wt%) in the glass or glass-ceramic is greater than or equal to 0.5 and less than or equal to 1.0.
[0056] Aspect 49 includes the glass or glass-ceramic of any one of aspects A44 to A48, which contains more than or equal to 55% by weight and less than or equal to 72% by weight of SiO2.
[0057] Fiftieth aspect A50 includes the glass or glass-ceramic of any one of aspects A44 to A49, which contains more than or equal to 12% by weight and less than or equal to 18% by weight of Li2O.
[0058] Fifty-one aspect A51 includes the glass or glass-ceramic of any one of aspects A44 to A50, which contains greater than or equal to 0.05% by weight and less than or equal to 3.0% by weight of Na2O.
[0059] Aspect 52 includes the glass or glass-ceramic of any one of aspects A44 to A51, which contains less than or equal to 0.5 K2O.
[0060] Aspect 53 includes the glass or glass-ceramic of any one of aspects A44 to A52, which contains more than or equal to 7% by weight and less than or equal to 12% by weight of ZrO2.
[0061] The 54th aspect A54 includes the glass or glass-ceramic of any one of aspects A44 to A53, which contains more than or equal to 3% by weight and less than or equal to 5% by weight of P2O5.
[0062] According to aspect 55 A55, the glass-ceramic article comprises: a phase composition comprising lithium disilicate (Li₂Si₂O₅) as the main crystalline phase and a residual amorphous glass phase, wherein the phase composition is substantially free of a lithium feldspar crystalline phase; a Young's modulus greater than or equal to 100 GPa and less than or equal to 130 GPa; and a fracture toughness greater than or equal to 1.10 MPa·m prior to ion exchange strengthening. 1 / 2 And less than or equal to 2.00 MPa·m 1 / 2 The transmittance is greater than 88% for light with wavelengths in the range of 400 nm or greater to 750 nm or less; and the haze is less than 1.0%.
[0063] Aspect 56, comprising aspect 55, includes glass-ceramic articles of 0.6 mm thickness, measured under D65 illumination and a 10° standard viewing angle, wherein the glass-ceramic article in the CIELAB color space... The reflectance color coordinates are greater than or equal to -3.80 and less than or equal to -2.20.
[0064] Aspect 57 includes a glass-ceramic article of any one of aspects A55 to A56, wherein for an article thickness of less than or equal to 0.5 mm, the glass-ceramic article has a transmittance of greater than 88% for light with wavelengths in the range of greater than or equal to 400 nm to less than or equal to 750 nm.
[0065] Aspect 58 includes a glass-ceramic article of any one of aspects A55 to A57, wherein the haze of the glass-ceramic article is less than 1.0% when the article thickness is less than or equal to 0.6 mm.
[0066] Aspect 59 includes a glass-ceramic article of any one of aspects A55 to A58, which, after damage is introduced by a pressurized gas method, has the following retention strengths: for an average defect depth of 150 µm or less, a retention strength greater than or equal to 100 MPa; for an average defect depth of 100 µm or less, a retention strength greater than or equal to 200 MPa; for an average defect depth of 50 µm or less, a retention strength greater than or equal to 350 MPa; for an average defect depth of 25 µm or less, a retention strength greater than or equal to 450 MPa; and for an average defect depth of 10 µm or less, a retention strength greater than or equal to 500 MPa.
[0067] Sixtieth aspect A60 includes a glass-ceramic article of any one of aspects A55 to A59, which contains a maximum central tension of 130 MPa or more and less than or equal to 250 MPa.
[0068] Sixty-one aspect A61 includes a glass-ceramic article of any one of aspects A55 to A60, wherein the maximum central tensile strength is greater than 220 MPa.
[0069] Aspect 62 includes glass-ceramic articles of any one of aspects A55 to A61, wherein the haze is less than or equal to 1.0%.
[0070] Aspect 63 includes a glass-ceramic article of any one of aspects A55 to A62, wherein the fracture toughness is greater than or equal to 1.2 MPa·m. 1 / 2 .
[0071] Aspect 64 includes a glass-ceramic article of any one of aspects A55 to A63, wherein the transmittance for light in the wavelength range of greater than or equal to 400 nm to less than or equal to 750 nm is greater than 90%.
[0072] Aspect 65 includes glass-ceramic articles of any one of aspects A55 to A64, wherein the Young's modulus is greater than or equal to 105 GPa and less than or equal to 130 GPa.
[0073] Aspect 66 includes any glass-ceramic article of any one of aspects A55 to A65, which includes a failure stress of greater than or equal to 110 MPa after impact with a pendulum impactor device with 180-grit sandpaper.
[0074] Aspect 67 includes any of aspects A55 to A66 of glass-ceramic articles, which include a failure stress of greater than or equal to 90 MPa after impact with a pendulum impactor device with 80-grit sandpaper.
[0075] Aspect 68 includes any of aspects A55 to A67 of glass-ceramic articles, which include a failure stress of greater than or equal to 80 MPa after impact with a pendulum impactor device with 30-grit sandpaper.
[0076] Aspect 69 includes a glass-ceramic article of any one of aspects A55 to A68, wherein the glass-ceramic article is not strengthened by ion exchange and contains an average defect depth of less than or equal to 70 µm after being impacted with a pendulum impactor device with 180-grit sandpaper.
[0077] Seventieth aspect A70 includes a glass-ceramic article of any one of aspects A55 to A69, wherein the glass-ceramic article is not strengthened by ion exchange and contains an average defect depth of less than or equal to 120 µm after being impacted by a pendulum impactor device with 80-grit sandpaper.
[0078] Seventy-one aspect A71 includes a glass-ceramic article of any one of aspects A55 to A70, wherein the glass-ceramic article is not strengthened by ion exchange and contains an average defect depth of less than or equal to 170 µm after being impacted by a pendulum impactor device with 30-grit sandpaper.
[0079] Aspect 72 includes a glass-ceramic article of any one of aspects A55 to A71, wherein the glass-ceramic article is not strengthened by ion exchange and contains an average defect depth of less than or equal to 80 µm after being impacted by a pendulum impactor device with 80-grit sandpaper.
[0080] Aspect 73 includes a glass-ceramic article of any one of aspects A55 to A72, wherein the glass-ceramic article has a retention strength of 250 MPa or greater.
[0081] Aspect 74 includes a glass-ceramic article of any one of aspects A55 to A73, wherein the glass-ceramic article is not strengthened by ion exchange and contains a content greater than or equal to 650 kgf / mm 2 And less than or equal to 700 kgf / mm 2 Knoop hardness.
[0082] Aspect 75 includes a glass-ceramic article of any one of aspects A55 to A74, wherein the glass-ceramic article is not strengthened by ion exchange and contains a content greater than or equal to 680 kgf / mm². 2 And less than or equal to 750 kgf / mm 2 Knoop hardness.
[0083] Aspect 76 includes a glass-ceramic article of any one of aspects A55 to A75, wherein the glass-ceramic article comprises a thickness t and a compressive stress CS greater than or equal to 300 MPa at a depth of 0.01t to 0.02t from the surface of the glass-ceramic article. D .
[0084] Aspect 77 includes glass-ceramic articles of any one of aspects A55 to A76, wherein the ratio of the Rietwald parameter of lithium disilicate to the crystallite size (in nm) of lithium disilicate is greater than or equal to 2.75 wt% / nm.
[0085] Aspect 78 includes a glass-ceramic article of any one of aspects A55 to A77, wherein the glass-ceramic article has a drop height of 180 cm or more on 80-mesh SiC sandpaper when the article thickness is 0.6 mm.
[0086] Aspect 79 includes a glass-ceramic article of any one of aspects A55 to A78, wherein the glass-ceramic article has a drop height of 130 cm or more on 80-mesh SiC sandpaper when the article thickness is 0.5 mm.
[0087] Eighty aspect A80 includes a glass-ceramic article of any one of aspects A55 to A79, wherein the glass-ceramic article has a drop height of greater than or equal to 160 cm on 80-grit SiC sandpaper when the article thickness is 0.55 mm.
[0088] Eighty-one aspect A81 includes a glass-ceramic article of any one of aspects A55 to A80, wherein the glass-ceramic article, when the article thickness is 0.55 mm, has a drop height greater than or equal to 45 cm on 36-mesh Al2O3 sandpaper.
[0089] Aspect 82 includes a glass-ceramic article of any one of aspects A55 to A81, wherein the glass-ceramic article, when the article thickness is 0.60 mm, has a drop height of more than or equal to 45 cm on 36-mesh Al2O3 sandpaper.
[0090] According to aspect 83 A83, the glass-ceramic article comprises: a phase composition comprising lithium disilicate (Li2Si2O5) as the main crystalline phase and a residual amorphous glass phase, wherein: the phase composition is substantially free of a lithium feldspar crystalline phase; and the ratio of the Ritwald parameter of lithium disilicate to the crystallite size (in nm) of lithium disilicate is greater than or equal to 2.75 wt% / nm.
[0091] Other features and advantages of the glass ceramics and glass described herein will be set forth in the following detailed description, and some features and advantages will be apparent to those skilled in the art from the description, or will be recognized by practice of the embodiments described herein, including the following description, the claims, and the drawings.
[0092] It should be understood that the foregoing general description and the following detailed description depict various embodiments and are intended to provide an overview or framework for understanding the nature and features of the claimed subject matter. The accompanying drawings, which are incorporated in and form a part of this specification, are included to provide a further understanding of the various embodiments. The drawings illustrate the various embodiments described herein and, together with the specification, serve to explain the principles and operation of the claimed subject matter. Attached Figure Description
[0093] Figure 1 A flowchart illustrating a method for forming glass-ceramics according to embodiments disclosed and described herein; Figure 2 A cross-section of a glass-ceramic product that has been chemically strengthened by ion exchange is schematically depicted. Figure 3A A top view of an electronic device comprising a glass-ceramic article according to embodiments disclosed and described herein is schematically depicted; Figure 3B A perspective view of an electronic device comprising a glass-ceramic article according to embodiments disclosed and described herein is schematically depicted; Figure 4 X-ray diffraction spectra of glass ceramics according to one or more embodiments described herein; Figure 5 To show SEM micrographs of the microstructure and crystallites of glass-ceramics according to one or more embodiments described herein; Figure 6 The maximum central tensile strength (Y-axis) of lithium disilicate glass-ceramic plates and lithium feldspar-lithium disilicate plates according to one or more embodiments described herein is graphically depicted as a function of ion exchange time (X-axis). Figure 7 The maximum central tensile strength (Y-axis) of the lithium disilicate glass-ceramic plate and the lithium feldspar-lithium disilicate plate according to the embodiments described herein is depicted graphically as a function of ion exchange time (X-axis). Figure 8 The haze (Y-axis) of a glass-ceramic plate according to the embodiments described herein and a glass-ceramic plate formed from a comparative glass-ceramic composition are graphically depicted as a function of thickness (X-axis). Figure 9The failure stress (Y-axis) of a glass-ceramic plate according to the embodiments described herein and a glass-ceramic plate formed from a comparative glass-ceramic composition is graphically depicted as a function of defect depth (X-axis). Figure 10 The compressive stress (Y-axis) of lithium disilicate glass ceramics and lithium feldspar-lithium disilicate glass ceramics according to the embodiments described herein is graphically depicted as a function of depth (X-axis). Figure 11 The defect depths (Y-axis) introduced in non-ion-exchanged lithium disilicate glass ceramics and non-ion-exchanged litharge-lithium disilicate glass ceramics according to the embodiments described herein are graphically depicted when different grits of sandpaper are used in the pendulum impactor device. Figure 12 The failure stress or retention strength (Y-axis) of nonion-exchanged lithium disilicate glass ceramics and nonion-exchanged litharge-lithium disilicate glass ceramics according to the embodiments described herein are graphically depicted in a pendulum impactor device with different sandpaper grits. Figure 13 The defect depth (Y-axis) introduced into ion-exchange lithium disilicate glass ceramics and ion-exchange litharge-lithium disilicate glass ceramics according to the embodiments described herein is graphically depicted when 80-grit sandpaper is used in a pendulum impactor device. Figure 14 The failure stress (Y-axis) of ion-exchange lithium disilicate glass ceramics and ion-exchange litharge-lithium disilicate glass ceramics according to the embodiments described herein is graphically depicted in a pendulum impactor device using 80-grit sandpaper. Figure 15 The Knoop hardness values of ion-exchanged (IOX) and non-ion-exchanged (NIX) lithium disilicate glass ceramics and ion-exchanged (IOX) and non-ion-exchanged (NIX) lithium feldspar-lithium disilicate glass ceramics according to the embodiments described herein are depicted graphically. Figure 16 The haze (Y-axis) of the lithium disilicate glass ceramic according to the embodiments described herein is graphically depicted as a function of the average crystallite size (X-axis). Figure 17 The haze (Y-axis) was graphically depicted as a ratio of the Rietwald parameter of lithium disilicate in glass ceramics to the average crystallite size (in nm) of lithium disilicate in glass ceramics. Figure 18 The drop test equipment is depicted schematically. Figure 19 The illustration depicts the use of... Figure 18 Drop testing equipment; Figure 20 The illustration depicts the use of... Figure 18 Drop testing equipment; Figure 21 The failure drop height (Y-axis) of glass-ceramic articles and comparative glass-ceramic articles according to the embodiments described herein is depicted graphically as a function of glass thickness (X-axis). Figure 22 The failure drop height (Y-axis) of glass-ceramic articles and comparative glass-ceramic articles according to the embodiments described herein is depicted graphically as a function of glass thickness (X-axis). Figure 23 The failure drop height (Y-axis) of glass-ceramic articles and comparative glass-ceramic articles according to the embodiments described herein is depicted graphically as a function of glass thickness (X-axis). Figure 24 The light reflected from the glass-ceramic substrate is depicted graphically as b The value (Y-axis) varies with haze (X-axis); and Figure 25 The image depicts the light transmitted through the glass-ceramic substrate in a graphical manner. The value (Y-axis) varies with the haze (X-axis). Detailed Implementation
[0094] Reference will now be made in detail to embodiments of the glass-ceramics and glasses described herein, examples of which are illustrated in the accompanying drawings. Wherever possible, the same reference numerals will be used throughout the drawings to refer to the same or similar components. According to embodiments, the glass-ceramics typically comprise a phase combination containing lithium disilicate (Li₂Si₂O₅) as the main crystalline phase and a residual amorphous glass phase. The glass-ceramics may contain greater than or equal to 1 wt% to less than 8 wt% CaO. The ratio of Al₂O₃ (wt%) to Li₂O (wt%) in the glass-ceramics may be greater than or equal to 0 and less than 0.50. The glass-ceramics may have a transmittance greater than 88% for light in the wavelength range of greater than or equal to 400 nm to less than or equal to 750 nm. In one or more embodiments, the glass-ceramics exhibiting the aforementioned transmittance have a thickness of 0.5 mm. Various embodiments of the glass-ceramics and glasses will be described herein with specific reference to the accompanying drawings.
[0095] As used herein, the term "glass" refers to a solid prior to exposure to controlled nucleation heat treatment and prior to exposure to the growth stage. The glass is amorphous (i.e., the sum of the Rietwald parameters of all crystalline phases in the glass, measured at 20 °C, is less than 0.5). The Rietwald parameters of the crystalline and amorphous phases of the glass are determined by X-ray diffraction (XRD) using the Rietwald method described herein.
[0096] As used herein, the term "nucleating glass" refers to a solid prepared by controlled nucleation of a glass but prior to exposure to a growth stage. A nucleating glass comprises one or more crystalline phases and a residual amorphous glassy phase. Nucleating glasses are formed by heat-treating the glass at a temperature above or equal to the nucleation temperature for a duration of nucleation (i.e., the nucleation duration), thereby forming a crystalline phase within the residual amorphous glassy phase. The nucleating glass is intended to crystallize more fully through controlled crystallization in subsequent heat treatments (i.e., exposure to subsequent growth stages) to form the final glass-ceramic. The crystalline phases in the nucleating glass may be the same as or different from the final crystalline phase of the glass-ceramic (e.g., in terms of composition, amount, morphology, size, or size distribution). The sum of the Rietwald parameters of all crystalline phases in a nucleating glass, measured at 20 °C, is greater than or equal to 0.5 and less than 20. After exposure to the nucleation temperature for a duration of nucleation and subsequent cooling of the nucleating glass to 20 °C, the Rietwald parameters of the crystalline phases of the nucleating glass are determined by X-ray diffraction (XRD) using the Rietwald method.
[0097] As used herein, the term "glass-ceramic" refers to a solid prepared by controlled crystallization of a nucleating glass, comprising one or more crystalline phases and a residual amorphous glassy phase. Glass-ceramics are formed by heat-treating a nucleating glass at a temperature above or equal to the growth temperature for a sustained growth time (i.e., the growth duration), thereby allowing the growth of a crystalline phase (referred to as the crystalline phase or the final crystalline phase after the growth stage) and / or the formation of additional crystalline phases in the residual amorphous glass. The crystalline phases may be the same as or different from the crystalline phases of the nucleating glass (e.g., in terms of composition, amount, morphology, size, or size distribution). The sum of the Rietwald parameters of all crystalline phases in a glass-ceramic, measured at 20 °C, is greater than or equal to 20. After exposure to the growth temperature for a sustained growth time and subsequent cooling to 20 °C, the Rietwald parameters of the crystalline phases of the glass-ceramic are determined by X-ray diffraction (XRD) using the Rietwald method.
[0098] The liquidus temperature of glass is the temperature above which no crystalline phase can coexist in equilibrium with the glass (in °C). The liquidus temperature is measured according to ASTM C829-81 (2022).
[0099] The liquidus viscosity of glass (in poise) is the viscosity of glass at its liquidus temperature. Liquidus viscosity is measured according to ASTM C965-23 (2023).
[0100] As used herein, “compression depth” or “DOC” refers to the depth of the compressive stress (CS) layer, which is the depth within a glass-ceramic article where the stress changes from compressive stress to tensile stress and the stress value is zero. According to convention commonly used in the art, compressive stress is expressed as negative (<0) stress, and tensile stress as positive (>0) stress. However, throughout this specification, unless otherwise indicated, CS is expressed as a positive or absolute value, i.e., as stated herein, CS = |CS|.
[0101] Compressive stress (CS) and depth of compression (DOC) values were measured using a hybrid method that combines measurements performed using evanescent prism coupled spectroscopy (EPCS) and light scattering polarization measurement (LSP), as disclosed in U.S. Patent Application Publication No. 2020 / 0300615, which is incorporated herein by reference in its entirety. Maximum central tensile strength (mCT) values were measured using a scattered light polarizer (SCALP) technique known in the art.
[0102] Fracture toughness (K) 1C K represents the ability of glass or glass-ceramic material to resist fracture. Fracture toughness is measured on non-chemically strengthened glass or glass-ceramic products, such as before ion exchange (IOX) treatment. 1C The value represents the characteristics of the article prior to IOX treatment. The fracture toughness test method described herein is not applicable to glass already exposed to IOX treatment. However, fracture toughness measurements described herein performed on the same article (e.g., glass or glass-ceramic substrate) prior to IOX treatment are correlated with fracture toughness after IOX treatment and are therefore used as is. The value used to measure K... 1C The herringbone-notched short bar (CNSB) method is disclosed in Reddy, KPR et al., “Fracture Toughness Measurement of Glass and Ceramic Materials Using Chevron-Notched Specimens,” J. Am. Ceram. Soc., 71 [6], C-310-C-313 (1988), the difference being Y It was calculated using Equation 5 from Bubsey, RT et al., “Closed-Form Expressions for Crack-Mouth Displacement and StressIntensity Factors for Chevron-Notched Short Bar and Short Rod Specimens Based on Experimental Compliance Measurements,” NASA Technical Memorandum 83796, pp. 1-30 (October 1992). This was used to measure K. 1C The double-torsion method and fixture are described in Shyam, A. and Lara-Curzio, E., “The double-torsion testing technique for determination of fracture toughness and slowcrack growth of materials: A review,” *Journal of Materials Science*, 41, pp. 4093-4104, (2006). The double-torsion method typically produces K values slightly higher than the herringbone notch short bar method. 1C Values. Unless otherwise stated, all fracture toughness values were measured using the herringbone notched short bar (CNSB) method.
[0103] As used herein, the term "retained strength" refers to the strength of a glass article after damage has been introduced when a glass-ceramic plate is bent to impart tensile stress. In some instances, retained strength is determined by introducing damage into the glass-ceramic plate using silicon carbide (SiC) particles entrained in a pressurized gas (i.e., by introducing damage via the "pressurized gas method"). Specifically, 30-mesh or 90-mesh SiC particles are entrained in a flowing gas (e.g., air) directed onto the surface of the glass-ceramic plate being tested. The mesh size of the SiC particles (i.e., 30-mesh or 90-mesh) and / or the pressure of the flowing gas can be varied to impart defects of different depths (e.g., defect depths ranging from approximately 10 µm to 180 µm). To determine retained strength, each glass-ceramic plate being tested is given a defect of a specific depth. In some instances, as described herein, retained strength is determined after damage has been introduced using a pendulum impactor apparatus.
[0104] After damage was introduced, the glass-ceramic plate was tested in a four-point bend according to ASTM C158-23 (2023), entitled "Standard Test Methods for Strength of Glass by Flexure (Determination of Modulus of Rupture)". Specifically, the glass-ceramic plate was tested in a four-point bend using a test fixture with a 24 mm span and a 12 mm gap between the load elements. A gradually increasing load (P) was applied to the plate until failure occurred, and the load at failure was recorded. The load was then calculated according to the equation σ = (3Pa) / (bd). 2 The load at failure is converted into stress (σ), where P is the load at failure, a is the span, d is the thickness of the glass-ceramic plate, and b is the width of the glass-ceramic plate. The stress (σ) is the remaining strength of the glass-ceramic plate. The remaining strength can also be called the failure stress.
[0105] Young's modulus, shear modulus, and Poisson's ratio are measured using a general type of resonant ultrasonic spectroscopy technique as described in ASTM E2001-13 (2018).
[0106] The haze of glass-ceramic products is measured using a haze meter (e.g., BYK Gardner Haze-Gard I) according to ASTM D1003-21 (2021) or ASTM D1044-19 (2019) on an optically polished glass-ceramic plate with a flat, parallel surface. Haze is reported as a percentage (%).
[0107] Optical transmittance (also referred to as “transmittance” in this document) was measured in the range of 400–1000 nm on optically polished samples with planar parallel surfaces using a Perkin Elmer Lambda 950 spectrophotometer, with data intervals of 2 nm. Transmittance was measured on the glass-ceramic article itself, without any coating or other application.
[0108] X-ray diffraction (XRD) was performed on the powder samples using a Bruker D4 Endeavor equipped with a Cu radiation source and a LynxEye detector. The Rietwald method was used, and the phase composition of the samples was determined using Bruker's Topas software package. The procedure for determining the Rietwald parameters of the crystalline and amorphous glassy phases of the glass-ceramics described herein is described in the section entitled "Procedure for Determining Rietwald Parameters of Glass-Ceramic Samples." It should be noted that the Rietwald parameters represent the relative concentration of each phase in the glass-ceramic, similar to the weight percentage (wt%) of each phase in the glass-ceramic, and can be converted to weight percentage using an internal standard. For example, a known amount of a crystalline phase not present in the analyzed glass-ceramic (e.g., fine-grained corundum of the lithium disilicate glass-ceramic of this application) can be added to the analyzed glass-ceramic sample, and XRD can be performed so that the Rietwald results are normalized relative to the known amount of the added crystalline phase.
[0109] The stored strain energy of glass-ceramic products is calculated as described in Gulati, Suresh T., “Frangibility of Tempered Soda-Lime Glass Sheet,” Glass Processing Days, September 13-15, 1997, pp. 72-76 (ISBN 952-90-8959-7), particularly according to equation (4) in the aforementioned publication.
[0110] The density was measured according to ASTM C693-93 (2019).
[0111] Vickers hardness is measured according to ASTM C1327-15 (2019) using a MITUTOYO HM114 hardness tester equipped with a Vickers indenter, with an indentation load of 200 grams (dwell time of 15 seconds). The diagonal of the indentation is measured using a calibrated optical microscope. The value is the average of five indentations measured for each sample. The test is performed on optically polished samples with flat, parallel surfaces.
[0112] Knoop hardness was measured according to ASTM C730-98 (2021) using a MITUTOYO HM114 hardness tester equipped with a Knoop indenter, with an indentation load of 200 g (dwell time of 15 seconds). The diagonal of the indentation was measured using a calibrated optical microscope. The value is the average of five indentations measured for each sample. The test was performed on optically polished samples with flat, parallel surfaces.
[0113] As used herein, the term "softening point" refers to a glass composition with a viscosity of 1 × 10⁻⁶. 7.6 Temperature at poise. Softening point was determined using the parallel plate viscosity method according to ASTM C1351M-96 (2012).
[0114] As used herein, the term "annealing point" refers to the point at which the viscosity of the glass or glass-ceramic reaches 1 × 10⁻⁶. 13 The annealing point was determined using the beam flexural viscosity method according to ASTM C598-93 (2013).
[0115] As used in this article, the terms "strain point" and "T" are used interchangeably. 应变 "This refers to a viscosity of 3 × 10⁻⁶ for glass or glass-ceramic materials." 14 Temperature at time of immersion. Strain point was determined using the beam bending viscosity method according to ASTM C598-93 (2013).
[0116] The linear coefficient of thermal expansion (CTE) of glass ceramics in the temperature range of 0°C to 300°C is expressed as the average CTE in the range, in ppm / °C (×10⁻⁶ / °C), and is determined using a pusher dilatometer according to ASTM E228-11 (2016).
[0117] As used in this article, the term "CIELAB color space" refers to the color space defined by the International Commission on Illumination (CIE) in 1976. It represents color as three values: L... a represents the lightness from black (0) to white (100). B represents the lightness from green (-) to red (+), and B It represents the brightness from blue (-) to yellow (+).
[0118] The terms "free from" and "substantially free from" when used to describe the concentration and / or absence of a particular constituent component in a glass or glass-ceramic mean that the constituent component was not intentionally added to the glass or glass-ceramic. However, the glass or glass-ceramic may contain trace amounts of the constituent component as contaminants or impurities, in amounts less than 0.01% by weight (i.e., the glass is substantially free from the constituent component). In terms of crystalline phase, if the Rietwald parameter of the crystalline phase is less than 0.5, then the glass-ceramic may be substantially free from the crystalline phase.
[0119] A range herein may be expressed as "less than or equal to" a specific value and / or "less than or equal to" another specific value. When representing such a range, another embodiment includes from one specific value and / or to another specific value. Similarly, when a value is expressed as an approximation using the antecedent "less than or equal to," it should be understood that the specific value forms another embodiment. It should be further understood that the endpoints of each range are meaningful both relative to and independent of another endpoint. Unless otherwise expressly stated, any range used herein includes all ranges and subranges, and any values in between.
[0120] As used in this article, directional terms such as up, down, right, left, front, back, top, and bottom are for reference only with reference to the accompanying drawings and are not intended to imply absolute orientation.
[0121] Unless otherwise expressly stated, it is not intended to interpret any method described herein as requiring its steps to be performed in a particular order, nor is it intended to require any particular orientation of any device. Therefore, it is not intended to infer any order or orientation in any way where a method claim does not actually describe the order in which its steps are followed, or where any device claim does not actually describe the order or orientation of individual components, or where the claims or description do not otherwise specifically specify that the steps are limited to a particular order, or where a particular order or orientation of the device's components is not described. This applies to any possible non-express basis for interpretation, including: logical questions concerning the arrangement of steps, the flow of operation, the order of components, or the orientation of components; general meanings derived from grammatical organization or punctuation; and the number or type of embodiments described in the specification.
[0122] As used herein, the singular forms “a”, “an”, and “the” include multiple indicators unless the context explicitly states otherwise. Thus, for example, unless the context explicitly states otherwise, a reference to a component of “a” includes aspects having two or more such components.
[0123] A range may be expressed herein as “about” a particular value and / or “about” another particular value. When such a range is expressed, another embodiment includes from one particular value and / or to another particular value. Similarly, when a value is expressed as an approximation using the antecedent “about,” it should be understood that the particular value forms another embodiment. It should be further understood that the endpoints of each range are meaningful both relative to and independent of another endpoint.
[0124] Glass-ceramics possess properties that make them suitable for use as cover substrates and / or housings in mobile electronic devices. For example, without being bound by theory, glass-ceramics with high fracture toughness and / or Young's modulus offer crack penetration resistance and exhibit good drop performance. When such glass-ceramics are chemically strengthened (e.g., through ion exchange), crack penetration resistance and drop performance can be further improved. High fracture toughness and / or Young's modulus may also increase the amount of stored tensile energy and maximum center tensile strength that can be imparted to glass-ceramics through chemical tempering (e.g., through ion exchange strengthening). Furthermore, in applications requiring high transparency, such as when glass-ceramics are used as cover glass in electronic devices, their optical properties (e.g., transmittance and haze) also make them well-suited for use as cover substrates and / or housings in mobile electronic devices.
[0125] In the embodiments described herein, the glass-ceramic exhibits a relatively high Young's modulus and relatively high fracture toughness. While not constrained by theory, it is believed that the relatively high Young's modulus is achieved by increasing the amount of the lithium disilicate phase in the glass-ceramic (compared to the amount of other possible phases present in the glass-ceramic). In this regard, it has been found that the amount of the lithium disilicate (Li₂Si₂O₅) phase in the glass-ceramic disclosed herein can be reduced or prevented by adjusting the composition of the glass (and the resulting glass-ceramic). 10 The formation of lithium disilicate crystals increases. Specifically, it has been found that limiting the amount of Al2O3 in the glass (and the resulting glass-ceramic) relative to the amount of Li2O in the glass, such that the Al2O3:Li2O ratio is less than 0.5, promotes the formation of lithium disilicate crystals in the glass-ceramic during ceramization, while reducing or preventing the formation of lepidolite crystals. This results in a relatively high Young's modulus value for the glass-ceramic, which in turn increases the amount of stored tensile energy and maximum central tensile strength that can be imparted to the glass-ceramic through chemical tempering (e.g., through ion exchange strengthening), thereby improving the mechanical properties of the glass-ceramic.
[0126] Furthermore, the optical properties of glass-ceramics can be improved by minimizing the formation of crystalline phases other than the lithium disilicate phase. For example, the various phases of a glass-ceramic (i.e., the various crystalline phases and the residual amorphous glass phase) can have different refractive indices. Minimizing the number of crystalline phases other than the lithium disilicate phase in the glass-ceramic reduces the overall difference between the refractive indices of the crystalline phases and the residual amorphous glass phase, thereby improving the optical properties of the glass-ceramic, such as transmittance and haze.
[0127] Furthermore, the glasses and glass-ceramics according to the embodiments disclosed and described herein may also include a relatively high amount of calcium oxide (CaO). Without being bound by any particular theory, it is believed that the additional calcium oxide increases the density of the glass-ceramic and thus slows ion diffusion into the glass-ceramic during chemical strengthening. This slowing of diffusion slows the ion exchange process but results in the glass-ceramic exhibiting greater compressive stress and central tensile strength compared to glasses and glass-ceramics with lower density. Zirconia is also believed to contribute to increasing the density of the glass-ceramics.
[0128] In the embodiments described herein, the composition of the glass is selected such that the resulting glass-ceramic has a phase combination comprising a lithium silicate phase (specifically a lithium disilicate phase), wherein the Rietwald parameter of the lithium disilicate phase is greater than that of other crystalline phases present in the glass-ceramic (i.e., the lithium disilicate phase is the dominant crystalline phase of the glass-ceramic). In the embodiments, the phase combination of the glass-ceramic may optionally comprise one or more secondary crystalline phases, such as, but not limited to, lithium metasilicate and / or lithium phosphate phases. The phase combination also includes a residual amorphous glass phase.
[0129] Lithium disilicate (Li₂Si₂O₅) is an orthorhombic crystal based on a corrugated sheet of {Si₂O₅} tetrahedral array. The crystals are typically plate-like or lath-like in shape, with prominent cleavage planes. Lithium disilicate-based glass ceramics offer highly desirable mechanical properties, including high bulk strength and fracture toughness, attributed to their randomly oriented, interlocking crystal microstructure—a crystal structure that forces cracks to propagate through the material via a tortuous path around these crystals.
[0130] In the embodiments, the Rietwald parameter of the lithium disilicate crystalline phase (also referred to herein as "L2S") in the glass-ceramic can be within the following ranges: greater than or equal to 20 to less than or equal to 90, greater than or equal to 20 to less than or equal to 85, greater than or equal to 20 to less than or equal to 80, greater than or equal to 20 to less than or equal to 75, greater than or equal to 20 to less than or equal to 70, greater than or equal to 20 to less than or equal to 65, greater than or equal to 20 to less than or equal to 60, greater than or equal to 20 to less than or equal to 55, greater than or equal to 20 to less than or equal to 50, greater than or equal to 20 to less than or equal to 45, greater than or equal to 20 to less than or equal to 40, greater than or equal to 20 to less than or equal to 35, greater than or equal to 20 to Less than or equal to 30, greater than or equal to 20 and less than or equal to 25, greater than or equal to 25 and less than or equal to 90, greater than or equal to 25 and less than or equal to 85, greater than or equal to 25 and less than or equal to 80, greater than or equal to 25 and less than or equal to 75, greater than or equal to 25 and less than or equal to 70, greater than or equal to 25 and less than or equal to 65, greater than or equal to 25 and less than or equal to 60, greater than or equal to 25 and less than or equal to 55, greater than or equal to 25 and less than or equal to 50, greater than or equal to 25 and less than or equal to 45, greater than or equal to 25 and less than or equal to 40, greater than or equal to 25 and less than or equal to 35, greater than or equal to 25 and less than or equal to 30, greater than or equal to 30 and less than or equal to 90 30 or more to 85 or less, 30 or more to 80 or less, 30 or more to 75 or less, 30 or more to 70 or less, 30 or more to 65 or less, 30 or more to 60 or less, 30 or more to 55 or less, 30 or more to 50 or less, 30 or more to 45 or less, 30 or more to 40 or less, 30 or more to 35 or less, 35 or more to 90 or less, 35 or more to 85 or less, 35 or more to 80 or less, 35 or more to 75 or more, 35 or more to 85 ... Less than or equal to 70, Greater than or equal to 35 to Less than or equal to 65, Greater than or equal to 35 to Less than or equal to 60, Greater than or equal to 35 to Less than or equal to 55, Greater than or equal to 35 to Less than or equal to 50, Greater than or equal to 35 to Less than or equal to 45, Greater than or equal to 35 to Less than or equal to 40, Greater than or equal to 40 to Less than or equal to 90, Greater than or equal to 40 to Less than or equal to 85, Greater than or equal to 40 to Less than or equal to 80, Greater than or equal to 40 to Less than or equal to 75, Greater than or equal to 40 to Less than or equal to 70, Greater than or equal to 40 to Less than or equal to 65, Greater than or equal to 40 to Less than or equal to 60, Greater than or equal to 40 to Less than or equal to 55, Greater than or equal to 40 to Less than or equal to 5040 or above to 45 or below, 45 or above to 90 or below, 45 or above to 85 or below, 45 or above to 80 or below, 45 or above to 75 or below, 45 or above to 70 or below, 45 or above to 65 or below, 45 or above to 60 or below, 45 or above to 55 or below, 45 or above to 50 or below, 50 or above to 50 or below. 90, greater than or equal to 50 to less than or equal to 85, greater than or equal to 50 to less than or equal to 80, greater than or equal to 50 to less than or equal to 75, greater than or equal to 50 to less than or equal to 70, greater than or equal to 50 to less than or equal to 65, greater than or equal to 50 to less than or equal to 60, greater than or equal to 50 to less than or equal to 55, greater than or equal to 55 to less than or equal to 90, greater than or equal to 55 to less than or equal to 85, greater than or equal to 55 to less than or equal to 80 ... 75 or above, 55 or above to 70 or below, 55 or above to 65 or below, 55 or above to 60 or below, 60 or above to 90 or below, 60 or above to 85 or below, 60 or above to 80 or below, 60 or above to 75 or below, 60 or above to 70 or below, 60 or above to 65 or below, 65 or above to 90 or below, 60 or above to 90 or below. The Ritterwald parameter of the lithium disilicate phase in the glass-ceramic can be within the following ranges: 5 to less than or equal to 85, greater than or equal to 65 to less than or equal to 80, greater than or equal to 65 to less than or equal to 75, greater than or equal to 65 to less than or equal to 70, greater than or equal to 70 to less than or equal to 90, greater than or equal to 70 to less than or equal to 85, greater than or equal to 70 to less than or equal to 80, greater than or equal to 70 to less than or equal to 75, greater than or equal to 75 to less than or equal to 90, greater than or equal to 75 to less than or equal to 85, or even greater than or equal to 75 to less than or equal to 80. In the embodiments, the Ritterwald parameter of the lithium disilicate phase in the glass-ceramic can be within the following ranges: greater than or equal to 60 to less than or equal to 74, greater than or equal to 62 to less than or equal to 72, greater than or equal to 63 to less than or equal to 72, greater than or equal to 64 to less than or equal to 72, or even greater than or equal to 66 to less than or equal to 71.5. In the embodiments, the lithium disilicate crystalline phase in the glass-ceramic may comprise approximately 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, ...The Ritwald parameter is 74 or 75. It should be understood that the above range includes all subranges within the explicitly disclosed range.
[0131] Lithium metasilicate (Li₂SiO₃) exhibits orthogonal symmetry, with its (Si₂O₆) chains parallel to the c-axis and linked together by lithium ions. Lithium metasilicate crystals can be readily dissolved from glass ceramics in dilute hydrofluoric acid.
[0132] In embodiments, when present in glass-ceramics, the Rietwald parameter of the lithium metasilicate crystalline phase can be within the following ranges: greater than or equal to 0 to less than or equal to 10.0, greater than or equal to 0 to less than or equal to 9.5, greater than or equal to 0 to less than or equal to 9.0, greater than or equal to 0 to less than or equal to 8.5, greater than or equal to 0 to less than or equal to 8.0, greater than or equal to 0 to less than or equal to 7.5, greater than or equal to 0 to less than or equal to 7.0, greater than or equal to 0 to less than or equal to 6.5, greater than or equal to 0 to less than or equal to 6.0, greater than or equal to 0 to less than or equal to 5.5, greater than or equal to 0 to less than or equal to 5.0, greater than or equal to 0 to less than or equal to 4.5, greater than or equal to 0 to less than or equal to 4.0, and greater than or equal to 4.0. 0 to 3.5, greater than or equal to 0 to 3.0, greater than or equal to 0 to 2.5, greater than or equal to 0 to 2.0, greater than or equal to 0 to 1.5, greater than or equal to 0 to 1.0, greater than or equal to 0 to 0.5, greater than or equal to 0.5 to 10.0, greater than or equal to 0.5 to 9.5, greater than or equal to 0.5 to 9.0, greater than or equal to 0.5 to 8.5, greater than or equal to 0.5 to 8.0, greater than or equal to 0.5 to 7.5, greater than or equal to 0.5 to 7.0, greater than or equal to 0.5 to 7.0, less than or equal to 3.5, greater than or equal to 3.0, greater than or equal to 0.5 to 10.0, greater than or equal to 0.5, less than or equal to 3.5, greater than or equal to 3.0, greater than or equal to 0.5, less than or equal to 3.0, greater than or equal to 3.0, less than or equal to 3.5, greater than or equal to 3.0, greater than or equal to 3.5, less ... Equal to 6.5, greater than or equal to 0.5 to less than or equal to 6.0, greater than or equal to 0.5 to less than or equal to 5.5, greater than or equal to 0.5 to less than or equal to 5.0, greater than or equal to 0.5 to less than or equal to 4.5, greater than or equal to 0.5 to less than or equal to 4.0, greater than or equal to 0.5 to less than or equal to 3.5, greater than or equal to 0.5 to less than or equal to 3.0, greater than or equal to 0.5 to less than or equal to 2.5, greater than or equal to 0.5 to less than or equal to 2.0, greater than or equal to 0.5 to less than or equal to 1.5, greater than or equal to 0.5 to less than or equal to 1.0, greater than or equal to 1.0 to less than or equal to 10.0, greater than or equal to 1.0 to less than or equal to 9.5, greater than or equal to 1.0 to Less than or equal to 9.0, Greater than or equal to 1.0 to less than or equal to 8.5, Greater than or equal to 1.0 to less than or equal to 8.0, Greater than or equal to 1.0 to less than or equal to 7.5, Greater than or equal to 1.0 to less than or equal to 7.0, Greater than or equal to 1.0 to less than or equal to 6.5, Greater than or equal to 1.0 to less than or equal to 6.0, Greater than or equal to 1.0 to less than or equal to 5.5, Greater than or equal to 1.0 to less than or equal to 5.0, Greater than or equal to 1.0 to less than or equal to 4.5, Greater than or equal to 1.0 to less than or equal to 4.0, Greater than or equal to 1.0 to less than or equal to 3.5, Greater than or equal to 1.0 to less than or equal to 3.0, Greater than or equal to 1.0 to less than or equal to 2.5, Greater than or equal to 1.0 to less than or equal to 2.0, greater than or equal to 1.0 to less than or equal to 1.5, greater than or equal to 1.5 to less than or equal to 10.0, greater than or equal to 1.5 to less than or equal to 9.5, greater than or equal to 1.5 to less than or equal to 9.0, greater than or equal to 1.5 to less than or equal to 8.5, greater than or equal to 1.5 to less than or equal to 8.0, greater than or equal to 1.5 to less than or equal to 7.5, greater than or equal to 1.5 to less than or equal to 7.0, greater than or equal to 1.5 to less than or equal to 6.5, greater than or equal to 1.5 to less than or equal to 6.0, greater than or equal to 1.5 to less than or equal to 5.5, greater than or equal to 1.5 to less than or equal to 5.0, greater than or equal to 1.5 to less than or equal to 4.5, greater than Values are 1.5 or less than or equal to 4.0, 1.5 or greater than or equal to 3.5, 1.5 or greater than or equal to 3.0, 1.5 or greater than or equal to 2.5, 1.5 or greater than or equal to 2.0, 2.0 or greater than or equal to 10.0, 2.0 or greater than or equal to 9.5, 2.0 or greater than or equal to 9.0, 2.0 or greater than or equal to 8.5, 2.0 or greater than or equal to 8.0, 2.0 or greater than or equal to 7.5, 2.0 or greater than or equal to 7.0, 2.0 or greater than or equal to 6.5, and 2.0 or greater than or equal to 6. 0, greater than or equal to 2.0 to less than or equal to 5.5, greater than or equal to 2.0 to less than or equal to 5.0, greater than or equal to 2.0 to less than or equal to 4.5, greater than or equal to 2.0 to less than or equal to 4.0, greater than or equal to 2.0 to less than or equal to 3.5, greater than or equal to 2.0 to less than or equal to 3.0, greater than or equal to 2.0 to less than or equal to 2.5, greater than or equal to 2.5 to less than or equal to 10.0, greater than or equal to 2.5 to less than or equal to 9.5, greater than or equal to 2.5 to less than or equal to 9.0, greater than or equal to 2.5 to less than or equal to 8.5, greater than or equal to 2.5 to less than or equal to 8.0, greater than or equal to 2.5 to less than or equal to 7.5, greater than or equal to 2.5 to less than Or equal to 7.0, greater than or equal to 2.5 to less than or equal to 6.5, greater than or equal to 2.5 to less than or equal to 6.0, greater than or equal to 2.5 to less than or equal to 5.5, greater than or equal to 2.5 to less than or equal to 5.0, greater than or equal to 2.5 to less than or equal to 4.5, greater than or equal to 2.5 to less than or equal to 4.0, greater than or equal to 2.5 to less than or equal to 3.5, greater than or equal to 2.5 to less than or equal to 3.0, greater than or equal to 3.0 to less than or equal to 10.0, greater than or equal to 3.0 to less than or equal to 9.5, greater than or equal to 3.0 to less than or equal to 9.0, greater than or equal to 3.0 to less than or equal to 8.5, greater than or equal to 3.0 to less than or equal to 8.0, greater than or equal to 3.0 to 7.5, 3.0 to 7.0, 3.0 to 6.5, 3.0 to 6.0, 3.0 to 5.5, 3.0 to 5.0, 4.5, 3.0 to 4.0, 3.5 to 10.0, 9.5, 9.0, 8.5, 8.0, 7.5, 7.0, 6.5, 7.0, 8.0, 7.5, 8.0, 7.5, 8.0, 7.5, 8.0, 7.5, 8.0, 7.5, 8.0, 7.5, 8.0, 7.5, 8.0, 7.5, 8.0, 7.5, 8.0, 8.5 ... 3.5 to less than or equal to 6.0, greater than or equal to 3.5 to less than or equal to 5.5, greater than or equal to 3.5 to less than or equal to 5.0, greater than or equal to 3.5 to less than or equal to 4.5, greater than or equal to 3.5 to less than or equal to 4.0, greater than or equal to 4.0 to less than or equal to 10.0, greater than or equal to 4.0 to less than or equal to 9.5, greater than or equal to 4.0 to less than or equal to 9.0, greater than or equal to 4.0 to less than or equal to 8.5, greater than or equal to 4.0 to less than or equal to 8.0, greater than or equal to 4.0 to less than or equal to 7.5, greater than or equal to 4.0 to less than or equal to 7.0, greater than or equal to 4.0 to less than or equal to 6.5, greater than or equal to 4.0 to less than or equal to 6.0, greater than or equal to 4.0 to less than or equal to 5.5, greater than or equal to 4.0 to less than or equal to 5.0, or even greater than or equal to 4.0 to less than or equal to 4.5. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope. In some embodiments, the Rietwald parameter of the lithium metasilicate crystalline phase in the glass-ceramic is 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, or even 10. In some embodiments, the glass-ceramic does not contain the lithium metasilicate crystalline phase. In some embodiments, the glass-ceramic is substantially free of the lithium metasilicate crystalline phase. For the purposes of this specification, the presence or absence of the crystalline phase is determined by X-ray diffraction (XRD) using the Rietwald method.
[0133] The glass-ceramics described herein may contain the lithium phosphate (Li3PO4 or "block lithium phosphate") crystalline phase. Li3PO4 contains a β-beryllium oxide-derived structure and crystallizes in orthorhombic Pnma space group.
[0134] In embodiments, when present in glass-ceramics, the Rietwald parameter of the lithium phosphate crystalline phase can be within the following ranges: greater than or equal to 0 to less than or equal to 10.0, greater than or equal to 0 to less than or equal to 9.5, greater than or equal to 0 to less than or equal to 9.0, greater than or equal to 0 to less than or equal to 8.5, greater than or equal to 0 to less than or equal to 8.0, greater than or equal to 0 to less than or equal to 7.5, greater than or equal to 0 to less than or equal to 7.0, greater than or equal to 0 to less than or equal to 6.5, greater than or equal to 0 to less than or equal to 6.0, greater than or equal to 0 to less than or equal to 5.5, greater than or equal to 0 to less than or equal to 5.0, greater than or equal to 0 to less than or equal to 4.5, greater than or equal to 0 to less than or equal to 4.0, greater than... or equal to 0 to less than or equal to 3.5, greater than or equal to 0 to less than or equal to 3.0, greater than or equal to 0 to less than or equal to 2.5, greater than or equal to 0 to less than or equal to 2.0, greater than or equal to 0 to less than or equal to 1.5, greater than or equal to 0 to less than or equal to 1.0, greater than or equal to 0 to less than or equal to 0.5, greater than or equal to 0.5 to less than or equal to 10.0, greater than or equal to 0.5 to less than or equal to 9.5, greater than or equal to 0.5 to less than or equal to 9.0, greater than or equal to 0.5 to less than or equal to 8.5, greater than or equal to 0.5 to less than or equal to 8.0, greater than or equal to 0.5 to less than or equal to 7.5, greater than or equal to 0.5 to less than or equal to 7.0, greater than or equal to 0.5 to less than or equal to 7.0. 6.5, greater than or equal to 0.5 to less than or equal to 6.0, greater than or equal to 0.5 to less than or equal to 5.5, greater than or equal to 0.5 to less than or equal to 5.0, greater than or equal to 0.5 to less than or equal to 4.5, greater than or equal to 0.5 to less than or equal to 4.0, greater than or equal to 0.5 to less than or equal to 3.5, greater than or equal to 0.5 to less than or equal to 3.0, greater than or equal to 0.5 to less than or equal to 2.5, greater than or equal to 0.5 to less than or equal to 2.0, greater than or equal to 0.5 to less than or equal to 1.5, greater than or equal to 0.5 to less than or equal to 1.0, greater than or equal to 1.0 to less than or equal to 10.0, greater than or equal to 1.0 to less than or equal to 9.5, greater than or equal to 1.0 to Less than or equal to 9.0, Greater than or equal to 1.0 to less than or equal to 8.5, Greater than or equal to 1.0 to less than or equal to 8.0, Greater than or equal to 1.0 to less than or equal to 7.5, Greater than or equal to 1.0 to less than or equal to 7.0, Greater than or equal to 1.0 to less than or equal to 6.5, Greater than or equal to 1.0 to less than or equal to 6.0, Greater than or equal to 1.0 to less than or equal to 5.5, Greater than or equal to 1.0 to less than or equal to 5.0, Greater than or equal to 1.0 to less than or equal to 4.5, Greater than or equal to 1.0 to less than or equal to 4.0, Greater than or equal to 1.0 to less than or equal to 3.5, Greater than or equal to 1.0 to less than or equal to 3.0, Greater than or equal to 1.0 to less than or equal to 2.5, Greater than or equal to 1.0 to less than or equal to 2.0, greater than or equal to 1.0 to less than or equal to 1.5, greater than or equal to 1.5 to less than or equal to 10.0, greater than or equal to 1.5 to less than or equal to 9.5, greater than or equal to 1.5 to less than or equal to 9.0, greater than or equal to 1.5 to less than or equal to 8.5, greater than or equal to 1.5 to less than or equal to 8.0, greater than or equal to 1.5 to less than or equal to 7.5, greater than or equal to 1.5 to less than or equal to 7.0, greater than or equal to 1.5 to less than or equal to 6.5, greater than or equal to 1.5 to less than or equal to 6.0, greater than or equal to 1.5 to less than or equal to 5.5, greater than or equal to 1.5 to less than or equal to 5.0, greater than or equal to 1.5 to less than or equal to 4.5, greater than Values are 1.5 or less than or equal to 4.0, 1.5 or greater than or equal to 3.5, 1.5 or greater than or equal to 3.0, 1.5 or greater than or equal to 2.5, 1.5 or greater than or equal to 2.0, 2.0 or greater than or equal to 10.0, 2.0 or greater than or equal to 9.5, 2.0 or greater than or equal to 9.0, 2.0 or greater than or equal to 8.5, 2.0 or greater than or equal to 8.0, 2.0 or greater than or equal to 7.5, 2.0 or greater than or equal to 7.0, 2.0 or greater than or equal to 6.5, and 2.0 or greater than or equal to 6. 0, greater than or equal to 2.0 to less than or equal to 5.5, greater than or equal to 2.0 to less than or equal to 5.0, greater than or equal to 2.0 to less than or equal to 4.5, greater than or equal to 2.0 to less than or equal to 4.0, greater than or equal to 2.0 to less than or equal to 3.5, greater than or equal to 2.0 to less than or equal to 3.0, greater than or equal to 2.0 to less than or equal to 2.5, greater than or equal to 2.5 to less than or equal to 10.0, greater than or equal to 2.5 to less than or equal to 9.5, greater than or equal to 2.5 to less than or equal to 9.0, greater than or equal to 2.5 to less than or equal to 8.5, greater than or equal to 2.5 to less than or equal to 8.0, greater than or equal to 2.5 to less than or equal to 7.5, greater than or equal to 2.5 to less than Or equal to 7.0, greater than or equal to 2.5 to less than or equal to 6.5, greater than or equal to 2.5 to less than or equal to 6.0, greater than or equal to 2.5 to less than or equal to 5.5, greater than or equal to 2.5 to less than or equal to 5.0, greater than or equal to 2.5 to less than or equal to 4.5, greater than or equal to 2.5 to less than or equal to 4.0, greater than or equal to 2.5 to less than or equal to 3.5, greater than or equal to 2.5 to less than or equal to 3.0, greater than or equal to 3.0 to less than or equal to 10.0, greater than or equal to 3.0 to less than or equal to 9.5, greater than or equal to 3.0 to less than or equal to 9.0, greater than or equal to 3.0 to less than or equal to 8.5, greater than or equal to 3.0 to less than or equal to 8.0, greater than or equal to 3.0 to 7.5, 3.0 to 7.0, 3.0 to 6.5, 3.0 to 6.0, 3.0 to 5.5, 3.0 to 5.0, 4.5, 3.0 to 4.0, 3.5 to 10.0, 9.5, 9.0, 8.5, 8.0, 7.5, 7.0, 6.5, 7.0, 8.0, 7.5, 8.0, 7.5, 8.0, 7.5, 8.0, 7.5, 8.0, 7.5, 8.0, 7.5, 8.0, 7.5, 8.0, 7.5, 8.0, 7.5, 8.0, 8.5 ... 3.5 to less than or equal to 6.0, greater than or equal to 3.5 to less than or equal to 5.5, greater than or equal to 3.5 to less than or equal to 5.0, greater than or equal to 3.5 to less than or equal to 4.5, greater than or equal to 3.5 to less than or equal to 4.0, greater than or equal to 4.0 to less than or equal to 10.0, greater than or equal to 4.0 to less than or equal to 9.5, greater than or equal to 4.0 to less than or equal to 9.0, greater than or equal to 4.0 to less than or equal to 8.5, greater than or equal to 4.0 to less than or equal to 8.0, greater than or equal to 4.0 to less than or equal to 7.5, greater than or equal to 4.0 to less than or equal to 7.0, greater than or equal to 4.0 to less than or equal to 6.5, greater than or equal to 4.0 to less than or equal to 6.0, greater than or equal to 4.0 to less than or equal to 5.5, greater than or equal to 4.0 to less than or equal to 5.0, or even greater than or equal to 4.0 to less than or equal to 4.5. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope. In some embodiments, the Rietwald parameter of the lithium phosphate crystalline phase in the glass-ceramic is 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, or even 10. In some embodiments, the glass-ceramic does not contain the lithium phosphate crystalline phase. In some embodiments, the glass-ceramic is substantially free of the lithium phosphate crystalline phase. For the purposes of this specification, the presence or absence of the crystalline phase is determined by X-ray diffraction (XRD) using the Rietwald method.
[0135] In the embodiments, the Rietwald parameters of the residual amorphous glass phase in the glass-ceramic are greater than or equal to 5 and less than or equal to 65, greater than or equal to 6 and less than or equal to 60, greater than or equal to 5 and less than or equal to 55, greater than or equal to 5 and less than or equal to 50, greater than or equal to 5 and less than or equal to 45, greater than or equal to 5 and less than or equal to 40, greater than or equal to 5 and less than or equal to 35, greater than or equal to 5 and less than or equal to 30, greater than or equal to 5 and less than or equal to 25, greater than or equal to 5 and less than or equal to 20, greater than or equal to 5 and less than or equal to 15, greater than or equal to 5 and less than or equal to 10, greater than or equal to 10 and less than or equal to 65, greater than or equal to 6 and less than or equal to 60, greater than or equal to 10 and less than or equal to 65. 55, greater than or equal to 10 to less than or equal to 50, greater than or equal to 10 to less than or equal to 45, greater than or equal to 10 to less than or equal to 40, greater than or equal to 10 to less than or equal to 35, greater than or equal to 10 to less than or equal to 30, greater than or equal to 10 to less than or equal to 25, greater than or equal to 10 to less than or equal to 20, greater than or equal to 10 to less than or equal to 15, greater than or equal to 15 to less than or equal to 65, greater than or equal to 5 to less than or equal to 60, greater than or equal to 15 to less than or equal to 55, greater than or equal to 15 to less than or equal to 50, greater than or equal to 15 to less than or equal to 45, greater than or equal to 15 to less than or equal to 40, greater than or equal to 15 to less than or equal to 35, greater than or equal to =15 to less than or equal to 30, greater than or equal to 15 to less than or equal to 25, greater than or equal to 15 to less than or equal to 20, greater than or equal to 20 to less than or equal to 65, greater than or equal to 20 to less than or equal to 60, greater than or equal to 20 to less than or equal to 55, greater than or equal to 20 to less than or equal to 50, greater than or equal to 20 to less than or equal to 45, greater than or equal to 20 to less than or equal to 40, greater than or equal to 20 to less than or equal to 35, greater than or equal to 20 to less than or equal to 30, greater than or equal to 20 to less than or equal to 25, greater than or equal to 25 to less than or equal to 65, greater than or equal to 25 to less than or equal to 60, greater than or equal to 25 to less than or equal to 5 ...65, greater than or equal to 25 to less than or equal to 65, greater than or equal to 25 to less than or 50 or above, 25 or above to 45 or below, 25 or above to 40 or below, 25 or above to 35 or below, 25 or above to 30 or below, 30 or above to 65 or below, 30 or above to 60 or below, 30 or above to 55 or below, 30 or above to 45 or below, 30 or above to 40 or below, 30 or above to 35 or below, 35 or above to 65 or below, 35 or above to 60 or below, 35 or above to 55 or above.The ranges are: greater than or equal to 35 and less than or equal to 45; greater than or equal to 35 and less than or equal to 40; greater than or equal to 40 and less than or equal to 65; greater than or equal to 40 and less than or equal to 60; greater than or equal to 40 and less than or equal to 55; greater than or equal to 45 and less than or equal to 50; greater than or equal to 50 and less than or equal to 60; greater than or equal to 50 and less than or equal to 55; or even greater than or equal to 55 and less than or equal to 60. It should be understood that the above ranges include all sub-ranges within the explicitly disclosed range. In the embodiments, the Rietwald parameter of the residual amorphous glass phase in the glass-ceramic can be approximately 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, or even 65.
[0136] In the embodiments described herein, the glass-ceramic comprises a lithium disilicate crystalline phase and a residual amorphous glassy phase. In some embodiments, the glass-ceramic comprises a lithium disilicate crystalline phase, a residual amorphous glassy phase, a lithium metasilicate crystalline phase, and a lithium phosphate crystalline phase. In some other embodiments, the glass-ceramic comprises a lithium disilicate crystalline phase, a residual amorphous glassy phase, a lithium metasilicate crystalline phase, and does not contain a lithium phosphate crystalline phase. In other embodiments, the glass-ceramic comprises a lithium disilicate crystalline phase, a residual amorphous glassy phase, a lithium phosphate crystalline phase, and does not contain a lithium metasilicate crystalline phase. In the embodiments described herein, the glass-ceramic comprises a lithoporite crystalline phase with a Ritterwald parameter less than 5. In the embodiments described herein, the glass-ceramic is substantially free of the lithoporite crystalline phase. In one or more embodiments, the glass-ceramic is free of the lithoporite crystalline phase. In the embodiments described herein, the glass-ceramic is free of the apatite crystalline phase. In the embodiments, the glass-ceramic is free of the cristobalite crystalline phase, the wollastonite crystalline phase, the β-quartz crystalline phase, and / or the fluorapatite crystalline phase. For the purposes of this specification, the presence or absence of a crystalline phase is determined by X-ray diffraction (XRD) using the Rietwald method.
[0137] The glasses and glass-ceramics described herein are generally described as lithium-containing silicate glasses and glass-ceramics, comprising SiO2, Li2O, Na2O, CaO, ZrO2, and P2O5. In embodiments, the lithium-containing silicate glasses and glass-ceramics may also comprise Al2O3. Furthermore, the glasses and glass-ceramics described herein may also comprise other alkali metal oxides, such as K2O, Rb2O, or Cs2O, as well as one or more other components described herein. As noted herein, the dominant microcrystalline phase of the phase combination of the glass-ceramics described herein is lithium disilicate. In embodiments, the sum of the Rietwald parameters of other crystalline phases (i.e., phases other than lithium disilicate, such as, but not limited to, lithium metasilicate (Li2SiO3) and lithium phosphate (Li3PO4)) may be less than 25, for example, less than 24, less than 23, less than 22, less than 21, or even less than 20. This phase combination provides glass-ceramics with low haze (high transparency) and improved mechanical properties.
[0138] SiO2, an oxide involved in glass formation, plays a role in stabilizing the network structure of glass and glass-ceramics. The concentration of SiO2 should be high enough to allow the formation of the lithium disilicate crystalline phase during heat treatment to transform the glass into a glass-ceramic. The amount of SiO2 may be limited to control the melting temperature of the glass, as the melting temperature of pure SiO2 or high-SiO2 glasses is unnecessarily high. In the embodiments, the glass and glass-ceramic contain greater than or equal to 55 wt% and less than or equal to 80 wt% SiO2, greater than or equal to 55 wt% and less than or equal to 75 wt% SiO2, greater than or equal to 55 wt% and less than or equal to 73 wt% SiO2, greater than or equal to 55 wt% and less than or equal to 72 wt% SiO2, greater than or equal to 60 wt% and less than or equal to 80 wt% SiO2, greater than or equal to 60 wt% and less than or equal to 75 wt% SiO2, greater than or equal to 60 wt% and less than or equal to 73 wt% SiO2, and greater than or equal to 60 wt% and less than or equal to 72 wt% SiO2. The range includes SiO2 of 65 wt% and less than or equal to 80 wt%, 65 wt% and less than or equal to 75 wt%, 65 wt% and less than or equal to 73 wt%, 65 wt% and less than or equal to 72 wt%, 68 wt% and less than or equal to 80 wt%, 68 wt% and less than or equal to 75 wt%, 68 wt% and less than or equal to 73 wt%, or even 68 wt% and less than or equal to 72 wt%. It should be understood that the above range includes all sub-ranges within the explicitly disclosed range.
[0139] In the glasses and glass-ceramics described herein, Li₂O facilitates the formation of the lithium disilicate crystalline phase. The addition of Li₂O also helps improve the stress level of the glass-ceramics according to the embodiments disclosed and described herein. In particular, lithium is the smallest of the alkali metal ions. Relatively high compressive stress and central tensile values can be achieved when lithium in the residual amorphous glass phase is replaced with larger alkali metal ions during ion exchange strengthening. However, excessive lithium in the glass makes it difficult to form, thus hindering the production of thin glass-ceramic articles required for handheld electronic devices such as mobile phones and tablets. In the embodiments described herein, to obtain lithium disilicate as the main crystalline phase, a composition containing at least about 7% by weight of Li₂O is desirable. Furthermore, it has been found that once Li₂O approaches about 20% by weight, the viscosity of the glass may decrease to an undesirable level, making the glass difficult to form.
[0140] Therefore, in the embodiments, the glass and glass-ceramics described herein may contain greater than or equal to 7 wt% and less than or equal to 20 wt% Li2O, 8 wt% and less than or equal to 20 wt% Li2O, greater than or equal to 9 wt% and less than or equal to 20 wt% Li2O, greater than or equal to 10 wt% and less than or equal to 20 wt% Li2O, greater than or equal to 11 wt% and less than or equal to 20 wt% Li2O, greater than or equal to 12 wt% and less than or equal to 20 wt% Li2O, greater than or equal to 13 wt% and less than or equal to 20 wt% Li2O, greater than or equal to 14 wt% and less than or equal to 20 wt% Li2O, greater than or equal to 15 wt% and less than or equal to 20 wt% Li2O, and so on. 20% by weight of Li₂O, greater than or equal to 16% by weight and less than or equal to 20% by weight of Li₂O, greater than or equal to 17% by weight and less than or equal to 20% by weight of Li₂O, greater than or equal to 18% by weight and less than or equal to 20% by weight of Li₂O, greater than or equal to 7% by weight and less than or equal to 19% by weight of Li₂O, 8% by weight and less than or equal to 19% by weight of Li₂O, 9% by weight and less than or equal to 19% by weight of Li₂O, greater than or equal to 10% by weight and less than or equal to 19% by weight of Li₂O, greater than or equal to 11% by weight and less than or equal to 19% by weight of Li₂O, greater than or equal to 12% by weight and less than or equal to 19% by weight of Li₂O, 13% by weight and less than or equal to 20% by weight of Li₂O, and 16% by weight and less than or equal to 20% by weight of Li₂O. =19% by weight of Li2O, greater than or equal to 14% by weight and less than or equal to 19% by weight of Li2O, 15% by weight and less than or equal to 19% by weight of Li2O, greater than or equal to 16% by weight and less than or equal to 19% by weight of Li2O, greater than or equal to 17% by weight and less than or equal to 19% by weight of Li2O, greater than or equal to 7% by weight and less than or equal to 18% by weight of Li2O, 8% by weight and less than or equal to 18% by weight of Li2O, 9% by weight and less than or equal to 18% by weight of Li2O, greater than or equal to 10% by weight and less than or equal to 18% by weight of Li2O, greater than or equal to 11% by weight and less than or equal to 18% by weight of Li2O, greater than or equal to 12% by weight and less than 19% by weight of Li2O, and 14% by weight and less than or equal to 19% by weight of Li2O, greater than or equal to 11% by weight and less than or equal to 18% by weight of Li2O, and 12% by weight and less than 19% by weight of Li2O. The following concentrations of Li2O are specified: 18% by weight or more; 13% by weight or more and 18% by weight or less; 14% by weight or more and 18% by weight or less; 15% by weight or more and 18% by weight or less; 16% by weight or more and 18% by weight or less; 7% by weight or more and 17% by weight or less; 8% by weight or less and 17% by weight; 9% by weight or more and 17% by weight or less; 10% by weight or more and 17% by weight or less; and 11% by weight or more and 17% by weight or less.Greater than or equal to 12 wt% and less than or equal to 17 wt% of Li₂O, greater than or equal to 13 wt% and less than or equal to 17 wt% of Li₂O, greater than or equal to 14 wt% and less than or equal to 17 wt% of Li₂O, greater than or equal to 15 wt% and less than or equal to 17 wt% of Li₂O, greater than or equal to 16 wt% and less than or equal to 17 wt% of Li₂O, greater than or equal to 7 wt% and less than or equal to 16 wt% of Li₂O, greater than or equal to 8 wt% and less than or equal to 16 wt% of Li₂O, greater than or equal to 9 wt% and less than or equal to 16 wt% of Li₂O, greater than or equal to 10 wt% and less than or equal to 16 wt% of Li₂O The following concentrations of Li₂O are specified: ≥11 wt% and ≤16 wt%; ≥12 wt% and ≤16 wt%; ≥13 wt% and ≤16 wt%; ≥14 wt% and ≤16 wt%; ≥7 wt% and ≤15 wt%; ≥8 wt% and ≤15 wt%; ≥9 wt% and ≤15 wt%; ≥10 wt% and ≤15 wt%; and ≥11 wt% and ≤15 wt% of Li₂O. Li₂O, greater than or equal to 12 wt% and less than or equal to 15 wt%, greater than or equal to 13 wt% and less than or equal to 15 wt%, greater than or equal to 14 wt% and less than or equal to 15 wt%, greater than or equal to 7 wt% and less than or equal to 14 wt%, greater than or equal to 8 wt% and less than or equal to 14 wt%, greater than or equal to 9 wt% and less than or equal to 14 wt%, greater than or equal to 10 wt% and less than or equal to 14 wt%, greater than or equal to 11 wt% and less than or equal to 14 wt%, greater than or equal to 12 wt% and less than or equal to 14 wt% of Li₂O. 2O, greater than or equal to 7 wt% and less than or equal to 13 wt% of Li2O, greater than or equal to 8 wt% and less than or equal to 13 wt% of Li2O, greater than or equal to 9 wt% and less than or equal to 13 wt% of Li2O, greater than or equal to 10 wt% and less than or equal to 13 wt% of Li2O, greater than or equal to 11 wt% and less than or equal to 13 wt% of Li2O, greater than or equal to 12 wt% and less than or equal to 13 wt% of Li2O, greater than or equal to 7 wt% and less than or equal to 12 wt% of Li2O, greater than or equal to 8 wt% and less than or equal to 12 wt% of Li2O, greater than or equal to 8 wt% and less than or equal to 12 wt% of Li2O,Or even greater than or equal to 10% by weight and less than or equal to 12% by weight of Li₂O. It should be understood that the above range includes all sub-ranges within the explicitly disclosed range.
[0141] As noted herein, alkali metal oxides Li₂O are commonly used to form various glass ceramics. However, other alkali metal oxides tend to reduce glass ceramic formation, instead forming silicate or aluminosilicate residual amorphous glass within the glass ceramic. It has been found that greater than about 5% by weight of Na₂O or K₂O, or combinations thereof, results in an excess of residual amorphous glass, which can lead to deformation during crystallization and undesirable microstructures from a mechanical property perspective. The composition of the residual amorphous glass can be adjusted to control viscosity during crystallization, minimize deformation or undesirable thermal expansion, or control microstructure properties. Therefore, typically, glasses may contain relatively low amounts of non-lithium alkali metal oxides. For example, in embodiments, the glass or glass ceramic may contain greater than or equal to 0% by weight to less than or equal to 5% by weight of R₂O, where R is one or more of the alkali metal cations Na and K. In embodiments, the glass or glass ceramic may contain greater than or equal to 0.1% by weight to less than or equal to 3% by weight of R₂O, where R is one or more of the alkali metal cations Na and K. In embodiments, the glass or glass-ceramic may contain greater than or equal to 0.1 wt% to less than or equal to 2.5 wt% of R2O, or even greater than or equal to 0.1 wt% to less than or equal to 2 wt% of R2O, wherein R is one or more of the alkali metal cations Na and K.
[0142] In the embodiments, the glass and glass-ceramic contain greater than or equal to 0 wt% and less than or equal to 5 wt% of Na2O, greater than or equal to 0 wt% and less than or equal to 4.5 wt% of Na2O, greater than or equal to 0 wt% and less than or equal to 4 wt% of Na2O, greater than or equal to 0 wt% and less than or equal to 3.5 wt% of Na2O, greater than or equal to 0 wt% and less than or equal to 3 wt% of Na2O, greater than or equal to 0 wt% and less than or equal to 2.5 wt% of Na2O, greater than or equal to 0 wt% and less than or equal to 2 wt% of Na2O, greater than or equal to 0 wt% and less than or equal to 1.5 wt% of Na2O, and greater than or equal to 0 wt% and less than or equal to 1 wt% of Na2O. The following concentrations of Na₂O are specified: ≥0.5% by weight; ≥0.05% by weight; ≥0.05% by weight; ≥0.45% by weight; ≥0.05% by weight; ≥0.4% by weight; ≥0.05% by weight; ≥0.35% by weight; ≥0.05% by weight; ≥0.3% by weight; ≥0.05% by weight; ≥0.25% by weight; ≥0.05% by weight; ≥0.2% by weight; ≥0.05 ... 1.5 wt% Na₂O, greater than or equal to 0.05 wt% and less than or equal to 1 wt% Na₂O, greater than or equal to 0.05 wt% and less than or equal to 0.5 wt% Na₂O, greater than or equal to 0.1 wt% and less than or equal to 5 wt% Na₂O, greater than or equal to 0.1 wt% and less than or equal to 4.5 wt% Na₂O, greater than or equal to 0.1 wt% and less than or equal to 4 wt% Na₂O, greater than or equal to 0.1 wt% and less than or equal to 3.5 wt% Na₂O, greater than or equal to 0.1 wt% and less than or equal to 3 wt% Na₂O, greater than or equal to 0.1 wt% and less than or equal to 2.5 wt% Na₂O, greater than or equal to 0.1 wt% Na₂O, and greater than or equal to 0.1 wt% Na₂O. The following concentrations of Na₂O are specified: % and less than or equal to 2 wt%; greater than or equal to 0.1 wt% and less than or equal to 1.5 wt%; greater than or equal to 0.1 wt% and less than or equal to 1 wt%; greater than or equal to 0.1 wt% and less than or equal to 0.5 wt%; greater than or equal to 0.5 wt% and less than or equal to 5 wt%; greater than or equal to 0.5 wt% and less than or equal to 4.5 wt%; greater than or equal to 0.5 wt% and less than or equal to 4 wt%; greater than or equal to 0.5 wt% and less than or equal to 3.5 wt%; greater than or equal to 0.5 wt% and less than or equal to 3 wt%; and greater than or equal to 0.The range includes 5% by weight and less than or equal to 2.5% by weight of Na₂O, greater than or equal to 0.5% by weight and less than or equal to 2% by weight of Na₂O, greater than or equal to 0.5% by weight and less than or equal to 1.5% by weight of Na₂O, or even greater than or equal to 0.5% by weight and less than or equal to 1% by weight of Na₂O. It should be understood that the above range includes all sub-ranges within the explicitly disclosed range. In embodiments, the glass or glass-ceramic does not contain Na₂O. In embodiments, the glass or glass-ceramic is substantially free of Na₂O.
[0143] In the embodiments, the glass and glass-ceramic contain greater than or equal to 0 wt% and less than or equal to 5 wt% of K2O, greater than or equal to 0 wt% and less than or equal to 4.5 wt% of K2O, greater than or equal to 0 wt% and less than or equal to 4 wt% of K2O, greater than or equal to 0 wt% and less than or equal to 3.5 wt% of K2O, greater than or equal to 0 wt% and less than or equal to 3 wt% of K2O, greater than or equal to 0 wt% and less than or equal to 2.5 wt% of K2O, greater than or equal to 0 wt% and less than or equal to 2 wt% of K2O, greater than or equal to 0 wt% and less than or equal to 1.5 wt% of K2O, greater than or equal to 0 wt% and less than or equal to 1 wt% of K2O, and greater than or equal to 0 wt% and less than or equal to 5 wt% of K2O. K₂O in the following amounts: 0.5% by weight and less than or equal to 0.5% by weight; 0.05% by weight and less than or equal to 5% by weight; 0.05% by weight and less than or equal to 4.5% by weight; 0.05% by weight and less than or equal to 4% by weight; 0.05% by weight and less than or equal to 3.5% by weight; 0.05% by weight and less than or equal to 3% by weight; 0.05% by weight and less than or equal to 2.5% by weight; 0.05% by weight and less than or equal to 2% by weight; 0.05% by weight and less than or equal to 1.5% by weight; and more than or equal to... K₂O of 0.05 wt% and less than or equal to 1 wt%, K₂O of 0.05 wt% and less than or equal to 0.5 wt%, K₂O of 0.1 wt% and less than or equal to 5 wt%, K₂O of 0.1 wt% and less than or equal to 4.5 wt%, K₂O of 0.1 wt% and less than or equal to 4 wt%, K₂O of 0.1 wt% and less than or equal to 3.5 wt%, K₂O of 0.1 wt% and less than or equal to 3 wt%, K₂O of 0.1 wt% and less than or equal to 2.5 wt%, K₂O of 0.1 wt% and less than or equal to 2 wt%, and more. 0.1 wt% and less than or equal to 1.5 wt% of K2O, greater than or equal to 0.1 wt% and less than or equal to 1 wt% of K2O, greater than or equal to 0.1 wt% and less than or equal to 0.5 wt% of K2O, greater than or equal to 0.5 wt% and less than or equal to 5 wt% of K2O, greater than or equal to 0.5 wt% and less than or equal to 4.5 wt% of K2O, greater than or equal to 0.5 wt% and less than or equal to 4 wt% of K2O, greater than or equal to 0.5 wt% and less than or equal to 3.5 wt% of K2O, greater than or equal to 0.5 wt% and less than or equal to 3 wt% of K2O, greater than or equal to 0.5 wt% and less than or equal to 2.5 wt% of K2O, greater than or equal to 0.The K₂O content is 5% by weight and less than or equal to 2% by weight, greater than or equal to 0.5% by weight and less than or equal to 1.5% by weight, or even greater than or equal to 0.5% by weight and less than or equal to 1% by weight. It should be understood that the above range includes all sub-ranges within the explicitly disclosed range. In embodiments, the glass or glass-ceramic does not contain K₂O. In embodiments, the glass or glass-ceramic is substantially free of K₂O.
[0144] In the embodiments, the ratio of Li₂O (wt%) to the sum of Li₂O (wt%), Na₂O (wt%), and K₂O (wt%) (i.e., Li₂O:(Li₂O+Na₂O+K₂O)) is greater than or equal to 0.5 and less than 1.0, greater than or equal to 0.6 and less than 1.0, greater than or equal to 0.7 and less than 1.0, greater than or equal to 0.8 and less than 1.0, or even greater than or equal to 0.9 and less than 1.0. If the total concentration of Na₂O and K₂O is too high (i.e., the ratio of Li₂O:(Li₂O+Na₂O+K₂O) is less than 0.5), then the stress generated in the glass-ceramic after ion exchange strengthening may be smaller.
[0145] Al₂O₃ can stabilize the glass network structure and improve the mechanical properties and chemical durability of the resulting glass and glass-ceramics. The amount of Al₂O₃ can be adjusted to control the viscosity of the glass during melting and forming. If the amount of Al₂O₃ is too high, the viscosity of the melt usually increases, while the fraction of lithium disilicate crystals decreases to a certain level, preventing the crystals in the phase assembly from forming an interlocking structure, thereby reducing the mechanical properties of the glass-ceramics. Furthermore, if the amount of Al₂O₃ is too high, the formation of the lithium aluminosilicate phase increases, while the elastic modulus and fracture toughness of the glass-ceramics decrease.
[0146] The glass and glass-ceramic embodiments described herein comprise 0% to 6.0% by weight of Al₂O₃, 0.1% to 6.0% by weight of Al₂O₃, 0.5% to 6.0% by weight of Al₂O₃, 1.0% to 6.0% by weight of Al₂O₃, 1.5% to 6.0% by weight of Al₂O₃, 2.0% to 6.0% by weight of Al₂O₃, 2.5% to 6.0% by weight of Al₂O₃, and 3.0% to 6.0% by weight of Al₂O₃. Al₂O₃ by weight%, greater than or equal to 3.5% by weight and less than or equal to 6.0% by weight, greater than or equal to 4.0% by weight and less than or equal to 6.0% by weight, greater than or equal to 4.5% by weight and less than or equal to 6.0% by weight, greater than or equal to 5.0% by weight, greater than or equal to 5.5% by weight and less than or equal to 6.0% by weight, greater than or equal to 0% by weight and less than or equal to 5.0% by weight, greater than or equal to 0.1% by weight and less than or equal to 5.0% by weight, greater than... Al₂O₃ in the following proportions: 0.5 wt% and less than or equal to 5.0 wt%; 1.0 wt% and less than or equal to 5.0 wt%; 1.5 wt% and less than or equal to 5.0 wt%; 2.0 wt% and less than or equal to 5.0 wt%; 2.5 wt% and less than or equal to 5.0 wt%; 3.0 wt% and less than or equal to 5.0 wt%; 3.5 wt% and less than or equal to 5.0 wt%; 4.0 wt% and less than or equal to 5.0 wt%; 4.5 wt% and less than or equal to 5.0 wt%; ... The following percentages of Al2O3 are specified: 5.0 wt% and less than or equal to 5.0 wt%; 0 wt% and less than or equal to 4.5 wt%; 0.1 wt% and less than or equal to 4.5 wt%; 0.5 wt% and less than or equal to 4.5 wt%; 1.0 wt% and less than or equal to 4.5 wt%; 1.5 wt% and less than or equal to 4.5 wt%; 2.0 wt% and less than or equal to 4.5 wt%; 2.5 wt% and less than or equal to 4.5 wt%; and 3.0 wt% and less than or equal to 4.5 wt%.5% by weight of Al2O3, greater than or equal to 3.5% by weight and less than or equal to 4.5% by weight of Al2O3, greater than or equal to 4.0% by weight and less than or equal to 4.5% by weight of Al2O3, greater than or equal to 0% by weight and less than or equal to 4.0% by weight of Al2O3, greater than or equal to 0.1% by weight and less than or equal to 4.0% by weight of Al2O3, greater than or equal to 0.5% by weight and less than or equal to 4.0% by weight of Al2O3, greater than or equal to 1.0% by weight and less than or equal to 4.0% by weight of Al2O3, greater than or equal to 1.5% by weight and less than or equal to 4.0% by weight of Al2O3, greater than or equal to 2.0% by weight and less than or equal to 4.0% by weight of Al2O3, The following are the concentrations of Al2O3: ≥2.5 wt% and ≤4.0 wt%; ≥3.0 wt% and ≤4.0 wt%; ≥3.5 wt% and ≤4.0 wt%; ≥0 wt% and ≤3.5 wt%; ≥0.1 wt% and ≤3.5 wt%; ≥0.5 wt% and ≤3.5 wt%; ≥1.0 wt% and ≤3.5 wt%; ≥1.5 wt% and ≤3.5 wt%; ≥2.0 wt% and... Al₂O₃ ≤ 3.5 wt%, ≥ 2.5 wt% and ≤ 3.5 wt%, ≥ 3.0 wt% and ≤ 3.5 wt%, ≥ 0 wt% and ≤ 3.0 wt%, ≥ 0.1 wt% and ≤ 3.0 wt%, ≥ 0.5 wt% and ≤ 3.0 wt%, ≥ 1.0 wt% and ≤ 3.0 wt%, ≥ 1.5 wt% and ≤ 3.0 wt%, ≥ 2.0 wt% and ≤ 3.0 wt% Al2O3, greater than or equal to 2.5 wt% and less than or equal to 3.0 wt% Al2O3, greater than or equal to 0 wt% and less than or equal to 2.5 wt% Al2O3, greater than or equal to 0.1 wt% and less than or equal to 2.5 wt% Al2O3, greater than or equal to 0.5 wt% and less than or equal to 2.5 wt% Al2O3, greater than or equal to 1.0 wt% and less than or equal to 2.5 wt% Al2O3, greater than or equal to 1.5 wt% and less than or equal to 2.5 wt% Al2O3, greater than or equal to 2.0 wt% and less than or equal to 2.5 wt% Al2O3, greater than or equal to 0 wt% and less than or equal to 2.0 wt% Al2O3, greater than or equal to 0.Al₂O₃ in amounts of 1% by weight and less than or equal to 2.0% by weight, 0.5% by weight and less than or equal to 2.0% by weight, 1.0% by weight and less than or equal to 2.0% by weight, 1.5% by weight and less than or equal to 2.0% by weight, 0% by weight and less than or equal to 1.5% by weight, 0.1% by weight and less than or equal to 1.5% by weight, and so on. The glass and glass-ceramic contain 0.5% by weight and less than or equal to 1.5% by weight, greater than or equal to 1.0% by weight and less than or equal to 1.5% by weight, greater than or equal to 0% by weight and less than or equal to 1.0% by weight, greater than or equal to 0.1% by weight and less than or equal to 1.0% by weight, greater than or equal to 0.5% by weight and less than or equal to 1.0% by weight, or greater than or equal to 0.1% by weight and less than or equal to 0.5% by weight. In the embodiments, the glass and glass-ceramic do not contain Al2O3. In the embodiments, the glass and glass-ceramic are substantially free of Al2O3. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0147] As noted herein, the ratio of Al2O3 (wt%) to Li2O (wt%) (Al2O3:Li2O) is minimized to reduce the formation of the lithium feldspar phase and promote the formation of the lithium disilicate phase during ceramization, thereby increasing the Young's modulus of the resulting glass-ceramic. In the embodiments, the ratio of Al2O3 (wt%) to Li2O (wt%) is greater than or equal to 0 and less than 0.50, greater than or equal to 0 and less than or equal to 0.45, greater than or equal to 0 and less than or equal to 0.40, greater than or equal to 0 and less than or equal to 0.35, greater than or equal to 0 and less than or equal to 0.30, greater than or equal to 0 and less than or equal to 0.25, greater than or equal to 0 and less than or equal to 0.20, greater than or equal to 0 and less than or equal to 0.15, or even greater than or equal to 0 and less than or equal to 0.1. In the embodiments, the ratio of Al2O3 (wt%) to Li2O (wt%) is 0, for example when the glass or glass ceramic does not contain Al2O3.
[0148] As noted herein, CaO can increase the density of glass (and the resulting glass-ceramics), thereby increasing the amount of compressive stress and central tensile force that can be generated in the glass. In embodiments, the glass and glass-ceramics comprise greater than 0 wt% and less than or equal to 10.0 wt% CaO, greater than or equal to 0.1 wt% and less than or equal to 10.0 wt% CaO, greater than or equal to 0.5 wt% and less than or equal to 10.0 wt% CaO, greater than or equal to 1.0 wt% and less than or equal to 10.0 wt% CaO, greater than or equal to 1.5 wt% and less than or equal to 10.0 wt% CaO, greater than or equal to 2.0 wt% and less than or equal to 10.0 wt% CaO, greater than or equal to 2.5 wt% and less than or equal to 10.0 wt% CaO, and greater than or equal to 3.0 wt% and less than or equal to 10.0 wt% CaO. CaO by weight%, ≥3.5% by weight and ≤10.0% by weight, ≥4.0% by weight and ≤10.0% by weight, ≥4.5% by weight and ≤10.0% by weight, ≥5.0% by weight and ≤10.0% by weight, ≥5.5% by weight and ≤10.0% by weight, ≥6.0% by weight and ≤10.0% by weight, ≥6.5% by weight and ≤10.0% by weight, ≥7.0% by weight and ≤10.0% by weight CaO, greater than or equal to 7.5% by weight and less than or equal to 10.0% by weight, greater than or equal to 8.0% by weight and less than or equal to 10.0% by weight, greater than or equal to 8.5% by weight and less than or equal to 10.0% by weight, greater than or equal to 9.0% by weight and less than or equal to 10.0% by weight, greater than 0% by weight and less than or equal to 9.0% by weight, greater than or equal to 0.1% by weight and less than or equal to 9.0% by weight, greater than or equal to 0.5% by weight and less than or equal to 9.0% by weight, greater than or equal to 1.0% by weight and less than or equal to 9.0% by weight, greater than or equal to 1.5% by weight. The following concentrations of CaO are specified in weight percentages: ≥9.0 wt%, ≥2.0 wt%, ≥2.5 wt%, ≥9.0 wt%, ≥3.0 wt%, ≥3.5 wt%, ≥9.0 wt%, ≥4.0 wt%, ≥4.5 wt%, ≥5.0 wt%, ≥9.0 wt%, and ≥5.5 wt%, ≤9.0 wt%.0% by weight of CaO, greater than or equal to 6.0% by weight and less than or equal to 9.0% by weight of CaO, greater than or equal to 6.5% by weight and less than or equal to 9.0% by weight of CaO, greater than or equal to 7.0% by weight and less than or equal to 9.0% by weight of CaO, greater than or equal to 7.5% by weight and less than or equal to 9.0% by weight of CaO, greater than or equal to 8.0% by weight and less than or equal to 9.0% by weight of CaO, greater than 0% by weight and less than or equal to 8.0% by weight of CaO, greater than 0.1% by weight and less than or equal to 8.0% by weight of CaO, greater than or equal to 0.5% by weight and less than or equal to 8.0% by weight of CaO, greater than or equal to 1.0% by weight and less than or equal to 8.0% by weight of CaO. CaO by weight%, greater than or equal to 1.5% by weight and less than or equal to 8.0% by weight, greater than or equal to 2.0% by weight and less than or equal to 8.0% by weight, greater than or equal to 2.5% by weight and less than or equal to 8.0% by weight, greater than or equal to 3.0% by weight and less than or equal to 8.0% by weight, greater than or equal to 3.5% by weight and less than or equal to 8.0% by weight, greater than or equal to 4.0% by weight and less than or equal to 8.0% by weight, greater than or equal to 4.5% by weight and less than or equal to 8.0% by weight, greater than or equal to 5.0% by weight and less than or equal to 8.0% by weight, greater than or equal to 5.5% by weight and less than or equal to 8.0% by weight, and so on. The following concentrations of CaO are specified: 8.0 wt%; ≥6.0 wt% and ≤8.0 wt%; ≥6.5 wt% and ≤8.0 wt%; ≥7.0 wt% and ≤8.0 wt%; ≥0 wt% and ≤6.0 wt%; ≥0.1 wt% and ≤6.0 wt%; ≥0.5 wt% and ≤6.0 wt%; ≥1.0 wt% and ≤6.0 wt%; ≥1.5 wt% and ≤6.0 wt%; ≥2.0 wt% and ≤6.0 wt%. 6.0 wt% CaO, greater than or equal to 2.5 wt% and less than or equal to 6.0 wt% CaO, greater than or equal to 3.0 wt% and less than or equal to 6.0 wt% CaO, greater than or equal to 3.5 wt% and less than or equal to 6.0 wt% CaO, greater than or equal to 4.0 wt% and less than or equal to 6.0 wt% CaO, greater than or equal to 4.5 wt% and less than or equal to 6.0 wt% CaO, greater than or equal to 5.0 wt% and less than or equal to 6.0 wt% CaO, greater than or equal to 0.1 wt% and less than or equal to 5.0 wt% CaO, greater than or equal to 0.5 wt% and less than or equal to 5.0 wt% CaO.0% by weight of CaO, greater than or equal to 1.0% by weight and less than or equal to 5.0% by weight of CaO, greater than or equal to 1.5% by weight and less than or equal to 5.0% by weight of CaO, greater than or equal to 2.0% by weight and less than or equal to 5.0% by weight of CaO, greater than or equal to 2.5% by weight and less than or equal to 5.0% by weight of CaO, greater than or equal to 3.0% by weight and less than or equal to 5.0% by weight of CaO, greater than or equal to 3.5% by weight and less than or equal to 5.0% by weight of CaO, greater than or equal to 4.0% by weight and less than or equal to 5.0% by weight of CaO, greater than 0% by weight and less than or equal to 4.0% by weight of CaO, greater than or equal to 0.1% by weight and less than or equal to 4.0% by weight of CaO. 0% by weight of CaO, greater than or equal to 0.5% by weight and less than or equal to 4.0% by weight of CaO, greater than or equal to 1.0% by weight and less than or equal to 4.0% by weight of CaO, greater than or equal to 1.5% by weight and less than or equal to 4.0% by weight of CaO, greater than or equal to 2.0% by weight and less than or equal to 4.0% by weight of CaO, greater than or equal to 2.5% by weight and less than or equal to 4.0% by weight of CaO, greater than or equal to 3.0% by weight and less than or equal to 4.0% by weight of CaO, greater than or equal to 3.5% by weight and less than or equal to 4.0% by weight of CaO, greater than 0% by weight and less than or equal to 3.5% by weight of CaO, greater than or equal to 0.05% by weight and less than or equal to 3.0% by weight of CaO, and greater than or equal to 0.05% by weight and less than or equal to 3.0% by weight of CaO. 0.5% by weight of CaO, greater than or equal to 0.1% by weight and less than or equal to 3.5% by weight of CaO, greater than or equal to 0.5% by weight and less than or equal to 3.5% by weight of CaO, greater than or equal to 1.0% by weight and less than or equal to 3.5% by weight of CaO, greater than or equal to 1.5% by weight and less than or equal to 3.5% by weight of CaO, greater than or equal to 2.0% by weight and less than or equal to 3.5% by weight of CaO, greater than or equal to 2.5% by weight and less than or equal to 3.5% by weight of CaO, greater than or equal to 3.0% by weight and less than or equal to 3.5% by weight of CaO, greater than ... 0.0 wt% CaO, greater than or equal to 0.5 wt% and less than or equal to 3.0 wt% CaO, greater than or equal to 1.0 wt% and less than or equal to 3.0 wt% CaO, greater than or equal to 1.5 wt% and less than or equal to 3.0 wt% CaO, greater than or equal to 2.0 wt% and less than or equal to 3.0 wt% CaO, greater than or equal to 2.5 wt% and less than or equal to 3.0 wt% CaO, greater than 0 wt% and less than or equal to 2.5 wt% CaO, greater than or equal to 0.05 wt% and less than or equal to 2.5 wt% CaO, greater than or equal to 0.1 wt% and less than or equal to 2.5 wt% CaO, greater than or equal to 0.5 wt% and less than or equal to 2.5% by weight of CaO, greater than or equal to 1.0% by weight and less than or equal to 2.5% by weight of CaO, greater than or equal to 1.5% by weight and less than or equal to 2.5% by weight of CaO, greater than or equal to 2.0% by weight and less than or equal to 2.5% by weight of CaO, greater than 0% by weight and less than or equal to 2.0% by weight of CaO, greater than 0.1% by weight and less than or equal to 2.0% by weight of CaO, greater than or equal to 0.5% by weight and less than or equal to 2.0% by weight of CaO, greater than or equal to 1.0% by weight and less than or equal to 2.0% by weight of CaO, greater than 1.5% by weight and less than or equal to 2.0% by weight of CaO, greater than 0% by weight of CaO. The range includes CaO concentrations of 1.5% by weight or less, 0.1% by weight or less than 1.5% by weight, 0.5% by weight or less than 1.5% by weight, 1.0% by weight or less than 1.5% by weight, 0% by weight or less than 1.0% by weight, 0.1% by weight or less than 1.0% by weight, 0.5% by weight or less than 1.0% by weight, 0% by weight or less than 0.5% by weight, or even 0.1% by weight or less than 0.5% by weight. It should be understood that the above range includes all sub-ranges within the explicitly disclosed range.
[0149] It has been found that ZrO2 can improve the stability of glass (and the resulting glass-ceramics) by significantly reducing glass devitrification during forming and lowering the liquidus temperature. At concentrations above 8 wt%, ZrSiO4 can form the main liquidus phase at high temperatures, which significantly reduces the liquidus viscosity. The addition of ZrO2 also contributes to the formation of clear glass (and the resulting glass-ceramics) and improves the chemical durability of the glass-ceramics. The addition of ZrO2 also helps reduce the crystallite size of the glass-ceramics, which facilitates the formation of clear glass-ceramics where high transparency is required. It has been found that the inclusion of ZrO2 in glass (and the resulting glass-ceramics), combined with the slightly higher lithium content in the glass and glass-ceramics described herein, can produce higher compressive stress and central tensile strength after chemical tempering without unduly affecting the melting behavior of the glass. Without being bound by any particular theory, it is considered that during the formation of glass-ceramics by heat treatment (which will be described in further detail herein), ZrO2 helps to distribute lithium in the residual amorphous glass phase of the glass-ceramics. Therefore, more lithium is present in the residual amorphous glass phase and readily exchanged with sodium and potassium during the chemical tempering process.
[0150] In embodiments, the glass and glass-ceramic contain greater than or equal to 0.5 wt% and less than or equal to 20 wt% of ZrO2, greater than or equal to 1.0 wt% and less than or equal to 20 wt% of ZrO2, greater than or equal to 1.5 wt% and less than or equal to 20 wt% of ZrO2, greater than or equal to 2.0 wt% and less than or equal to 20 wt% of ZrO2, greater than or equal to 2.5 wt% and less than or equal to 20 wt% of ZrO2, greater than or equal to 3.0 wt% and less than or equal to 20 wt% of ZrO2, greater than or equal to 3.5 wt% and less than or equal to 20 wt% of ZrO2, greater than or equal to 4.0 wt% and less than or equal to 20 wt% of ZrO2, greater than or equal to ZrO2 concentrations of 0.5 wt% and less than or equal to 19 wt%, 1.0 wt% and less than or equal to 19 wt%, 1.5 wt% and less than or equal to 19 wt%, 2.0 wt% and less than or equal to 19 wt%, 2.5 wt% and less than or equal to 19 wt%, 3.0 wt% and less than or equal to 19 wt%, 3.5 wt% and less than or equal to 19 wt%, 4.0 wt% and less than or equal to 19 wt%, and 0.5 wt% and less than or equal to 18 wt% ZrO2, greater than or equal to 1.0 wt% and less than or equal to 18 wt% ZrO2, greater than or equal to 1.5 wt% and less than or equal to 18 wt% ZrO2, greater than or equal to 2.0 wt% and less than or equal to 18 wt% ZrO2, greater than or equal to 2.5 wt% and less than or equal to 18 wt% ZrO2, greater than or equal to 3.0 wt% and less than or equal to 18 wt% ZrO2, greater than or equal to 3.5 wt% and less than or equal to 18 wt% ZrO2, greater than or equal to 4.0 wt% and less than or equal to 18 wt% ZrO2, greater than or equal to 0.5 wt% and less than or equal to 17 wt% ZrO2, greater than or equal to 1.0 wt% and less than or equal to 18 wt% ZrO2, greater than or equal to 1.0 wt% and less than or equal to 18 wt% ZrO2, greater than or equal to 1.0 wt% and less than or equal to 18 wt% ZrO2, greater than or equal to 1.0 wt% and less than or equal to 18 wt% ZrO2, greater than or equal to 1.5 ... ZrO2 equal to 17 wt%, greater than or equal to 1.5 wt% and less than or equal to 17 wt%, greater than or equal to 2.0 wt% and less than or equal to 17 wt%, greater than or equal to 2.5 wt% and less than or equal to 17 wt%, greater than or equal to 3.0 wt% and less than or equal to 17 wt%, greater than or equal to 3.5 wt% and less than or equal to 17 wt%, greater than or equal to 4.0 wt% and less than or equal to 17 wt%, greater than or equal to 0.5 wt% and less than or equal to 16 wt%, greater than or equal to 1.0 wt% and less than or equal to 16 wt%, greater than or equal to 1.5% by weight and less than or equal to 16% by weight of ZrO2, greater than or equal to 2.0% by weight and less than or equal to 16% by weight of ZrO2, greater than or equal to 2.5% by weight and less than or equal to 16% by weight of ZrO2, greater than or equal to 3.0% by weight and less than or equal to 16% by weight of ZrO2, greater than or equal to 3.5% by weight and less than or equal to 16% by weight of ZrO2, greater than or equal to 4.0% by weight and less than or equal to 16% by weight of ZrO2, greater than or equal to 0%. 5% by weight and less than or equal to 15% by weight of ZrO2, greater than or equal to 1.0% by weight and less than or equal to 15% by weight of ZrO2, greater than or equal to 1.5% by weight and less than or equal to 15% by weight of ZrO2, greater than or equal to 2.0% by weight and less than or equal to 15% by weight of ZrO2, greater than or equal to 2.5% by weight and less than or equal to 15% by weight of ZrO2, greater than or equal to 3.0% by weight and less than or equal to 15% by weight of ZrO2, greater than or equal to 3.ZrO2 of 5% by weight and less than or equal to 15% by weight, ZrO2 of 4% by weight and less than or equal to 15% by weight, ZrO2 of 5% by weight and less than or equal to 15% by weight, ZrO2 of 6% by weight and less than or equal to 15% by weight, ZrO2 of 7% by weight and less than or equal to 15% by weight, ZrO2 of 8% by weight and less than or equal to 15% by weight, ZrO2 of 9% by weight and less than or equal to 15% by weight, ZrO2 of 10% by weight and less than or equal to 15% by weight, ZrO2 of 11% by weight and less than or equal to 15% by weight, ZrO2 of 12 ... ZrO2 concentrations of % and less than or equal to 15 wt%, % and greater than 13 wt% and less than or equal to 15 wt%, % and greater than 14 wt% and less than or equal to 15 wt%, % and greater than 4 wt% and less than or equal to 14 wt%, % and greater than or equal to 5 wt% and less than or equal to 14 wt%, % and greater than or equal to 6 wt% and less than or equal to 14 wt%, % and greater than or equal to 7 wt% and less than or equal to 14 wt%, % and greater than or equal to 8 wt% and less than or equal to 14 wt%, % and greater than or equal to 9 wt% and less than or equal to 14 wt%, and % and greater than or equal to 10 wt% and less than 15 wt%. ZrO2 of 14% by weight or more, greater than or equal to 11% by weight and less than or equal to 14% by weight, greater than or equal to 12% by weight and less than or equal to 14% by weight, greater than or equal to 4% by weight and less than or equal to 12% by weight, greater than or equal to 5% by weight and less than or equal to 12% by weight, greater than or equal to 6% by weight and less than or equal to 12% by weight, greater than or equal to 7% by weight and less than or equal to 12% by weight, greater than or equal to 8% by weight and less than or equal to 12% by weight, greater than or equal to 9% by weight and less than or equal to 12% by weight, greater than or equal to 10% by weight and less than or equal to 1% by weight, and less than or equal to 1% by weight. The range includes 2% by weight of ZrO2, greater than or equal to 4% by weight and less than or equal to 10% by weight of ZrO2, greater than or equal to 5% by weight and less than or equal to 10% by weight of ZrO2, greater than or equal to 6% by weight and less than or equal to 10% by weight of ZrO2, greater than or equal to 7% by weight and less than or equal to 10% by weight of ZrO2, greater than or equal to 8% by weight and less than or equal to 10% by weight of ZrO2, greater than or equal to 4% by weight and less than or equal to 9% by weight of ZrO2, greater than or equal to 5% by weight and less than or equal to 9% by weight of ZrO2, greater than or equal to 6% by weight and less than or equal to 9% by weight of ZrO2, or greater than or equal to 7% by weight and less than or equal to 9% by weight of ZrO2. It should be understood that the above range includes all sub-ranges within the explicitly disclosed range.
[0151] Furthermore, it has been determined that by balancing the amounts of Li₂O and ZrO₂ in the glass and the resulting glass-ceramic, the central stretching generated in the glass-ceramic via ion exchange can be maximized. Specifically, it has been found that when the ratio of Li₂O (wt%) to ZrO₂ (wt%) in the glass and the resulting glass-ceramic (i.e., Li₂O:ZrO₂) is greater than or equal to 1.10 to less than or equal to 5.0, the central stretching in the glass-ceramic strengthened by ion exchange can be maximized. In this regard, without being constrained by any particular theory, it is considered that compositions with Li₂O to ZrO₂ ratios within this range maximize the amount of Li₂O in the residual amorphous glass phase of the glass-ceramic, which in turn allows for more ion exchange between the smaller lithium ions in the residual amorphous glass phase and the larger sodium and / or potassium ions from the ion exchange bath, thereby resulting in greater central stretching in the glass-ceramic.
[0152] Therefore, in some embodiments, the ratio of Li2O to ZrO2 in the glass and glass ceramic is greater than or equal to 1.10 to less than or equal to 5.0, greater than or equal to 1.10 to less than or equal to 4.5, greater than or equal to 1.10 to less than or equal to 4.0, greater than or equal to 1.10 to less than or equal to 3.5, greater than or equal to 1.10 to less than or equal to 3.0, greater than or equal to 1.10 to less than or equal to 2.5, or even greater than or equal to 1.10 to less than or equal to 2.0. In some embodiments, the ratio of Li₂O to ZrO₂ in the glass and glass-ceramic is greater than or equal to 1.10 and less than or equal to 1.90, greater than or equal to 1.15 and less than or equal to 1.90, greater than or equal to 1.20 and less than or equal to 1.90, greater than or equal to 1.25 and less than or equal to 1.90, greater than or equal to 1.30 and less than or equal to 1.90, greater than or equal to 1.35 and less than or equal to 1.90, greater than or equal to 1.40 and less than or equal to 1.90, greater than or equal to 1.45 and less than or equal to 1.90, or greater than or equal to 1.50 and less than or equal to 1. 90, greater than or equal to 1.55 to less than or equal to 1.90, greater than or equal to 1.60 to less than or equal to 1.90, greater than or equal to 1.65 to less than or equal to 1.90, greater than or equal to 1.70 to less than or equal to 1.90, greater than or equal to 1.75 to less than or equal to 1.90, greater than or equal to 1.80 to less than or equal to 1.90, greater than or equal to 1.10 to less than or equal to 1.85, greater than or equal to 1.15 to less than or equal to 1.85, greater than or equal to 1.20 to less than or equal to 1.85, greater than or equal to 1.25 to less than or equal to 1.85, greater than or equal to... From 1.30 to less than or equal to 1.85, greater than or equal to 1.35 to less than or equal to 1.85, greater than or equal to 1.40 to less than or equal to 1.85, greater than or equal to 1.45 to less than or equal to 1.85, greater than or equal to 1.50 to less than or equal to 1.85, greater than or equal to 1.55 to less than or equal to 1.85, greater than or equal to 1.60 to less than or equal to 1.85, greater than or equal to 1.65 to less than or equal to 1.85, greater than or equal to 1.70 to less than or equal to 1.85, greater than or equal to 1.75 to less than or equal to 1.85, greater than or equal to 1.10 to Less than or equal to 1.80, greater than or equal to 1.15 to less than or equal to 1.80, greater than or equal to 1.20 to less than or equal to 1.80, greater than or equal to 1.25 to less than or equal to 1.80, greater than or equal to 1.30 to less than or equal to 1.80, greater than or equal to 1.35 to less than or equal to 1.80, greater than or equal to 1.40 to less than or equal to 1.80, greater than or equal to 1.45 to less than or equal to 1.80, greater than or equal to 1.50 to less than or equal to 1.80, greater than or equal to 1.55 to less than or equal to 1.80, greater than or equal to 1.60 to less than or equal to 1.80, greater than or equal to 1.65 to less than or equal to 1.80, greater than or equal to 1.70 to less than or equal to 1.80, greater than or equal to 1.10 to less than or equal to 1.75, greater than or equal to 1.15 to less than or equal to 1.75, greater than or equal to 1.20 to less than or equal to 1.75, greater than or equal to 1.25 to less than or equal to 1.75, greater than or equal to 1.30 to less than or equal to 1.75, greater than or equal to 1.35 to less than or equal to 1.75, greater than or equal to 1.40 to less than or equal to 1.75, greater than or equal to 1.45 to less than or equal to 1.75, greater than or equal to 1.50 to less than or equal to 1.75, greater than or equal to 1.55 to less than or equal to 1.75, greater than or equal to 1. 60 to less than or equal to 1.75, greater than or equal to 1.65 to less than or equal to 1.75, greater than or equal to 1.10 to less than or equal to 1.70, greater than or equal to 1.15 to less than or equal to 1.70, greater than or equal to 1.20 to less than or equal to 1.70, greater than or equal to 1.25 to less than or equal to 1.70, greater than or equal to 1.30 to less than or equal to 1.70, greater than or equal to 1.35 to less than or equal to 1.70, greater than or equal to 1.40 to less than or equal to 1.70, greater than or equal to 1.45 to less than or equal to 1.70, greater than or equal to 1.50 to less than or equal to 1.70, greater than or equal to 1.55 to less than or equal to 1.70, greater than or equal to 1.60 to less than or equal to 1. 70, greater than or equal to 1.10 to less than or equal to 1.65, greater than or equal to 1.15 to less than or equal to 1.65, greater than or equal to 1.20 to less than or equal to 1.65, greater than or equal to 1.25 to less than or equal to 1.65, greater than or equal to 1.30 to less than or equal to 1.65, greater than or equal to 1.35 to less than or equal to 1.65, greater than or equal to 1.40 to less than or equal to 1.65, greater than or equal to 1.45 to less than or equal to 1.65, greater than or equal to 1.50 to less than or equal to 1.65, greater than or equal to 1.10 to less than or equal to 1.60, greater than or equal to 1.15 to less than or equal to 1.60, greater than or equal to 1. 20 to less than or equal to 1.60, greater than or equal to 1.25 to less than or equal to 1.60, greater than or equal to 1.30 to less than or equal to 1.60, greater than or equal to 1.35 to less than or equal to 1.60, greater than or equal to 1.40 to less than or equal to 1.60, greater than or equal to 1.45 to less than or equal to 1.60, greater than or equal to 1.50 to less than or equal to 1.60, greater than or equal to 1.55 to less than or equal to 1.60, greater than or equal to 1.10 to less than or equal to 1.55, greater than or equal to 1.15 to less than or equal to 1.55, greater than or equal to 1.20 to less than or equal to 1.55, greater than or equal to 1.25 to less than or equal to 1.55, greater than or equal to 1.30 to less than or equal to 1.55. Greater than or equal to 1.35 and less than or equal to 1.55, greater than or equal to 1.40 and less than or equal to 1.55, greater than or equal to 1.45 and less than or equal to 1.55, or even greater than or equal to 1.50 and less than or equal to 1.55. It should be understood that the above ranges include all sub-ranges within the explicitly disclosed range.
[0153] The glasses and glass-ceramics described herein also contain P2O5. P2O5 can act as a nucleating agent to produce bulk nucleation. As used herein, bulk nucleation produces nucleated glasses with one or more crystalline phases. If the concentration of P2O5 is too low, the glass will indeed crystallize, but only at higher temperatures (due to lower viscosity) and from the surface inward, producing a weak and generally deformable bulk. However, if the concentration of P2O5 is too high, devitrification during cooling during glass sheet forming can be difficult to control. Examples of glass and glass-ceramics contain greater than or equal to 1.0 wt% and less than or equal to 8.0 wt% of P2O5, greater than or equal to 1.5 wt% and less than or equal to 8.0 wt% of P2O5, greater than or equal to 2.0 wt% and less than or equal to 8.0 wt% of P2O5, greater than or equal to 2.5 wt% and less than or equal to 8.0 wt% of P2O5, greater than or equal to 3.0 wt% and less than or equal to 8.0 wt% of P2O5, greater than or equal to 1.0 wt% and less than or equal to 7.5 wt% of P2O5, and greater than or equal to 1.5 wt% and less than or equal to 7.5 wt% of P2O5. P2O5 by weight%, greater than or equal to 2.0% by weight and less than or equal to 7.5% by weight, greater than or equal to 2.5% by weight and less than or equal to 7.5% by weight, greater than or equal to 3.0% by weight and less than or equal to 7.5% by weight, greater than or equal to 1.0% by weight and less than or equal to 7.0% by weight, greater than or equal to 1.5% by weight and less than or equal to 7.0% by weight, greater than or equal to 2.0% by weight and less than or equal to 7.0% by weight, greater than or equal to 2.5% by weight and less than or equal to 7.0% by weight. P2O5, greater than or equal to 3.0 wt% and less than or equal to 7.0 wt%, greater than or equal to 1.0 wt% and less than or equal to 6.5 wt%, greater than or equal to 1.5 wt% and less than or equal to 6.5 wt%, greater than or equal to 2.0 wt% and less than or equal to 6.5 wt%, greater than or equal to 2.5 wt% and less than or equal to 6.5 wt%, greater than or equal to 3.0 wt% and less than or equal to 6.5 wt%, greater than or equal to 1.0 wt% and less than or equal to 6.0 wt%, greater than The following concentrations of P2O5 are specified: 1.5 wt% and less than or equal to 6.0 wt%; 2.0 wt% and less than or equal to 6.0 wt%; 2.5 wt% and less than or equal to 6.0 wt%; 3.0 wt% and less than or equal to 6.0 wt%; 1.0 wt% and less than or equal to 5.5 wt%; 1.5 wt% and less than or equal to 5.5 wt%; 2.0 wt% and less than or equal to 5.5 wt%; and 2.0 wt% and less than or equal to 5.5 wt%.5% by weight and less than or equal to 5.5% by weight of P2O5, greater than or equal to 3.0% by weight and less than or equal to 5.5% by weight of P2O5, greater than or equal to 1.0% by weight and less than or equal to 5.0% by weight of P2O5, greater than or equal to 1.5% by weight and less than or equal to 5.0% by weight of P2O5, greater than or equal to 2.0% by weight and less than or equal to 5.0% by weight of P2O5, greater than or equal to 2.5% by weight and less than or equal to 5.0% by weight of P2O5, greater than or equal to 3% by weight of P2O5, and less than or equal to 5% by weight of P2O5. 0.0 wt% and less than or equal to 5.0 wt% of P2O5, greater than or equal to 1.0 wt% and less than or equal to 4.5 wt% of P2O5, greater than or equal to 1.5 wt% and less than or equal to 4.5 wt% of P2O5, greater than or equal to 2.0 wt% and less than or equal to 4.5 wt% of P2O5, greater than or equal to 2.25 wt% and less than or equal to 4.5 wt% of P2O5, greater than or equal to 2.5 wt% and less than or equal to 4.5 wt% of P2O5, greater than or equal to 3.0 wt% and less than or equal to 4.5 wt% of P2O5, greater than or equal to 1.0 wt% and less than or equal to 4.0 wt% of P2O5, greater than or equal to 1.5 wt% and less than or equal to 4.0 wt% of P2O5, greater than or equal to 2.0 wt% and less than or equal to 4.0 wt% of P2O5, greater than or equal to 2.5 wt% and less than or equal to 4.0 wt% of P2O5, greater than or equal to 3.0 wt% and less than or equal to 4.0 wt% of P2O5, greater than or equal to... The range includes P2O5 concentrations of 1.0 wt% and less than or equal to 3.5 wt%, greater than or equal to 1.5 wt% and less than or equal to 3.5 wt%, greater than or equal to 2.0 wt% and less than or equal to 3.5 wt%, greater than or equal to 2.25 wt% and less than or equal to 3.5 wt%, greater than or equal to 2.5 wt% and less than or equal to 3.5 wt%, or even greater than or equal to 3.0 wt% and less than or equal to 3.5 wt%. It should be understood that the above range includes all sub-ranges within the explicitly disclosed range.
[0154] In the embodiments, the glass or glass-ceramic may also contain MgO. Divalent cations (e.g., divalent cations from alkaline earth metal oxides and ZnO) generally improve the melting behavior of the glass. Without being bound by theory, it is believed that the addition of MgO can enter the residual amorphous glass phase. It is believed that the addition of MgO into the residual amorphous glass phase can reduce the diffusivity of alkali metal ions in the glass, for example, during ion exchange. Therefore, the MgO content in the embodiments described herein is limited to less than or equal to 5.0% by weight to avoid any adverse effects on ion exchange performance. In the embodiments, the glass and glass-ceramic contain greater than or equal to 0 wt% and less than or equal to 5.0 wt% of MgO, greater than or equal to 0 wt% and less than or equal to 4.5 wt% of MgO, greater than or equal to 0 wt% and less than or equal to 4.0 wt% of MgO, greater than or equal to 0 wt% and less than or equal to 3.5 wt% of MgO, greater than or equal to 0 wt% and less than or equal to 3.0 wt% of MgO, greater than or equal to 0 wt% and less than or equal to 2.5 wt% of MgO, greater than or equal to 0 wt% and less than or equal to 2.0 wt% of MgO, greater than or equal to 0 wt% and less than or equal to 1.5 wt% of MgO, greater than or equal to 0 wt% and less than or equal to 1.0 wt% of MgO, greater than or equal to 0 wt% and less than or equal to 0.5 wt% of MgO, and greater than The glass and glass-ceramics may contain 0.1% to 5.0% by weight, or more than 0.1% to 4.5% by weight, or more than 0.1% to 4.0% by weight, or more than 0.1% to 3.5% by weight, or more than 0.1% to 3.0% by weight, or more than 0.1% to 2.5% by weight, or more than 0.1% to 2.0% by weight, or more than 0.1% to 1.5% by weight, or more than 0.1% to 1.0% by weight, or more than 0.1% to 0.5% by weight. In the embodiments, the glass and glass-ceramics do not contain MgO. In the embodiments, the glass and glass-ceramics are substantially free of MgO. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0155] In embodiments, the glass or glass-ceramic may also contain SrO. As noted herein, divalent cations (e.g., divalent cations from alkaline earth metal oxides and ZnO) generally improve the melting behavior of glass. Without being bound by theory, it is believed that SrO (when present) can increase the amount of residual glass in the resulting glass-ceramic. In embodiments, the glass and glass-ceramic contain greater than or equal to 0 wt% and less than or equal to 10.0 wt% of SrO, greater than or equal to 0 wt% and less than or equal to 9.5 wt% of SrO, greater than or equal to 0 wt% and less than or equal to 9.0 wt% of SrO, greater than or equal to 0 wt% and less than or equal to 8.5 wt% of SrO, greater than or equal to 0 wt% and less than or equal to 8.0 wt% of SrO, greater than or equal to 0 wt% and less than or equal to 7.5 wt% of SrO, greater than or equal to 0 wt% and less than or equal to 7.0 wt% of SrO, and greater than or equal to 0 wt% and less than or equal to 6.5 wt% of SrO. SrO3 concentrations greater than or equal to 0% by weight and less than or equal to 6.0% by weight; SrO3 concentrations greater than or equal to 0% by weight and less than or equal to 5.5% by weight; SrO3 concentrations greater than or equal to 0% by weight and less than or equal to 5.0% by weight; SrO3 concentrations greater than or equal to 0% by weight and less than or equal to 4.5% by weight; SrO3 concentrations greater than or equal to 0% by weight and less than or equal to 4.0% by weight; SrO3 concentrations greater than or equal to 0% by weight and less than or equal to 3.5% by weight; SrO3 concentrations greater than or equal to 0% by weight and less than or equal to 3.0% by weight; SrO3 concentrations greater than or equal to 0% by weight and less than or equal to 2.5% by weight; SrO3 concentrations greater than or equal to 0% by weight and less than or equal to 6.0% by weight; SrO3 concentrations greater than or equal to 0% by weight and less than or equal to 6.0% by weight; SrO3 concentrations greater than or equal to 0% by weight and less than or equal to 6.0% by weight; SrO3 concentrations greater than or equal to 0% by weight and less than or equal to 3.5% by weight; SrO3 concentrations greater than or equal to 0% by weight and less than or equal to 3.0% by weight; SrO3 concentrations greater than or equal to 0% by weight and less than or equal to 6 ... The following concentrations of SrO are specified: 2.0 wt%; greater than or equal to 0 wt% and less than or equal to 1.5 wt%; greater than or equal to 0 wt% and less than or equal to 1.0 wt%; greater than or equal to 0 wt% and less than or equal to 0.5 wt%; greater than or equal to 0.1 wt% and less than or equal to 10.0 wt%; greater than or equal to 0.1 wt% and less than or equal to 9.5 wt%; greater than or equal to 0.1 wt% and less than or equal to 9.0 wt%; greater than or equal to 0.1 wt% and less than or equal to 8.5 wt%; and greater than or equal to 0.1 wt% and less than or equal to 8.0 wt%. SrO by weight%, greater than or equal to 0.1% and less than or equal to 7.5% by weight, greater than or equal to 0.1% and less than or equal to 7.0% by weight, greater than or equal to 0.1% and less than or equal to 6.5% by weight, greater than or equal to 0.1% and less than or equal to 6.0% by weight, greater than or equal to 0.1% and less than or equal to 5.5% by weight, greater than or equal to 0.1% and less than or equal to 5.0% by weight, greater than or equal to 0.1% and less than or equal to 4.5% by weight, greater than or equal to 0.1% and less than or equal to 4.5% by weight, greater than or equal to 0.1% and less than or equal to 4.5% by weight.The range includes 0% by weight of SrO, greater than or equal to 0.1% by weight and less than or equal to 3.5% by weight of SrO, greater than or equal to 0.1% by weight and less than or equal to 3.0% by weight of SrO, greater than or equal to 0.1% by weight and less than or equal to 2.5% by weight of SrO, greater than or equal to 0.1% by weight and less than or equal to 2.0% by weight of SrO, greater than or equal to 0.1% by weight and less than or equal to 1.5% by weight of SrO, greater than or equal to 0.1% by weight and less than or equal to 1.0% by weight of SrO, and greater than or equal to 0.1% by weight and less than or equal to 0.5% by weight of SrO. In embodiments, the glass and glass-ceramics do not contain SrO. In embodiments, the glass and glass-ceramics are substantially free of SrO. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0156] In embodiments, the glass or glass-ceramic may also contain BaO. As noted herein, divalent cations (e.g., divalent cations from alkaline earth metal oxides and ZnO) generally improve the melting behavior of glass. Without being bound by theory, it is believed that BaO (when present) can increase the amount of residual glass in the resulting glass-ceramic. In embodiments, the glass and glass-ceramic contain greater than or equal to 0 wt% and less than or equal to 10.0 wt% BaO, greater than or equal to 0 wt% and less than or equal to 9.5 wt% BaO, greater than or equal to 0 wt% and less than or equal to 9.0 wt% BaO, greater than or equal to 0 wt% and less than or equal to 8.5 wt% BaO, greater than or equal to 0 wt% and less than or equal to 8.0 wt% BaO, greater than or equal to 0 wt% and less than or equal to 7.5 wt% BaO, greater than or equal to 0 wt% and less than or equal to 7.0 wt% BaO, and greater than or equal to 0 wt% and less than or equal to 6.5 wt% BaO. BaO with a content greater than or equal to 0% by weight and less than or equal to 6.0% by weight; BaO with a content greater than or equal to 0% by weight and less than or equal to 5.5% by weight; BaO with a content greater than or equal to 0% by weight and less than or equal to 5.0% by weight; BaO with a content greater than or equal to 0% by weight and less than or equal to 4.5% by weight; BaO with a content greater than or equal to 0% by weight and less than or equal to 4.0% by weight; BaO with a content greater than or equal to 0% by weight and less than or equal to 3.5% by weight; BaO with a content greater than or equal to 0% by weight and less than or equal to 3.0% by weight; BaO with a content greater than or equal to 0% by weight and less than or equal to 2.5% by weight; BaO with a content greater than or equal to 0% by weight and less than or equal to 6.0 ... BaO at 2.0 wt%, greater than or equal to 0 wt% and less than or equal to 1.5 wt%, greater than or equal to 0 wt% and less than or equal to 1.0 wt%, greater than or equal to 0 wt% and less than or equal to 0.5 wt%, greater than or equal to 0.1 wt% and less than or equal to 10.0 wt%, greater than or equal to 0.1 wt% and less than or equal to 9.5 wt%, greater than or equal to 0.1 wt% and less than or equal to 9.0 wt%, greater than or equal to 0.1 wt% and less than or equal to 8.5 wt%, greater than or equal to 0.1 wt% and less than or equal to 8.0 wt%. BaO by weight%, greater than or equal to 0.1% and less than or equal to 7.5% by weight, greater than or equal to 0.1% and less than or equal to 7.0% by weight, greater than or equal to 0.1% and less than or equal to 6.5% by weight, greater than or equal to 0.1% and less than or equal to 6.0% by weight, greater than or equal to 0.1% and less than or equal to 5.5% by weight, greater than or equal to 0.1% and less than or equal to 5.0% by weight, greater than or equal to 0.1% and less than or equal to 4.5% by weight, greater than or equal to 0.1% and less than or equal to 4.The range includes 0% by weight of BaO, greater than or equal to 0.1% by weight and less than or equal to 3.5% by weight of BaO, greater than or equal to 0.1% by weight and less than or equal to 3.0% by weight of BaO, greater than or equal to 0.1% by weight and less than or equal to 2.5% by weight of BaO, greater than or equal to 0.1% by weight and less than or equal to 2.0% by weight of BaO, greater than or equal to 0.1% by weight and less than or equal to 1.5% by weight of BaO, greater than or equal to 0.1% by weight and less than or equal to 1.0% by weight of BaO, and greater than or equal to 0.1% by weight and less than or equal to 0.5% by weight of BaO. In embodiments, the glass and glass-ceramics do not contain BaO. In embodiments, the glass and glass-ceramics are substantially free of BaO. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0157] In embodiments, the glass or glass-ceramic may further comprise ZnO. As noted herein, divalent cations (e.g., divalent cations from ZnO and alkaline earth metal oxides) improve the melting behavior of the glass. In embodiments, the glass and glass-ceramic comprise greater than or equal to 0 wt% and less than or equal to 10.0 wt% ZnO, greater than or equal to 0 wt% and less than or equal to 9.5 wt% ZnO, greater than or equal to 0 wt% and less than or equal to 9.0 wt% ZnO, greater than or equal to 0 wt% and less than or equal to 8.5 wt% ZnO, greater than or equal to 0 wt% and less than or equal to 8.0 wt% ZnO, greater than or equal to 0 wt% and less than or equal to 7.5 wt% ZnO, greater than or equal to 0 wt% and less than or equal to 7.0 wt% ZnO, greater than or equal to 0 wt% and less than or equal to 6 ...7.0 wt% ZnO, greater than or equal to 0 ZnO with a weight percentage of 6.0% or less, greater than or equal to 0% and less than or equal to 5.5% by weight, greater than or equal to 0% and less than or equal to 5.0% by weight, greater than or equal to 0% and less than or equal to 4.5% by weight, greater than or equal to 0% and less than or equal to 4.0% by weight, greater than or equal to 0% and less than or equal to 3.5% by weight, greater than or equal to 0% and less than or equal to 3.0% by weight, greater than or equal to 0% and less than or equal to 2.5% by weight, greater than or equal to 0% and less than or equal to 2.0% by weight, and greater than... ZnO of 0% or less than or equal to 1.5% by weight, ZnO of 0% or less than or equal to 1.0% by weight, ZnO of 0% or less than or equal to 0.5% by weight, ZnO of 0.1% or less than or equal to 10.0% by weight, ZnO of 0.1% or less than or equal to 9.5% by weight, ZnO of 0.1% or less than or equal to 9.0% by weight, ZnO of 0.1% or less than or equal to 8.5% by weight, ZnO of 0.1% or less than or equal to 8.0% by weight, ZnO of 0.1% or less than or equal to 10 ... ZnO of 7.5% by weight or more, greater than or equal to 0.1% by weight and less than or equal to 7.0% by weight, greater than or equal to 0.1% by weight and less than or equal to 6.5% by weight, greater than or equal to 0.1% by weight and less than or equal to 6.0% by weight, greater than or equal to 0.1% by weight and less than or equal to 5.5% by weight, greater than or equal to 0.1% by weight and less than or equal to 5.0% by weight, greater than or equal to 0.1% by weight and less than or equal to 4.5% by weight, greater than or equal to 0.1% by weight and less than or equal to 4.0% by weight, and greater than or equal to 0.1% by weight and less than or equal to 3%.The amounts are: 5% by weight of ZnO, greater than or equal to 0.1% by weight and less than or equal to 3.0% by weight of ZnO, greater than or equal to 0.1% by weight and less than or equal to 2.5% by weight of ZnO, greater than or equal to 0.1% by weight and less than or equal to 2.0% by weight of ZnO, greater than or equal to 0.1% by weight and less than or equal to 1.5% by weight of ZnO, greater than or equal to 0.1% by weight and less than or equal to 1.0% by weight of ZnO, and greater than or equal to 0.1% by weight and less than or equal to 0.5% by weight of ZnO. In embodiments, the glass and glass-ceramics do not contain ZnO. In embodiments, the glass and glass-ceramics are substantially free of ZnO. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0158] In embodiments, the glass or glass-ceramic may further contain B2O3. Without being bound by theory, it is believed that the addition of B2O3 can distribute it into the remaining amorphous glass. It is also believed that the addition of B2O3 can reduce the viscosity of the glass at the ceramization temperature. In embodiments, the glass and glass-ceramic contain greater than or equal to 0 wt% and less than or equal to 2.0 wt% of B2O3, greater than or equal to 0 wt% and less than or equal to 1.5 wt% of B2O3, greater than or equal to 0 wt% and less than or equal to 1.0 wt% of B2O3, greater than or equal to 0 wt% and less than or equal to 0.5 wt% of B2O3, greater than or equal to 0.1 wt% and less than or equal to 2.0 wt% of B2O3, greater than or equal to 0.1 wt% and less than or equal to 1.5 wt% of B2O3, greater than or equal to 0.1 wt% and less than or equal to 1.0 wt% of B2O3, or even greater than or equal to 0.1 wt% and less than or equal to 0.5 wt% of B2O3. In the embodiments, the glass and glass-ceramics do not contain B2O3. In the embodiments, the glass and glass-ceramics are substantially free of B2O3. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0159] Fe2O3 can lower the melting point of glass and glass-ceramics. However, adding too much Fe2O3 may alter the color of the glass and glass-ceramics. In this embodiment, the glass and glass-ceramics do not contain Fe2O3. In this embodiment, the glass and glass-ceramics are substantially free of Fe2O3. In embodiments, the glass and glass-ceramic contain greater than 0.0 wt% and less than or equal to 1.0 wt% of Fe₂O₃, greater than or equal to 0 wt% and less than or equal to 0.5 wt% of Fe₂O₃, greater than 0.0 wt% and less than or equal to 0.3 wt% of Fe₂O₃, greater than or equal to 0.0 wt% and less than or equal to 0.2 wt% of Fe₂O₃, greater than 0.0 wt% and less than or equal to 0.1 wt% of Fe₂O₃, greater than 0.03 wt% and less than or equal to 1.0 wt% of Fe₂O₃, greater than or equal to 0.03 wt% and less than or equal to 0.5 wt% of Fe₂O₃, greater than 0.03 wt% and less than or equal to 0.3 wt% of Fe₂O₃, greater than or equal to 0.03 wt% and less than or equal to 0.2 wt% of Fe₂O₃, or greater than 0.03 wt% and less than or equal to 0.1 wt% of Fe₂O₃. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0160] In embodiments, the glass or glass-ceramic may further comprise La2O3. Without being bound by theory, it is believed that the addition of La2O3 can increase the refractive index of the glass and the resulting glass-ceramic. In embodiments, the glass and glass-ceramic comprise greater than or equal to 0 wt% and less than or equal to 10.0 wt% of La2O3, greater than or equal to 0 wt% and less than or equal to 9.5 wt% of La2O3, greater than or equal to 0 wt% and less than or equal to 9.0 wt% of La2O3, greater than or equal to 0 wt% and less than or equal to 8.5 wt% of La2O3, greater than or equal to 0 wt% and less than or equal to 8.0 wt% of La2O3, greater than or equal to 0 wt% and less than or equal to 7.5 wt% of La2O3, greater than or equal to 0 wt% and less than or equal to 7.0 wt% of La2O3, and greater than or equal to 0 wt% and less than or equal to 6.5 wt% of La2O3. La₂O₃ by weight%, greater than or equal to 0% by weight and less than or equal to 6.0% by weight, greater than or equal to 0% by weight and less than or equal to 5.5% by weight, greater than or equal to 0% by weight and less than or equal to 5.0% by weight, greater than or equal to 0% by weight and less than or equal to 4.5% by weight, greater than or equal to 0% by weight and less than or equal to 4.0% by weight, greater than or equal to 0% by weight and less than or equal to 3.5% by weight, greater than or equal to 0% by weight and less than or equal to 3.0% by weight, and greater than or equal to 0% by weight and less than or equal to 2.5% by weight. The following concentrations of La2O3 are specified: ≥0 wt% and ≤2.0 wt%; ≥0 wt% and ≤1.5 wt%; ≥0 wt% and ≤1.0 wt%; ≥0 wt% and ≤0.5 wt%; ≥0.1 wt% and ≤10.0 wt%; ≥0.1 wt% and ≤9.5 wt%; ≥0.1 wt% and ≤9.0 wt%; ≥0.1 wt% and ≤8.5 wt% of La2O3. O3, greater than or equal to 0.1 wt% and less than or equal to 8.0 wt% of La2O3, greater than or equal to 0.1 wt% and less than or equal to 7.5 wt% of La2O3, greater than or equal to 0.1 wt% and less than or equal to 7.0 wt% of La2O3, greater than or equal to 0.1 wt% and less than or equal to 6.5 wt% of La2O3, greater than or equal to 0.1 wt% and less than or equal to 6.0 wt% of La2O3, greater than or equal to 0.1 wt% and less than or equal to 5.5 wt% of La2O3, greater than or equal to 0.1 wt% and less than or equal to 5.0 wt% of La2O3, greater than or equal to 0.1 wt% and less than or equal to 4.The glass and glass-ceramic contain 5% by weight of La₂O₃, greater than or equal to 0.1% by weight and less than or equal to 4.0% by weight of La₂O₃, greater than or equal to 0.1% by weight and less than or equal to 3.5% by weight of La₂O₃, greater than or equal to 0.1% by weight and less than or equal to 3.0% by weight of La₂O₃, greater than or equal to 0.1% by weight and less than or equal to 2.5% by weight of La₂O₃, greater than or equal to 0.1% by weight and less than or equal to 2.0% by weight of La₂O₃, greater than or equal to 0.1% by weight and less than or equal to 1.5% by weight of La₂O₃, greater than or equal to 0.1% by weight and less than or equal to 1.0% by weight of La₂O₃, and greater than or equal to 0.1% by weight and less than or equal to 0.5% by weight of La₂O₃. In the embodiments, the glass and glass-ceramic do not contain La₂O₃. In the embodiments, the glass and glass-ceramic are substantially free of La₂O₃. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0161] In embodiments, the glass or glass-ceramic may further contain HfO2. Without being bound by theory, it is believed that the addition of HfO2 can at least partially replace ZrO2 in the composition. In embodiments, the glass and glass-ceramic contain greater than or equal to 0 wt% and less than or equal to 3.0 wt% HfO2, greater than or equal to 0 wt% and less than or equal to 2.5 wt% HfO2, greater than or equal to 0 wt% and less than or equal to 2.0 wt% HfO2, greater than or equal to 0 wt% and less than or equal to 1.5 wt% HfO2, greater than or equal to 0 wt% and less than or equal to 1.0 wt% HfO2, and greater than or equal to 0 wt% and less than or equal to 0.5 wt% HfO2. O2, greater than or equal to 0.1% to less than or equal to 3% by weight of HfO2, greater than or equal to 0.1% by weight and less than or equal to 2.5% by weight of HfO2, greater than or equal to 0.1% by weight and less than or equal to 2.0% by weight of HfO2, greater than or equal to 0.1% by weight and less than or equal to 1.5% by weight of HfO2, greater than or equal to 0.1% by weight and less than or equal to 1.0% by weight of HfO2, or even greater than or equal to 0.1% by weight and less than or equal to 0.5% by weight of HfO2. In embodiments, the glass and glass-ceramics do not contain HfO2. In embodiments, the glass and glass-ceramics are substantially free of HfO2. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0162] In embodiments, the glass or glass-ceramic may further contain Y₂O₃. Without being bound by theory, it is believed that adding Y₂O₃ can increase the refractive index of the glass and the resulting glass-ceramic. In embodiments, the glass and glass-ceramic contain greater than or equal to 0 wt% and less than or equal to 2.0 wt% of Y₂O₃, greater than or equal to 0 wt% and less than or equal to 1.5 wt% of Y₂O₃, greater than or equal to 0 wt% and less than or equal to 1.0 wt% of Y₂O₃, greater than or equal to 0 wt% and less than or equal to 0.5 wt% of Y₂O₃, greater than or equal to 0.1 wt% and less than or equal to 2.0 wt% of Y₂O₃, greater than or equal to 0.1 wt% and less than or equal to 1.5 wt% of Y₂O₃, greater than or equal to 0.1 wt% and less than or equal to 1.0 wt% of Y₂O₃, or even greater than or equal to 0.1 wt% and less than or equal to 0.5 wt% of Y₂O₃. In embodiments, the glass and glass-ceramic do not contain Y₂O₃. In the embodiments, the glass and glass-ceramics are substantially free of Y2O3. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0163] In the embodiments, the glass or glass-ceramic may further contain Ta₂O₅. Without being bound by theory, it is believed that the addition of Ta₂O₅ can increase the refractive index of the glass and the resulting glass-ceramic. It is also believed that the addition of Ta₂O₅ can increase the modulus of the glass and the resulting glass-ceramic. In embodiments, the glass and glass-ceramic contain greater than or equal to 0 wt% and less than or equal to 2.0 wt% of Ta₂O₅, greater than or equal to 0 wt% and less than or equal to 1.5 wt% of Ta₂O₅, greater than or equal to 0 wt% and less than or equal to 1.0 wt% of Ta₂O₅, greater than or equal to 0 wt% and less than or equal to 0.5 wt% of Ta₂O₅, greater than or equal to 0.1 wt% and less than or equal to 2.0 wt% of Ta₂O₅, greater than or equal to 0.1 wt% and less than or equal to 1.5 wt% of Ta₂O₅, greater than or equal to 0.1 wt% and less than or equal to 1.0 wt% of Ta₂O₅, or even greater than or equal to 0.1 wt% and less than or equal to 0.5 wt% of Ta₂O₅. In embodiments, the glass and glass-ceramic do not contain Ta₂O₅. In embodiments, the glass and glass-ceramic are substantially free of Ta₂O₅. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0164] In the embodiments, the glass or glass-ceramic may also contain GeO2. Without being bound by theory, it is believed that the addition of GeO2 can increase the refractive index of the glass and the resulting glass-ceramic. In embodiments, the glass and glass-ceramic contain greater than or equal to 0 wt% and less than or equal to 5.0 wt% of GeO2, greater than or equal to 0 wt% and less than or equal to 4.5 wt% of GeO2, greater than or equal to 0 wt% and less than or equal to 4.0 wt% of GeO2, greater than or equal to 0 wt% and less than or equal to 3.5 wt% of GeO2, greater than or equal to 0 wt% and less than or equal to 3.0 wt% of GeO2, greater than or equal to 0 wt% and less than or equal to 2.5 wt% of GeO2, greater than or equal to 0 wt% and less than or equal to 2.0 wt% of GeO2, greater than or equal to 0 wt% and less than or equal to 1.5 wt% of GeO2, greater than or equal to 0 wt% and less than or equal to 1.0 wt% of GeO2, greater than or equal to 0 wt% and less than or equal to 0.5 wt% of GeO2, and greater than or equal to... The amounts of GeO2 are 0.1 wt% and less than or equal to 5.0 wt%, greater than or equal to 0.1 wt% and less than or equal to 4.5 wt%, greater than or equal to 0.1 wt% and less than or equal to 4.0 wt%, greater than or equal to 0.1 wt% and less than or equal to 3.5 wt%, greater than or equal to 0.1 wt% and less than or equal to 3.0 wt%, greater than or equal to 0.1 wt% and less than or equal to 2.5 wt%, greater than or equal to 0.1 wt% and less than or equal to 2.0 wt%, greater than or equal to 0.1 wt% and less than or equal to 1.5 wt%, greater than or equal to 0.1 wt% and less than or equal to 1.0 wt%, or even greater than or equal to 0.1 wt% and less than or equal to 0.5 wt%. In the embodiments, the glass and glass ceramics do not contain GeO2. In the embodiments, the glass and glass-ceramics are substantially free of GeO2. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0165] In embodiments, the glass or glass-ceramic may further comprise TiO2. In embodiments, the glass and glass-ceramic comprise greater than or equal to 0 wt% and less than or equal to 2.0 wt% TiO2, greater than or equal to 0 wt% and less than or equal to 1.5 wt% TiO2, greater than or equal to 0 wt% and less than or equal to 1.0 wt% TiO2, greater than or equal to 0 wt% and less than or equal to 0.5 wt% TiO2, greater than or equal to 0.1 wt% and less than or equal to 2.0 wt% TiO2, greater than or equal to 0.1 wt% and less than or equal to 1.5 wt% TiO2, greater than or equal to 0.1 wt% and less than or equal to 1.0 wt% TiO2, or even greater than or equal to 0.1 wt% and less than or equal to 0.5 wt% TiO2. In embodiments, the glass and glass-ceramic do not comprise TiO2. In embodiments, the glass and glass-ceramic are substantially free of TiO2. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0166] In embodiments, the glass or glass-ceramic may further contain F. - Without being bound by theory, it is believed that the addition of fluorine can act as a nucleating agent and / or a clarifying agent. In embodiments, the glass and glass-ceramic may contain greater than or equal to 0% by weight and less than or equal to 1.5% by weight of fluorine. - F greater than or equal to 0% by weight and less than or equal to 1.0% by weight - F greater than or equal to 0% by weight and less than or equal to 0.5% by weight - F ≥ 0.1% by weight and ≤ 2.0% by weight - 0.1% by weight and less than or equal to 1.5% by weight of F - F greater than or equal to 0.1% by weight and less than or equal to 1.0% by weight - or even greater than or equal to 0.1% by weight and less than or equal to 0.5% by weight of F - In the embodiments, the glass and glass-ceramics do not contain F. - In the embodiments, the glass and glass-ceramics are substantially free of F. - It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0167] In embodiments, the glass or glass-ceramic may further comprise a chemical clarifying agent. Such clarifying agents include, but are not limited to, SnO2, As2O3, Sb2O3, SO3, F, Cl, and Br. In embodiments, the concentration of the chemical clarifying agent is maintained at a level of 3, 2, 1, or 0.5, >0% by weight. In embodiments, the chemical clarifying agent is SnO2 and the glass or glass-ceramic contains greater than or equal to 0 to less than or equal to 3% by weight of SnO2. In the embodiments, the glass or glass-ceramic contains greater than or equal to 0 wt% and less than or equal to 2.5 wt% of SnO2, greater than or equal to 0 wt% and less than or equal to 2.0 wt% of SnO2, greater than or equal to 0 wt% and less than or equal to 1.5 wt% of SnO2, greater than or equal to 0 wt% and less than or equal to 1.0 wt% of SnO2, greater than or equal to 0 wt% and less than or equal to 0.5 wt% of SnO2, greater than 0.01 wt% to less than or equal to 3 wt% of SnO2, greater than 0.01 wt% and less than or equal to 2.5 wt% of SnO2, greater than 0.01 wt% and less than or equal to 2.0 wt% of SnO2, greater than 0.01 wt% and less than or equal to 1.5 wt% of SnO2, greater than 0.01 wt% and less than or equal to 1.0 wt% of SnO2, or even greater than 0.01 wt% and less than or equal to 0.5 wt% of SnO2. In the embodiments, the glass or glass-ceramic does not contain chemical clarifying agents.
[0168] In some embodiments, the glass or glass-ceramic may be substantially free of Sb₂O₃, As₂O₃, or combinations thereof. For example, the glass or glass-ceramic may contain 0.05% by weight or less of Sb₂O₃ or As₂O₃, or combinations thereof; the glass or glass-ceramic may contain 0% by weight of Sb₂O₃ or As₂O₃, or combinations thereof; or the glass or glass-ceramic may, for example, be free of any intentionally added Sb₂O₃, As₂O₃, or combinations thereof.
[0169] In the embodiments, glass having the composition described herein can first be formed by mixing batches of constituent component sources (i.e., SiO2 source, Li2O source, etc.), heating the batches to form molten glass, and subsequently shaping or molding the molten glass into a glass article using conventional forming processes (e.g., slot drawing, float glass, rolling, melt forming, etc.). At this point, the glass or glass article may be referred to as "glass," meaning glass or glass article that has not yet undergone the heat treatment (e.g., ceramization) required to transform glass into glass ceramics to form glass ceramic articles.
[0170] A method for manufacturing glass-ceramics according to embodiments described herein includes heat-treating a glass at two preselected temperatures for one or more preselected times to induce glass homogenization and crystallization (i.e., nucleation and growth) of one or more crystalline phases (e.g., having one or more compositions, amounts, morphologies, sizes, or size distributions). Nucleation produces a nucleated glass having one or more crystalline phases, while growth produces a final glass-ceramic having one or more crystalline phases (also referred to as the final crystalline phase). These two temperatures may be referred to as the nucleation temperature and the growth temperature, respectively.
[0171] Now for reference Figure 1 An embodiment of a method 1000 for manufacturing glass-ceramics will be generally described below. First, in step 1001, glass is heated in an oven to a nucleation temperature greater than or equal to 450°C and less than or equal to 650°C. It should be understood that the nucleation temperature corresponds to the oven temperature at which the glass is heated, and that the glass temperature can be within + / - 5°C of the nucleation temperature when the oven temperature is at the nucleation temperature. In step 1002, the glass is held in an oven at a temperature range greater than or equal to the nucleation temperature and less than or equal to 650°C for a first duration to form a nucleated glass. In step 1003, the nucleated glass is heated to a growth temperature greater than or equal to 650°C and less than or equal to 800°C. In step 1004, the nucleated glass is held at a temperature range greater than or equal to the growth temperature and less than or equal to 800°C for a second duration to form a glass-ceramic having a final crystalline phase. In an embodiment, in step 1005, the glass-ceramic may be exposed to an ion exchange medium comprising molten potassium salt, molten sodium salt, or a combination thereof, with or without LiNO3 added to the ion exchange bath, to form a reinforced glass-ceramic. Each of these steps will be described in more detail below.
[0172] In an embodiment, the nucleation stage occurs when the glass is held at a predetermined nucleation temperature for a predetermined duration (i.e., nucleation time). In an embodiment, the nucleation temperatures are greater than or equal to 450°C and less than or equal to 650°C, greater than or equal to 460°C and less than or equal to 650°C, greater than or equal to 470°C and less than or equal to 650°C, greater than or equal to 480°C and less than or equal to 650°C, greater than or equal to 490°C and less than or equal to 650°C, greater than or equal to 500°C and less than or equal to 650°C, greater than or equal to 510°C and less than or equal to 650°C, greater than or equal to 520°C and less than or equal to 650°C, greater than or equal to 530°C and less than or equal to 650°C, greater than or equal to 540°C and less than or equal to 650°C, greater than or equal to 550°C and less than or equal to 650°C, and greater than or equal to 560°C. 0℃ and less than or equal to 650℃, greater than or equal to 570℃ and less than or equal to 650℃, greater than or equal to 580℃ and less than or equal to 650℃, greater than or equal to 590℃ and less than or equal to 650℃, greater than or equal to 600℃ and less than or equal to 650℃, greater than or equal to 610℃ and less than or equal to 650℃, greater than or equal to 620℃ and less than or equal to 650℃, greater than or equal to 630℃ and less than or equal to 650℃, greater than or equal to 640℃ and less than or equal to 650℃, greater than or equal to 450℃ and less than or equal to 640℃, greater than or equal to 460℃ and less than or equal to 640℃, greater than or equal to 470℃ and less than or equal to 640℃, greater than or equal to 480℃ and less than or equal to 640℃, greater than or equal to 490℃ and less than or equal to 640℃, greater than or equal to 500℃ and less than or equal to 640℃, greater than or equal to 510℃ and less than or equal to 640℃, greater than or equal to 520℃ and less than or equal to 640℃, greater than or equal to 530℃ and less than or equal to 640℃, greater than or equal to 540℃ and less than or equal to 640℃, greater than or equal to 550℃ and less than or equal to 640℃, greater than or equal to 560℃ and less than or equal to 640℃, greater than or equal to 570℃ and less than or equal to 640℃, greater than or equal to 580℃ and less than or equal to 640℃, greater than or equal to 590℃ and less than or equal to 640℃, greater than The following temperatures are considered acceptable: 600℃ and less than or equal to 640℃; 610℃ and less than or equal to 640℃; 620℃ and less than or equal to 640℃; 630℃ and less than or equal to 640℃; 450℃ and less than or equal to 630℃; 460℃ and less than or equal to 630℃; 470℃ and less than or equal to 630℃; 480℃ and less than or equal to 630℃; 490℃ and less than or equal to 630℃; 500℃ and less than or equal to 630℃; 510℃ and less than or equal to 630℃; 520℃ and less than or equal to 630℃.530℃ or higher and 630℃ or lower; 540℃ or higher and 630℃ or lower; 550℃ or higher and 630℃ or lower; 560℃ or higher and 630℃ or lower; 570℃ or higher and 630℃ or lower; 580℃ or higher and 630℃ or lower; 590℃ or higher and 630℃ or lower; 600℃ or higher and 630℃ or lower; 610℃ or higher and 630℃ or lower; 620℃ or higher and 630℃ or lower; 450℃ or higher and 620℃ or higher; 460℃ or higher and 620℃ or higher; 470℃ or higher and 630℃ or lower. ≤620℃, ≥480℃ and ≤620℃, ≥490℃ and ≤620℃, ≥500℃ and ≤620℃, ≥510℃ and ≤620℃, ≥520℃ and ≤620℃, ≥530℃ and ≤620℃, ≥540℃ and ≤620℃, ≥550℃ and ≤620℃, ≥560℃ and ≤620℃, ≥570℃ and ≤620℃, ≥580℃ and ≤620℃, ≥590℃ and ≤620℃ ≥600℃ and ≤620℃, ≥610℃ and ≤620℃, ≥450℃ and ≤610℃, ≥460℃ and ≤610℃, ≥470℃ and ≤610℃, ≥480℃ and ≤610℃, ≥490℃ and ≤610℃, ≥500℃ and ≤610℃, ≥510℃ and ≤610℃, ≥520℃ and ≤610℃, ≥530℃ and ≤610℃, ≥540℃ and ≤610℃, ≥550℃ and ≤610℃, ≥560℃ and ≤610℃, ≥570℃ and ≤610℃, ≥580℃ and ≤610℃, ≥590℃ and ≤610℃, ≥600℃ and ≤610℃, ≥450℃ and ≤600℃, ≥460℃ and ≤600℃, ≥470℃ and ≤600℃, ≥480℃ and ≤600℃, ≥490℃ and ≤600℃, ≥500℃ and ≤600℃, ≥510℃ and ≤600℃≥520℃ and ≤600℃, ≥530℃ and ≤600℃, ≥540℃ and ≤600℃, ≥550℃ and ≤600℃, ≥560℃ and ≤600℃, ≥570℃ and ≤600℃, ≥580℃ and ≤600℃, ≥590℃ and ≤600℃, ≥450℃ and ≤590℃, ≥460℃ and ≤590℃, ≥470℃ and ≤590℃, ≥480℃ and ≤590℃, ≥490℃ and 590℃ or less, 500℃ or greater and 590℃ or less, 510℃ or greater and 590℃ or less, 520℃ or greater and 590℃ or less, 530℃ or greater and 590℃ or less, 540℃ or greater and 590℃ or less, 550℃ or greater and 590℃ or less, 560℃ or greater and 590℃ or less, 570℃ or greater and 590℃ or less, 580℃ or greater and 590℃ or less, 450℃ or greater and 580℃ or less, 460℃ or greater and 580℃ or greater, 470℃ or greater and 580℃ or less. 480℃ or higher and 580℃ or lower; 490℃ or higher and 580℃ or lower; 500℃ or higher and 580℃ or lower; 510℃ or higher and 580℃ or lower; 520℃ or higher and 580℃ or lower; 530℃ or higher and 580℃ or lower; 540℃ or higher and 580℃ or lower; 550℃ or higher and 580℃ or lower; 560℃ or higher and 580℃ or lower; 570℃ or higher and 580℃ or lower; 450℃ or higher and 570℃ or higher; 460℃ or higher and 570℃ or lower; 470℃ or higher and... 570℃ or less, 480℃ or more and 570℃ or less, 490℃ or more and 570℃ or less, 500℃ or more and 570℃ or less, 510℃ or more and 570℃ or less, 520℃ or more and 570℃ or less, 530℃ or more and 570℃ or less, 540℃ or more and 570℃ or less, 550℃ or more and 570℃ or less, 560℃ or more and 570℃ or less, 450℃ or more and 560℃ or more, 460℃ or more and 560℃ or more, 470℃ or more and 560℃ or less.The temperatures are greater than or equal to 480℃ and less than or equal to 560℃, greater than or equal to 490℃ and less than or equal to 560℃, greater than or equal to 500℃ and less than or equal to 560℃, greater than or equal to 510℃ and less than or equal to 560℃, greater than or equal to 520℃ and less than or equal to 560℃, greater than or equal to 530℃ and less than or equal to 560℃, greater than or equal to 540℃ and less than or equal to 560℃, or greater than or equal to 550℃ and less than or equal to 560℃. It should be understood that the above ranges include all sub-ranges within the explicitly disclosed range.
[0173] In the embodiments, the duration for which the glass is held at the nucleation temperature is greater than or equal to 1 minute and less than or equal to 720 minutes, greater than or equal to 30 minutes and less than or equal to 720 minutes, greater than or equal to 60 minutes and less than or equal to 720 minutes, greater than or equal to 90 minutes and less than or equal to 720 minutes, greater than or equal to 120 minutes and less than or equal to 720 minutes, greater than or equal to 150 minutes and less than or equal to 720 minutes, greater than or equal to 180 minutes and less than or equal to 720 minutes, greater than or equal to 210 minutes and less than or equal to 720 minutes, greater than or equal to 240 minutes and less than or equal to 720 minutes, greater than or equal to 270 minutes and less than or equal to 720 minutes, greater than or equal to 300 minutes and less than or equal to 720 minutes, greater than or equal to 330 minutes and less than or equal to 720 minutes. The timeframes are as follows: 720 minutes, 360 minutes or more but less than or equal to 720 minutes, 390 minutes or more but less than or equal to 720 minutes, 420 minutes or more but less than or equal to 720 minutes, 450 minutes or more but less than or equal to 720 minutes, 480 minutes or more but less than or equal to 720 minutes, 510 minutes or more but less than or equal to 720 minutes, 540 minutes or more but less than or equal to 720 minutes, 570 minutes or more but less than or equal to 720 minutes, 600 minutes or more but less than or equal to 720 minutes, 630 minutes or more but less than or equal to 720 minutes, 660 minutes or more but less than or equal to 720 minutes, or even 690 minutes or more but less than or equal to 720 minutes. In the embodiments, the duration for which the glass is held at the nucleation temperature is greater than or equal to 1 minute and less than or equal to 360 minutes, greater than or equal to 30 minutes and less than or equal to 360 minutes, greater than or equal to 60 minutes and less than or equal to 360 minutes, greater than or equal to 90 minutes and less than or equal to 360 minutes, greater than or equal to 120 minutes and less than or equal to 360 minutes, greater than or equal to 150 minutes and less than or equal to 360 minutes, greater than or equal to 180 minutes and less than or equal to 360 minutes, greater than or equal to 210 minutes and less than or equal to 360 minutes, greater than or equal to 240 minutes and less than or equal to 360 minutes, greater than or equal to 270 minutes and less than or equal to 360 minutes. Less than or equal to 360 minutes, greater than or equal to 300 minutes and less than or equal to 360 minutes, greater than or equal to 330 minutes and less than or equal to 360 minutes, greater than or equal to 1 minute and less than or equal to 330 minutes, greater than or equal to 30 minutes and less than or equal to 330 minutes, greater than or equal to 60 minutes and less than or equal to 330 minutes, greater than or equal to 90 minutes and less than or equal to 330 minutes, greater than or equal to 120 minutes and less than or equal to 330 minutes, greater than or equal to 150 minutes and less than or equal to 330 minutes, greater than or equal to 180 minutes and less than or equal to 330 minutes, greater than or equal to 210 minutes and less than or equal to 330 minutes,240 minutes or more and 330 minutes or less; 270 minutes or more and 330 minutes or less; 300 minutes or more and 330 minutes or less; 1 minute or more and 300 minutes or less; 30 minutes or more and 300 minutes or less; 60 minutes or more and 300 minutes or less; 90 minutes or more and 300 minutes or less; 120 minutes or more and 300 minutes or less; 150 minutes or more and 300 minutes or less; 180 minutes or more and 300 minutes or less; 210 minutes or more and 300 minutes or less; 240 minutes or more... 300 minutes or less, 270 minutes or more or less, 1 minute or more or less, 30 minutes or more or less, 60 minutes or more or less, 90 minutes or more or less, 120 minutes or more or less, 150 minutes or more or less, 180 minutes or more or less, 210 minutes or more or less, 240 minutes or more or less, 1 minute or more or less, 240 minutes or more, 1 minute or more or less than 240 minutes. minutes, greater than or equal to 30 minutes and less than or equal to 240 minutes, greater than or equal to 60 minutes and less than or equal to 240 minutes, greater than or equal to 90 minutes and less than or equal to 240 minutes, greater than or equal to 120 minutes and less than or equal to 240 minutes, greater than or equal to 150 minutes and less than or equal to 240 minutes, greater than or equal to 180 minutes and less than or equal to 240 minutes, greater than or equal to 210 minutes and less than or equal to 240 minutes, greater than or equal to 1 minute and less than or equal to 210 minutes, greater than or equal to 30 minutes and less than or equal to 210 minutes, greater than or equal to 60 minutes and less than or equal to 210 minutes, greater than or equal to 90 minutes and less than or equal to 210 minutes, greater than or equal to 120 minutes Clocks up to 210 minutes or less, 150 minutes or more to 210 minutes or less, 180 minutes or more to 210 minutes or less, 1 minute or more to 180 minutes or less, 30 minutes or more to 180 minutes or less, 60 minutes or more to 180 minutes or less, 90 minutes or more to 180 minutes or less, 120 minutes or more to 180 minutes or less, 150 minutes or more to 180 minutes or less, 1 minute or more to 150 minutes or less, 30 minutes or more to 150 minutes or less, 60 minutes or more to 150 minutes or less.The timeframes are: greater than or equal to 90 minutes and less than or equal to 150 minutes; greater than or equal to 120 minutes and less than or equal to 150 minutes; greater than or equal to 1 minute and less than or equal to 120 minutes; greater than or equal to 30 minutes and less than or equal to 120 minutes; greater than or equal to 60 minutes and less than or equal to 120 minutes; greater than or equal to 90 minutes and less than or equal to 1 minute; greater than or equal to 30 minutes and less than or equal to 90 minutes; greater than or equal to 60 minutes and less than or equal to 90 minutes; greater than or equal to 1 minute and less than or equal to 60 minutes; greater than or equal to 30 minutes and less than or equal to 60 minutes; or greater than or equal to 1 minute and less than or equal to 30 minutes. It should be understood that the above ranges include all sub-ranges within the explicitly disclosed range. After the nucleation stage, the glass is referred to as nucleated glass.
[0174] A growth phase occurs when the nucleating glass is maintained at a predetermined growth temperature for a predetermined duration (i.e., the growth time). In embodiments, the growth temperature is greater than the nucleation temperature. In embodiments, the growth temperatures are greater than or equal to 650°C and less than or equal to 800°C, greater than or equal to 660°C and less than or equal to 800°C, greater than or equal to 670°C and less than or equal to 800°C, greater than or equal to 680°C and less than or equal to 800°C, greater than or equal to 690°C and less than or equal to 800°C, greater than or equal to 700°C and less than or equal to 800°C, greater than or equal to 710°C and less than or equal to 800°C, greater than or equal to 720°C and less than or equal to 800°C, greater than or equal to 730°C and less than or equal to 800°C, greater than or equal to 740°C and less than or equal to 800°C, greater than or equal to 750°C and less than or equal to 800°C, greater than... The following temperatures are considered high: 760℃ and less than or equal to 800℃; 770℃ and less than or equal to 800℃; 780℃ and less than or equal to 800℃; 790℃ and less than or equal to 800℃; 650℃ and less than or equal to 790℃; 660℃ and less than or equal to 790℃; 670℃ and less than or equal to 790℃; 680℃ and less than or equal to 790℃; 690℃ and less than or equal to 790℃; 700℃ and less than or equal to 790℃; 710℃ and less than or equal to 790℃; 720℃ and less than or equal to... 790℃, greater than or equal to 730℃ and less than or equal to 790℃, greater than or equal to 740℃ and less than or equal to 790℃, greater than or equal to 750℃ and less than or equal to 790℃, greater than or equal to 760℃ and less than or equal to 790℃, greater than or equal to 770℃ and less than or equal to 790℃, greater than or equal to 780℃ and less than or equal to 790℃, greater than or equal to 650℃ and less than or equal to 780℃, greater than or equal to 660℃ and less than or equal to 780℃, greater than or equal to 670℃ and less than or equal to 780℃, greater than or equal to 680℃ and less than or equal to 780℃, greater than or equal to 7 ... 0℃ and less than or equal to 780℃, greater than or equal to 710℃ and less than or equal to 780℃, greater than or equal to 720℃ and less than or equal to 780℃, greater than or equal to 730℃ and less than or equal to 780℃, greater than or equal to 740℃ and less than or equal to 780℃, greater than or equal to 750℃ and less than or equal to 780℃, greater than or equal to 760℃ and less than or equal to 780℃, greater than or equal to 770℃ and less than or equal to 780℃, greater than or equal to 650℃ and less than or equal to 770℃, greater than or equal to 660℃ and less than or equal to 770℃, greater than or equal to 670℃ and less than or equal to 770℃, greater than or equal to 680℃ and less than or equal to 770℃≥690℃ and ≤770℃, ≥700℃ and ≤770℃, ≥710℃ and ≤770℃, ≥720℃ and ≤770℃, ≥730℃ and ≤770℃, ≥740℃ and ≤770℃, ≥750℃ and ≤770℃, ≥760℃ and ≤770℃, ≥650℃ and ≤760℃, ≥660℃ and ≤760℃, ≥670℃ and ≤760℃, ≥680℃ and ≤760℃, ≥690℃ and ≤770℃ Less than or equal to 760℃, greater than or equal to 700℃ and less than or equal to 760℃, greater than or equal to 710℃ and less than or equal to 760℃, greater than or equal to 720℃ and less than or equal to 760℃, greater than or equal to 730℃ and less than or equal to 760℃, greater than or equal to 740℃ and less than or equal to 760℃, greater than or equal to 750℃ and less than or equal to 760℃, greater than or equal to 650℃ and less than or equal to 750℃, greater than or equal to 660℃ and less than or equal to 750℃, greater than or equal to 670℃ and less than or equal to 750℃, greater than or equal to 680℃ and less than or equal to 750℃, greater than or equal to 690℃ and less than or equal to 750℃, greater than or equal to 700℃ and less than or equal to 750℃, ≥710℃ and ≤750℃, ≥720℃ and ≤750℃, ≥730℃ and ≤750℃, ≥740℃ and ≤750℃, ≥650℃ and ≤740℃, ≥660℃ and ≤740℃, ≥670℃ and ≤740℃, ≥680℃ and ≤740℃, ≥690℃ and ≤740℃, ≥700℃ and ≤740℃, ≥710℃ and ≤740℃, ≥720℃ and ≤740℃, ≥730℃ and ≤750℃ 740℃ or less, 650℃ or more and 730℃ or less, 660℃ or more and 730℃ or less, 670℃ or more and 730℃ or less, 680℃ or more and 730℃ or less, 690℃ or more and 730℃ or less, 700℃ or more and 730℃ or less, 710℃ or more and 730℃ or less, 720℃ or more and 730℃ or less, 650℃ or more and 720℃ or less, 660℃ or more and 720℃ or more, 670℃ or more and 720℃ or more, 680℃ or more and 720℃ or less.690℃ or higher and 720℃ or lower; 700℃ or higher and 720℃ or lower; 710℃ or higher and 720℃ or lower; 650℃ or higher and 710℃ or lower; 660℃ or higher and 710℃ or lower; 670℃ or higher and 710℃ or lower; 680℃ or higher and 710℃ or lower; 690℃ or higher and 710℃ or lower; 700℃ or higher and 710℃ or lower The temperatures are defined as follows: greater than or equal to 650℃ and less than or equal to 700℃; greater than or equal to 660℃ and less than or equal to 700℃; greater than or equal to 670℃ and less than or equal to 700℃; greater than or equal to 690℃ and less than or equal to 700℃; greater than or equal to 650℃ and less than or equal to 690℃; greater than or equal to 660℃ and less than or equal to 690℃; greater than or equal to 670℃ and less than or equal to 690℃; or greater than or equal to 680℃ and less than or equal to 690℃. It should be understood that the above ranges include all sub-ranges within the explicitly disclosed range.
[0175] In the embodiments, the nucleating glass is held at the growth temperature for a duration of ≥1 minute to ≤240 minutes, ≥30 minutes to ≤240 minutes, ≥60 minutes to ≤240 minutes, ≥90 minutes to ≤240 minutes, ≥120 minutes to ≤240 minutes, ≥150 minutes to ≤240 minutes, ≥180 minutes to ≤240 minutes, or ≥210 minutes to ≤240 minutes. 1 minute or more to 210 minutes or less; 30 minutes or more to 210 minutes or less; 60 minutes or more to 210 minutes or less; 90 minutes or more to 210 minutes or less; 120 minutes or more to 210 minutes or less; 150 minutes or more to 210 minutes or less; 180 minutes or more to 210 minutes or less; 1 minute or more to 180 minutes or less; 30 minutes or more to 180 minutes or less; 1 minute or more to 21 ... 60 minutes to less than or equal to 180 minutes, 90 minutes to less than or equal to 180 minutes, 120 minutes to less than or equal to 180 minutes, 150 minutes to less than or equal to 180 minutes, 1 minute to less than or equal to 150 minutes, 30 minutes to less than or equal to 150 minutes, 60 minutes to less than or equal to 150 minutes, 90 minutes to less than or equal to 150 minutes, 120 minutes to less than or equal to 150 minutes, 1 minute to less than or equal to 1 The timeframes are defined as follows: minutes to less than or equal to 120 minutes, greater than or equal to 30 minutes to less than or equal to 120 minutes, greater than or equal to 60 minutes to less than or equal to 120 minutes, greater than or equal to 90 minutes to less than or equal to 1 minute, greater than or equal to 30 minutes to less than or equal to 90 minutes, greater than or equal to 60 minutes to less than or equal to 90 minutes, greater than or equal to 1 minute to less than or equal to 60 minutes, greater than or equal to 30 minutes to less than or equal to 60 minutes, or greater than or equal to 1 minute to less than or equal to 30 minutes. It should be understood that the above ranges include all sub-ranges within the explicitly disclosed range. The growth stage transforms the nucleating glass into a glass-ceramic material (i.e., glass-ceramic or glass-ceramic articles).
[0176] Holding the glass disclosed and described herein at the nucleation and growth temperatures for the duration disclosed and described herein will form a glass-ceramic having a phase combination comprising a residual amorphous glass phase and a lithium disilicate (Li₂Si₂O₅) crystalline phase. Optionally, the glass-ceramic may also comprise a lithium metasilicate (Li₂SiO₃) crystalline phase and / or a lithium phosphate (Li₃PO₄) crystalline phase. As noted herein, this phase combination provides a glass-ceramic with low haze (high transparency) and improved mechanical properties.
[0177] It is believed that the nucleation and growth temperatures and durations disclosed and described herein are primarily heat treatments for producing the desired phase combination in glass-ceramics. Additional heat treatments may be included before, between, and after the nucleation stage, without causing significant deviations in the phase combination of the glass-ceramic material. These additional heat treatments include isothermal holding, heating with specific heating schemes comprising many different heating rates, and combinations thereof.
[0178] Therefore, in embodiments, one of several additional temperature holdings may exist between the nucleation temperature and the growth temperature. In embodiments, after maintaining the glass at the nucleation temperature, the article may be heated to one or more intermediate temperatures (wherein the intermediate temperature is within the range between the nucleation temperature and the growth temperature) and held at the one or more intermediate temperatures for a predetermined time (e.g., from 1 minute to 360 minutes and all ranges and subranges therebetween), and then heated to the growth temperature.
[0179] In some embodiments, the nucleation stage comprises isothermal holding at a single nucleation temperature for a period of time. However, in other embodiments, the nucleation stage comprises heating the glass at one or more heating rates to the nucleation temperature range described herein (i.e., greater than or equal to 550°C to less than or equal to 650°C). Similarly, in some embodiments, the growth stage comprises isothermal holding at a single growth temperature for a period of time. However, in other embodiments, the growth stage comprises heating or cooling the nucleated glass at one or more heating rates within the growth temperature range described herein (i.e., greater than or equal to 680°C to less than or equal to 800°C).
[0180] According to embodiments, the heating rates used for heating from room temperature to the nucleation temperature during the nucleation stage, between the nucleation stage and the growth stage, during the growth stage, and after the growth stage are greater than or equal to 0.1°C / min and less than or equal to 50°C / min, greater than or equal to 5°C / min and less than or equal to 50°C / min, greater than or equal to 10°C / min and less than or equal to 50°C / min, greater than or equal to 15°C / min and less than or equal to 50°C / min, greater than or equal to 20°C / min and less than or equal to 50°C / min, greater than or equal to 25°C / min and less than or equal to 50°C / min, and greater than or equal to 30°C / min and less than or equal to 50°C / min. n, greater than or equal to 35℃ / min and less than or equal to 50℃ / min, greater than or equal to 40℃ / min and less than or equal to 50℃ / min, greater than or equal to 45℃ / min and less than or equal to 50℃ / min, greater than or equal to 0.1℃ / min and less than or equal to 45℃ / min, greater than or equal to 5℃ / min and less than or equal to 45℃ / min, greater than or equal to 10℃ / min and less than or equal to 45℃ / min, greater than or equal to 15℃ / min and less than or equal to 45℃ / min, greater than or equal to 20℃ / min and less than or equal to 45℃ / min, greater than or equal to 25℃ / min and less than or equal to 45℃ / min, large =At or equal to 30℃ / min and less than or equal to 45℃ / min, greater than or equal to 35℃ / min and less than or equal to 45℃ / min, greater than or equal to 40℃ / min and less than or equal to 45℃ / min, greater than or equal to 0.1℃ / min and less than or equal to 40℃ / min, greater than or equal to 5℃ / min and less than or equal to 40℃ / min, greater than or equal to 10℃ / min and less than or equal to 40℃ / min, greater than or equal to 15℃ / min and less than or equal to 40℃ / min, greater than or equal to 20℃ / min and less than or equal to 40℃ / min, greater than or equal to 25℃ / min and less than or equal to 40℃ / min, greater than or equal to At 30℃ / min and less than or equal to 40℃ / min, greater than or equal to 35℃ / min and less than or equal to 40℃ / min, greater than or equal to 0.1℃ / min and less than or equal to 35℃ / min, greater than or equal to 5℃ / min and less than or equal to 35℃ / min, greater than or equal to 10℃ / min and less than or equal to 35℃ / min, greater than or equal to 15℃ / min and less than or equal to 35℃ / min, greater than or equal to 20℃ / min and less than or equal to 35℃ / min, greater than or equal to 25℃ / min and less than or equal to 35℃ / min, greater than or equal to 30℃ / min and less than or equal to 35℃ / min, greater than or equal to 0.1℃ / min and less than or equal to 30℃ / min, greater than or equal to 5℃ / min and less than or equal to 30℃ / min, greater than or equal to 10℃ / min and less than or equal to 30℃ / min, greater than or equal to 15℃ / min and less than or equal to 30℃ / min, greater than or equal to 20℃ / min and less than or equal to 30℃ / min, greater than or equal to 25℃ / min and less than or equal to 30℃ / min, greater than or equal to 0.1℃ / min and less than or equal to 25℃ / min, greater than or equal to 5℃ / min and less than or equal to 25℃ / min, greater than or equal to 10℃ / min and less than or equal to 25℃ / min, greater than or equal to 15℃ / min and less than or equal to 25℃ / min, greater than or equal to 20℃ / min and less than or equal to 30℃ / min. The heating rates are 25°C / min, greater than or equal to 0.1°C / min and less than or equal to 20°C / min, greater than or equal to 5°C / min and less than or equal to 20°C / min, greater than or equal to 10°C / min and less than or equal to 20°C / min, greater than or equal to 15°C / min and less than or equal to 20°C / min, greater than or equal to 0.1°C / min and less than or equal to 15°C / min, greater than or equal to 5°C / min and less than or equal to 15°C / min, greater than or equal to 10°C / min and less than or equal to 15°C / min, greater than or equal to 0.1°C / min and less than or equal to 10°C / min, greater than or equal to 5°C / min and less than or equal to 10°C / min, or greater than or equal to 0.1°C / min and less than or equal to 5°C / min. It should be understood that the above ranges include all sub-ranges within the explicitly disclosed range. Such heating rates enable adequate nucleation and crystal growth without damaging the glass-ceramic product. If heating proceeds too rapidly, the material may be damaged. However, if heating proceeds too slowly, proper nucleation and growth may not occur.
[0181] In one or more embodiments, the nucleating glass can be formed during the growth step. In one or more embodiments, the nucleating glass can be formed into a non-planar shape. In some embodiments, the nucleating glass can be formed into a planar shape. In some embodiments, forming can be performed within a mold or other structure that imparts the desired shape to the nucleating glass as it is subjected to the growth temperature.
[0182] In this embodiment, the glass-ceramic is cooled after being held at the growth temperature. In this embodiment, the glass-ceramic may be cooled to room temperature in a single stage at a constant cooling rate, in two stages at different cooling rates, or in three or more stages at different cooling rates. In this embodiment, the glass-ceramic is cooled from the growth temperature at a controlled rate to minimize the temperature gradient and residual stress on the article. Differences in temperature gradient and residual stress can cause the article to warp during cooling. Therefore, controlling the cooling to control the temperature gradient and residual stress also minimizes the warping of the glass-ceramic.
[0183] The phase combination of the glass-ceramics described in this paper (i.e., the Rietwald parameters of the crystalline phase and the residual amorphous glass phase, respectively) restricts the refractive index mismatch between the crystalline and residual amorphous glass phases, thereby reducing the light scattering and resulting haze of the glass-ceramics, while improving the transmittance of the glass-ceramics.
[0184] The average crystallite size in the crystalline phase is a factor that affects the transparency (i.e., transmittance) of glass ceramics. In the embodiments, the average crystallite size of the glass-ceramic is within the following ranges: greater than or equal to 5 nm to less than or equal to 150 nm, greater than or equal to 5 nm to less than or equal to 125 nm, greater than or equal to 5 nm to less than or equal to 100 nm, greater than or equal to 5 nm to less than or equal to 75 nm, greater than or equal to 5 nm to less than or equal to 50 nm, greater than or equal to 5 nm to less than or equal to 27 nm, greater than or equal to 5 nm to less than or equal to 26 nm, greater than or equal to 5 nm to less than or equal to 25 nm, greater than or equal to 5 nm to less than or equal to 22 nm, greater than or equal to 10 nm to less than or equal to 150 nm, greater than or equal to 10 nm to less than or equal to 125 nm, greater than or equal to 10 nm to less than or equal to 100 nm, greater than or equal to 10 nm to less than or equal to 75 nm, greater than or equal to 10 nm to less than or equal to 50 nm, greater than or equal to 10 nm to less than or equal to 25 nm, greater than or equal to 10 nm to less than or equal to 22 nm, greater than or equal to 12 nm. nm to less than or equal to 150 nm, greater than or equal to 12 nm to less than or equal to 125 nm, greater than or equal to 12 nm to less than or equal to 100 nm, greater than or equal to 12 nm to less than or equal to 75 nm, greater than or equal to 12 nm to less than or equal to 50 nm, greater than or equal to 12 nm to less than or equal to 27 nm, greater than or equal to 12 nm to less than or equal to 26 nm, greater than or equal to 12 nm to less than or equal to 25 nm, greater than or equal to 12 nm to less than or equal to 22 nm, greater than or equal to 13 nm to less than or equal to 150 nm, greater than or equal to 13 nm to less than or equal to 125 nm, greater than or equal to 13 nm to less than or equal to 100 nm, greater than or equal to 13 nm to less than or equal to 75 nm, greater than or equal to 13 nm to less than or equal to 50 nm, greater than or equal to 13 nm to less than or equal to 27 nm, greater than or equal to 13 nm to less than or equal to 26 nm, greater than or equal to 13 nm to less than or equal to 250 nm. nm, greater than or equal to 13 nm to less than or equal to 22 nm, greater than or equal to 15 nm to less than or equal to 150 nm, greater than or equal to 15 nm to less than or equal to 125 nm, greater than or equal to 15 nm to less than or equal to 125 nm, greater than or equal to 15 nm to less than or equal to 100 nm, greater than or equal to 15 nm to less than or equal to 75 nm, greater than or equal to 15 nm to less than or equal to 50 nm, greater than or equal to 15 nm to less than or equal to 27 nm, greater than or equal to 15 nm to less than or equal to 26 nm, greater than or equal to 15nm to less than or equal to 25 nm, greater than or equal to 16 nm to less than or equal to 150 nm, greater than or equal to 16 nm to less than or equal to 165 nm, greater than or equal to 16 nm to less than or equal to 100 nm, greater than or equal to 16 nm to less than or equal to 75 nm, greater than or equal to 16 nm to less than or equal to 50 nm, greater than or equal to 16 nm to less than or equal to 27 nm, greater than or equal to 16 nm to less than or equal to 26 nm, greater than or equal to 16 nm to less than or equal to 25 nm, greater than or equal to 16 nm to less than or equal to 22 nm, greater than or equal to 17 nm to less than or equal to 150 nm, greater than or equal to 17 nm to less than or equal to 175 nm, greater than or equal to 17 nm to less than or equal to 100 nm, greater than or equal to 17 nm to less than or equal to 75 nm, greater than or equal to 17 nm to less than or equal to 50 nm, greater than or equal to 17 nm to less than or equal to 27 nm, greater than or equal to 17 nm to less than or equal to 26 nm, greater than or equal to 17 nm to less than or equal to 25 nm, greater than or equal to 17 nm to less than or equal to 22 nm, greater than or equal to 18 nm to less than or equal to 150 nm, greater than or equal to 18 nm to less than or equal to 185 nm, greater than or equal to 18 nm to less than or equal to 100 nm, greater than or equal to 18 nm to less than or equal to 75 nm, greater than or equal to 18 nm to less than or equal to 50 nm, greater than or equal to 18 nm to less than or equal to 27 nm, greater than or equal to 18 nm to less than or equal to 26 nm, greater than or equal to 18 nm to less than or equal to 25 nm, greater than or equal to 18 nm to less than or equal to 22 nm, greater than or equal to 19 nm to less than or equal to 150 nm, greater than or equal to 19 nm to less than or equal to 195 nm, greater than or equal to 19 nm to less than or equal to 100 nm, greater than or equal to 19 nm to less than or equal to 75 nm, greater than or equal to 19 nm to less than or equal to 50 nm, greater than or equal to 19 nm to less than or equal to 27 nm, greater than or equal to 19 nm to less than or equal to 26 nm, greater than or equal to 19 nm to less than or equal to 25 nm, greater than or equal to 19 nm to less than or equal to 22 nm, greater than or equal to 20 nm to less than or equal to 150 nm, greater than or equal to 20 nm to less than or equal to 125 nm, greater than or equal to 20 nm to less than or equal to 125 nm, greater than or equal to 15 nm to less than or equal to 22 nm, greater than or equal to 20 nm to less than or equal to 100 nm, greater than or equal to 20 nm to less than or equal to 75 nm, greater than or equal to 20 nm to less than or equal to 50 nm, greater than or equal to 20 nm to less than or equal to 27 nmThe average crystallite size in glass-ceramics is determined by X-ray diffraction data. Specifically, X-ray diffraction was performed on powder samples of glass-ceramics, and X-ray diffraction patterns were obtained. The average size of the crystalline phases and crystallites present in the samples (i.e., crystallite size) was determined from the X-ray diffraction patterns using Bruker AXSTOPAS Ritwald refinement software.
[0185] In one embodiment, the glass-ceramic exhibits high transparency and low haze, making it suitable as a cover glass for electronic devices, such as mobile electronic devices. In another embodiment, the glass-ceramic is transparent because it exhibits a transmittance of 75% or greater, 76% or greater, 77% or greater, 78% or greater, 79% or greater, 80% or greater, 81% or greater, 82% or greater, 83% or greater, 84% or greater, 85% or greater, 86% or greater, 87% or greater, 88% or greater, 89% or greater, 90% or greater, 91% or greater, 92% or greater, 93% or greater, or 94% or greater for light with wavelengths greater than or equal to 400 nm to less than or equal to 1000 nm. In one or more embodiments, the thickness of the glass-ceramic exhibiting the aforementioned transmittance is 0.5 mm.
[0186] In other embodiments, the glass-ceramic may be translucent to light in the wavelength range of 400 nm to 750 nm. In embodiments, the translucent glass-ceramic may have a transmittance in the range of about 20% to less than 75% to light in the wavelength range of about 400 nm to about 750 nm. In embodiments, the translucent glass-ceramic may have a transmittance in the range of about 20% to less than 75% to light in the wavelength range of about 400 nm to about 1000 nm. In one or more embodiments, the thickness of the glass-ceramic exhibiting the aforementioned transmittance is 0.5 mm. It should be understood that the above ranges include all sub-ranges within the explicitly disclosed range.
[0187] In the embodiments, the haze (%) of the glass-ceramic article is less than or equal to 1.0, 0.95, 0.90, 0.85, 0.80, 0.75, 0.70, 0.65, 0.60, 0.55, 0.50, 0.45, 0.40, 0.35, 0.30, 0.25, 0.20, 0.15, 0.14, 0.13, 0.12, 0.11, 0.10, 0.09, 0.08, 0.07, 0.06, or 0.05. In one or more embodiments, the thickness of the glass-ceramic article exhibiting the haze is less than or equal to 0.6 mm, for example, less than or equal to 0.5 mm, less than or equal to 0.4 mm, less than or equal to 0.3 mm, less than or equal to 0.2 mm, or even less than or equal to 0.1 mm. In one or more embodiments, the haze (%) of the glass-ceramic article is greater than or equal to 0 and less than or equal to 1.0, greater than or equal to 0 and less than or equal to 0.95, greater than or equal to 0 and less than or equal to 0.90, greater than or equal to 0 and less than or equal to 0.85, greater than or equal to 0 and less than or equal to 0.80, greater than or equal to 0 and less than or equal to 0.75, greater than or equal to 0 and less than or equal to 0.70, greater than or equal to 0 and less than or equal to 0.65, greater than or equal to 0 and less than or equal to 0.60, greater than or equal to 0 and less than or equal to 1. ...1.0, greater than or equal to 0 and less than or equal to 0.70, greater than or equal to 0 and less than or equal to 0.60, greater than or equal to 0 and less than or equal to 1.0, greater than or equal to 0 and less than or equal to 1.0, greater than or equal to 0 and less than or equal to 1.0, greater than or equal to 0 and less than or equal to 0.70, greater than or equal to 0 and =0.55, greater than or equal to 0 and less than or equal to 0.50, greater than or equal to 0 and less than or equal to 0.45, greater than or equal to 0 and less than or equal to 0.40, greater than or equal to 0 and less than or equal to 0.35, greater than or equal to 0 and less than or equal to 0.30, greater than or equal to 0 and less than or equal to 0.25, greater than or equal to 0 and less than or equal to 0.20, greater than or equal to 0 and less than or equal to 0.15, greater than or equal to 0 and less than or equal to 0.14, greater than or equal to 0 and less than or equal to 0.13, greater than or equal to 0 and less than or equal to 0.12, greater than or equal to 0 and less than or equal to 0.11, greater than or equal to 0 and less than or equal to 0.10, greater than or equal to 0 and less than or equal to 0.09, greater than or equal to 0 and less than or equal to 0.08, greater than or equal to 0 and less than or equal to 0.07, greater than or equal to 0 and less than or equal to 0.06, greater than or equal to 0 and less than or equal to 0.05, greater than or equal to 0.05 and less than or equal to 1.0, greater than or equal to 0.05 and less than or equal to 0.95, greater than or equal to 0.05 and less than or equal to 0.12, greater than or equal to 0 and less than or equal to 0.11, greater than or equal to 0 and less than or equal to 0.10, greater than or equal to 0 and less than or equal to 0.09, greater than or equal to 0 and less than or equal to 0.05, greater than or equal to 0 and less than or equal to 0.05, greater than or equal to 0.05 and less than or equal to 0.05, greater than or equal to 0.05, ... The values are: equal to 0.90, greater than or equal to 0.05 and less than or equal to 0.85, greater than or equal to 0.05 and less than or equal to 0.80, greater than or equal to 0.05 and less than or equal to 0.75, greater than or equal to 0.05 and less than or equal to 0.70, greater than or equal to 0.05 and less than or equal to 0.65, greater than or equal to 0.05 and less than or equal to 0.60, greater than or equal to 0.05 and less than or equal to 0.55, greater than or equal to 0.05 and less than or equal to 0.50, and greater than or equal to 0.05 and less than or equal to 0.45. Greater than or equal to 0.05 and less than or equal to 0.40; Greater than or equal to 0.05 and less than or equal to 0.35; Greater than or equal to 0.05 and less than or equal to 0.30; Greater than or equal to 0.05 and less than or equal to 0.25; Greater than or equal to 0.05 and less than or equal to 0.20; Greater than or equal to 0.05 and less than or equal to 0.15; Greater than or equal to 0.05 and less than or equal to 0.14; Greater than or equal to 0.05 and less than or equal to 0.13; Greater than or equal to 0.05 and less than or equal to 0.12; Greater than or equal to 0.05 and less than or equal to 0.11; Greater than or equal to 0.05 and less than or equal to 0.10; Greater than or equal to 0.05 and less than or equal to 0.09; Greater than or equal to 0. 0.05 and less than or equal to 0.08, greater than or equal to 0.05 and less than or equal to 0.07, greater than or equal to 0.07 and less than or equal to 1.0, greater than or equal to 0.07 and less than or equal to 0.95, greater than or equal to 0.07 and less than or equal to 0.90, greater than or equal to 0.07 and less than or equal to 0.85, greater than or equal to 0.07 and less than or equal to 0.80, greater than or equal to 0.07 and less than or equal to 0.75, greater than or equal to 0.07 and less than or equal to 0.70, greater than or equal to 0.07 and less than or equal to 0.65, greater than or equal to 0.07 and less than or equal to 0.60, greater than or equal to 0.07 and less than or equal to 0.55, greater than or equal to 0.07 and less than or equal to 0. 0.50, greater than or equal to 0.07 and less than or equal to 0.45, greater than or equal to 0.07 and less than or equal to 0.40, greater than or equal to 0.07 and less than or equal to 0.35, greater than or equal to 0.07 and less than or equal to 0.30, greater than or equal to 0.07 and less than or equal to 0.25, greater than or equal to 0.07 and less than or equal to 0.20, greater than or equal to 0.07 and less than or equal to 0.15, greater than or equal to 0.07 and less than or equal to 0.14, greater than or equal to 0.07 and less than or equal to 0.13, greater than or equal to 0.07 and less than or equal to 0.12, greater than or equal to 0.07 and less than or equal to 0.11, greater than or equal to 0.07 and less than or equal to 0.10, greater than or equal to 0.07 and less than or equal to 0.09, greater than or equal to 0.07 and less than or equal to 0.08, greater than or equal to 0.1 and less than or equal to 1.0, greater than or equal to 0.1 and less than or equal to 0.95, greater than or equal to 0.1 and less than or equal to 0.90, greater than or equal to 0.1 and less than or equal to 0.85, greater than or equal to 0.1 and less than or equal to 0.80, greater than or equal to 0.1 and less than or equal to 0.75, greater than or equal to 0.1 and less than or equal to 0.70, greater than or equal to 0.1 and less than or equal to 0.65, greater than or equal to 0.1 and less than or equal to 0.60, greater than or equal to 0.1 and less than or equal to 0.55, greater than or equal to 0.1 and less than or equal to 0.50, greater than or equal to 0.The thickness of the glass-ceramic article exhibiting the haze is less than or equal to 0.45, greater than or equal to 0.1 and less than or equal to 0.40, greater than or equal to 0.1 and less than or equal to 0.35, greater than or equal to 0.1 and less than or equal to 0.30, greater than or equal to 0.1 and less than or equal to 0.25, greater than or equal to 0.1 and less than or equal to 0.20, or even greater than or equal to 0.1 and less than or equal to 0.15. In one or more embodiments, the thickness of the glass-ceramic article exhibiting the haze is less than or equal to 0.6 mm, for example, less than or equal to 0.5 mm, less than or equal to 0.4 mm, less than or equal to 0.3 mm, less than or equal to 0.2 mm, or even less than or equal to 0.1 mm. It should be noted that when a glass-ceramic article has a certain haze value at a specified thickness, glass-ceramic articles with the same composition and the same phase combination will have at least the same or smaller haze value at a thickness less than the specified thickness. For example, a glass-ceramic article with a thickness of 0.5 mm will have the same or lower haze value as a glass-ceramic article formed from the same composition and containing the same phase combination but with a thickness of 0.6 mm. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0188] In embodiments, the haze of the glass-ceramic can be characterized based on the haze value (or haze) per millimeter (mm) of thickness of the glass-ceramic. In embodiments, the haze (%) per millimeter of thickness of the glass-ceramic can be greater than or equal to 0.04 / mm and less than or equal to 2.0 / mm, greater than or equal to 0.04 / mm and less than or equal to 1.8 / mm, greater than or equal to 0.04 / mm and less than or equal to 1.6 / mm, greater than or equal to 0.04 / mm and less than or equal to 1.4 / mm, greater than or equal to 0.04 / mm and less than or equal to 1.2 / mm, greater than or equal to 0.04 / mm and less than or equal to 1.0 / mm, greater than or equal to 0.04 / mm and less than or equal to 0.8 / mm, or even greater than or equal to 0.04 / mm and less than or equal to 0.6 / mm. In embodiments, the haze (%) per millimeter thickness of the glass-ceramic can be greater than or equal to 0.06 / mm and less than or equal to 0.4 / mm, greater than or equal to 0.06 / mm and less than or equal to 0.3 / mm, greater than or equal to 0.06 / mm and less than or equal to 0.2 / mm, or even greater than or equal to 0.06 / mm and less than or equal to 0.1 / mm. It should be understood that the above ranges include all sub-ranges within the explicitly disclosed range.
[0189] The fracture toughness of glass-ceramics typically increases with the amount of lithium disilicate crystalline phase in the glass-ceramic, as indicated by the Rietwald parameter. However, the optical properties of glass-ceramics (e.g., haze) may deteriorate with increasing crystallite size of the lithium disilicate crystalline phase. It has now been found that when the ratio of the Rietwald parameter of the lithium disilicate crystalline phase to the average crystallite size (in nm) of the lithium disilicate crystalline phase is greater than or equal to 2.75 wt% / nm, the glass-ceramic exhibits relatively high fracture toughness and relatively low haze, making it suitable for applications such as cover glass for handheld electronic devices. That is, when the ratio of the Rietwald parameter of the lithium disilicate crystalline phase to the crystallite size of the lithium disilicate crystalline phase is greater than or equal to 2.75 wt% / nm, the glass-ceramic exhibits a favorable combination of high fracture toughness and low haze. In the embodiments, the ratio of the Ritwald parameter of the lithium disilicate phase to the crystallite size of the lithium disilicate phase is greater than or equal to 2.75 wt% / nm, greater than or equal to 3.0 wt% / nm, greater than or equal to 3.25 wt% / nm, greater than or equal to 3.5 wt% / nm, greater than or equal to 3.75 wt% / nm, greater than or equal to 4.0 wt% / nm, greater than or equal to 4.25 wt% / nm, greater than or equal to 4.5 wt% / nm, greater than or equal to 4.75 wt% / nm, greater than or equal to 5.0 wt% / nm, greater than or equal to 5.25 wt% / nm, greater than or equal to 5.5 wt% / nm, or even greater than or equal to 5.75 wt% / nm. In the embodiments, the ratio of the Rietwald parameter of the lithium disilicate crystalline phase to the crystallite size of the lithium disilicate crystalline phase is greater than or equal to 2.75 wt% / nm and less than or equal to 6.0 wt% / nm, greater than or equal to 2.75 wt% / nm and less than or equal to 5.75 wt% / nm, greater than or equal to 2.75 wt% / nm and less than or equal to 5.5 wt% / nm, greater than or equal to 2.75 wt% / nm and less than or equal to 5.25 wt% / nm, greater than or equal to 2.75 wt% / nm and less than or equal to 5.0 wt% / nm, greater than or equal to 2.75 wt% / nm and less than or equal to 4.75 wt% / nm, greater than or equal to 2.75 wt% / nm and... Less than or equal to 4.5 wt% / nm, greater than or equal to 4.75 wt% / nm and less than or equal to 4.25 wt% / nm, greater than or equal to 2.75 wt% / nm and less than or equal to 4.0 wt% / nm, greater than or equal to 2.75 wt% / nm and less than or equal to 3.75 wt% / nm, greater than or equal to 2.75 wt% / nm and less than or equal to 3.5 wt% / nm, greater than or equal to 2.75 wt% / nm and less than or equal to 3.25 wt% / nm, greater than or equal to 2.75 wt% / nm and less than or equal to 3.0 wt% / nm, greater than or equal to 3.0 wt% / nm and less than or equal to 6.0 wt% / nm, greater than or equal to 3.0 wt% / nm and less than or equal to 5.75 wt% / nm, greater than or equal to 3.0 wt% / nm and less than or equal to 5.5 wt% / nm, greater than or equal to 3.0 wt% / nm and less than or equal to 5.25 wt% / nm, greater than or equal to 3.0 wt% / nm and less than or equal to 5.0 wt% / nm, greater than or equal to 3.0 wt% / nm and less than or equal to 4.75 wt% / nm, greater than or equal to 3.0 wt% / nm and less than or equal to 4.5 wt% / nm, greater than or equal to 4.75 wt% / nm and less than or equal to 4.25 wt% / nm, greater than or equal to 3.0 wt% / nm and less than or equal to 4.0 wt% / nm, greater than or equal to 3 0 wt% / nm and less than or equal to 3.75 wt% / nm, greater than or equal to 3.0 wt% / nm and less than or equal to 3.5 wt% / nm, greater than or equal to 3.0 wt% / nm and less than or equal to 3.25 wt% / nm, greater than or equal to 3.25 wt% / nm and less than or equal to 6.0 wt% / nm, greater than or equal to 3.25 wt% / nm and less than or equal to 5.75 wt% / nm, greater than or equal to 3.25 wt% / nm and less than or equal to 5.5 wt% / nm, greater than or equal to 3.25 wt% / nm and less than or equal to 5.25 wt% / nm, greater than or equal to 3.25 wt% / nm and less than or equal to 5.0 wt% / nm, large 3.25 wt% / nm and less than or equal to 4.75 wt% / nm, greater than or equal to 3.25 wt% / nm and less than or equal to 4.5 wt% / nm, greater than or equal to 4.75 wt% / nm and less than or equal to 4.25 wt% / nm, greater than or equal to 3.25 wt% / nm and less than or equal to 4.0 wt% / nm, greater than or equal to 3.25 wt% / nm and less than or equal to 3.75 wt% / nm, greater than or equal to 3.25 wt% / nm and less than or equal to 3.5 wt% / nm, greater than or equal to 3.5 wt% / nm and less than or equal to 6.0 wt% / nm, greater than or equal to 3.5 wt% / nm and less than or equal to 5.75 wt%. % / nm, greater than or equal to 3.5 wt% / nm and less than or equal to 5.5 wt% / nm, greater than or equal to 3.5 wt% / nm and less than or equal to 5.25 wt% / nm, greater than or equal to 3.5 wt% / nm and less than or equal to 5.0 wt% / nm, greater than or equal to 3.5 wt% / nm and less than or equal to 4.75 wt% / nm, greater than or equal to 3.5 wt% / nm and less than or equal to 4.5 wt% / nm, greater than or equal to 4.75 wt% / nm and less than or equal to 4.25 wt% / nm, greater than or equal to 3.5 wt% / nm and less than or equal to 4.0 wt% / nm, or even greater than or equal to 3.5 wt% / nm and less than or equal to 3.75 wt% / nm. It should be understood that the above range includes all sub-ranges within the explicitly disclosed range.
[0190] It has been established that in the glass-ceramics described in this paper, the haze of the glass-ceramics generally increases with increasing crystallite size. Increasing the crystallite size can also alter the reflectivity and transmittance characteristics of the glass-ceramics. For example, glass-ceramics with relatively large crystallite sizes may exhibit a larger proportion of blue light in reflected light and a larger proportion of yellow light in transmitted light. These variations in reflected and transmitted light can be quantified using the CIELAB color coordinates of the glass-ceramics.
[0191] In the embodiments, as measured under D65 illumination and a 10° standard viewing angle when the article thickness is 0.6 mm, the transmission color coordinates of the glass-ceramic described herein in the CIELAB color space are L. Greater than or equal to 96.5 and less than or equal to 97.5, a Greater than or equal to -0.25 and less than or equal to -0.15, and b Greater than or equal to -0.30 and less than or equal to -0.05.
[0192] In the embodiments, as measured under D65 illumination and a standard viewing angle of 10° (excluding the specular component (SCE)) when the article thickness is 0.6 mm, the reflectance color coordinates of the glass-ceramic described herein in the CIELAB color space are L. a is greater than or equal to 0.5 and less than or equal to 1.5. Greater than or equal to 0.35 and less than or equal to 0.75, and b Greater than or equal to -3.80 and less than or equal to -2.20.
[0193] In embodiments, glass-ceramics and glass-ceramic articles may be strengthened to create a compressive stress layer on one or more of their surfaces and a corresponding central tension in the thickness direction of the glass-ceramic article. Reference will now be made by way of example. Figure 2 It depicts an exemplary cross-sectional side view of a reinforced glass-ceramic article 100 having a first surface 102 separated by thickness (t) and an opposing second surface 104. In an embodiment, the reinforced glass-ceramic article 100 is ion-exchanged and has a compressive stress (CS) layer 106 (or a first region) extending from the first surface 102 to the depth of compression (DOC). In an embodiment, as... Figure 2 As shown, the glass-ceramic article 100 also has a compressive stress (CS) layer 108 extending from the second surface 104 to the compression depth DOC'. A central tensile region 110 with central tension (CT) is located between DOC and DOC'.
[0194] In embodiments, glass ceramics and glass ceramic articles can be chemically hardened (also known as chemical strengthening) using one or more ion exchange techniques. In these embodiments, ion exchange can be performed by subjecting one or more surfaces of such glass ceramics or glass ceramic articles to one or more ion exchange media (e.g., molten salt baths) having a specific composition and temperature for a specified period of time to impart a compressive stress layer to the one or more surfaces. In embodiments, the ion exchange medium is a molten salt bath containing ions (e.g., alkali metal ions) larger than those present in the glass ceramics or glass ceramic articles (e.g., alkali metal ions), wherein the larger ions from the molten bath exchange with smaller ions in the glass ceramic articles to impart compressive stress in the glass ceramics or glass ceramic articles, thereby increasing the strength of the glass ceramics or glass ceramic articles.
[0195] In this embodiment, a one-step ion exchange process may be used. In other embodiments, a multi-step ion exchange process (e.g., a two-step ion exchange process) may be used. In this embodiment, for both one-step and multi-step ion exchange processes, the ion exchange medium (e.g., a molten bath) may include potassium nitrate (KNO3) and sodium nitrate (NaNO3) as main components. In this embodiment, the ion exchange medium may also include lithium nitrate (LiNO3), sodium nitrite (NaNO2), and silicic acid.
[0196] In the embodiments, the ion exchange medium comprises greater than or equal to 2 wt% and less than or equal to 80 wt%, greater than or equal to 2 wt% and less than or equal to 70 wt% of KNO3, greater than or equal to 2 wt% and less than or equal to 60 wt% of KNO3, greater than or equal to 2 wt% and less than or equal to 50 wt% of KNO3, greater than or equal to 2 wt% and less than or equal to 40 wt% of KNO3, greater than or equal to 2 wt% and less than or equal to 30 wt% of KNO3, greater than or equal to 2 wt% and less than or equal to 20 wt% of KNO3, greater than or equal to 2 wt% and less than or equal to 10 wt% of KNO3, or greater than or equal to 2 wt% and less than or equal to 10 wt% of KNO3. In embodiments, the ion exchange medium comprises 10% by weight and less than or equal to 30% by weight of KNO3, 15% by weight and less than or equal to 30% by weight of KNO3, 20% by weight and less than or equal to 30% by weight of KNO3, 25% by weight and less than or equal to 30% by weight of KNO3, 10% by weight and less than or equal to 25% by weight of KNO3, 15% by weight and less than or equal to 25% by weight of KNO3, 20% by weight and less than or equal to 25% by weight of KNO3, 10% by weight and less than or equal to 20% by weight of KNO3, or 15% by weight and less than or equal to 20% by weight of KNO3. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0197] In the embodiments, the ion exchange medium further comprises greater than or equal to 20 wt% and less than or equal to 98 wt% of NaNO3, greater than or equal to 20 wt% and less than or equal to 90 wt% of NaNO3, greater than or equal to 20 wt% and less than or equal to 80 wt% of NaNO3, greater than or equal to 20 wt% and less than or equal to 70 wt% of NaNO3, greater than or equal to 20 wt% and less than or equal to 60 wt% of NaNO3, greater than or equal to 20 wt% and less than or equal to 50 wt% of NaNO3, greater than or equal to 20 wt% and less than or equal to 40 wt% of NaNO3, or greater than or equal to 20 wt% and less than or equal to 30 wt% of NaNO3. In embodiments, the ion exchange medium further comprises greater than or equal to 70 wt% and less than or equal to 90 wt% NaNO3, greater than or equal to 75 wt% and less than or equal to 90 wt% NaNO3, greater than or equal to 80 wt% and less than or equal to 90 wt% NaNO3, greater than or equal to 70 wt% and less than or equal to 85 wt% NaNO3, greater than or equal to 75 wt% and less than or equal to 85 wt% NaNO3, greater than or equal to 80 wt% and less than or equal to 80 wt% NaNO3, or greater than or equal to 75 wt% and less than or equal to 80 wt% NaNO3. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0198] In the embodiments, the ion exchange medium comprises 0.05 wt% and less than 0.5 wt% of LiNO3, 0.05 wt% and less than 0.45 wt% of LiNO3, 0.05 wt% and less than 0.4 wt% of LiNO3, 0.05 wt% and less than 0.35 wt% of LiNO3, 0.05 wt% and less than 0.3 wt% of LiNO3, 0.05 wt% and less than 0.25 wt% of LiNO3, or even 0.05 wt% and less than 0.2 wt% of LiNO3. In the embodiments, the ion exchange medium comprises ≥0.05 wt% and ≤0.15 wt% of LiNO3, ≥0.08 wt% and ≤0.15 wt% of LiNO3, ≥0.10 wt% and ≤0.15 wt% of LiNO3, ≥0.12 wt% and ≤0.15 wt% of LiNO3, and ≥0.05 wt% and ≤0.12 wt% of LiNO3. The range includes LiNO3 in amounts greater than or equal to 0.08 wt% and less than or equal to 0.12 wt%, greater than or equal to 0.10 wt% and less than or equal to 0.12 wt%, greater than or equal to 0.05 wt% and less than or equal to 0.10 wt%, greater than or equal to 0.08 wt% and less than or equal to 0.10 wt%, or greater than or equal to 0.05 wt% and less than or equal to 0.08 wt%. It should be understood that the above range includes all sub-ranges within the explicitly disclosed range.
[0199] In embodiments, the ion exchange medium may further comprise greater than or equal to 0.40 wt% and less than or equal to 0.60 wt% of silicic acid, greater than or equal to 0.45 wt% and less than or equal to 0.60 wt% of silicic acid, greater than or equal to 0.50 wt% and less than or equal to 0.60 wt% of silicic acid, greater than or equal to 0.55 wt% and less than or equal to 0.40 wt% and less than or equal to 0.55 wt% of silicic acid, greater than or equal to 0.50 wt% and less than or equal to 0.55 wt% of silicic acid, greater than or equal to 0.40 wt% and less than or equal to 0.50 wt% of silicic acid, greater than or equal to 0.45 wt% and less than or equal to 0.50 wt% of silicic acid, or greater than or equal to 0.40 wt% and less than or equal to 0.45 wt%. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0200] In the embodiments, the temperatures of the ion exchange media are greater than or equal to 430°C and less than or equal to 550°C, greater than or equal to 450°C and less than or equal to 550°C, greater than or equal to 475°C and less than or equal to 550°C, greater than or equal to 500°C and less than or equal to 550°C, greater than or equal to 525°C and less than or equal to 550°C, greater than or equal to 530°C and less than or equal to 550°C, greater than or equal to 430°C and less than or equal to 530°C, greater than or equal to 450°C and less than or equal to 530°C, greater than or equal to 475°C and less than or equal to 530°C, greater than or equal to 430°C and less than or equal to 530°C, greater than or equal to 475°C and less than or equal to 530°C, greater than or equal to 530°C, greater than or equal to 530°C, less ... The temperatures are equal to or less than or equal to 500℃ and 530℃, greater than or equal to 525℃ and 530℃, greater than or equal to 430℃ and 525℃, greater than or equal to 450℃ and 525℃, greater than or equal to 475℃ and 525℃, greater than or equal to 500℃ and 525℃, greater than or equal to 430℃ and 500℃, greater than or equal to 450℃ and 500℃, greater than or equal to 475℃ and 500℃, or greater than or equal to 450℃ and 475℃. It should be understood that the above ranges include all sub-ranges within the explicitly disclosed range.
[0201] According to the embodiments, the duration of contact between the glass ceramic or glass ceramic product and the ion exchange medium is greater than or equal to 1 hour and less than or equal to 16 hours, greater than or equal to 2 hours and less than or equal to 16 hours, greater than or equal to 4 hours and less than or equal to 16 hours, greater than or equal to 6 hours and less than or equal to 16 hours, greater than or equal to 8 hours and less than or equal to 16 hours, greater than or equal to 10 hours and less than or equal to 16 hours, greater than or equal to 12 hours and less than or equal to 16 hours, greater than or equal to 14 hours and less than or equal to 16 hours, greater than or equal to 1 hour and less than or equal to 14 hours, greater than or equal to 2 hours and less than or equal to 14 hours, greater than or equal to 4 hours and less than or equal to 14 hours, greater than or equal to 6 hours and less than or equal to 14 hours, greater than or equal to 8 hours and less than or equal to 14 hours, greater than or equal to 10 hours and less than or equal to 14 hours, greater than or equal to 12 hours and less than or equal to 14 hours, greater than or equal to 1 hour and less than or equal to 12 hours, greater than or equal to 2 hours and less than or equal to 12 hours. Hours, greater than or equal to 4 hours and less than or equal to 12 hours, greater than or equal to 6 hours and less than or equal to 12 hours, greater than or equal to 8 hours and less than or equal to 12 hours, greater than or equal to 10 hours and less than or equal to 12 hours, greater than or equal to 1 hour and less than or equal to 10 hours, greater than or equal to 2 hours and less than or equal to 10 hours, greater than or equal to 4 hours and less than or equal to 10 hours, greater than or equal to 6 hours and less than or equal to 10 hours, greater than or equal to 8 hours and less than or equal to 10 hours, greater than or equal to 1 hour and less than or equal to 8 hours, greater than or equal to 2 hours and less than or equal to 8 hours, greater than or equal to 4 hours and less than or equal to 8 hours, greater than or equal to 6 hours and less than or equal to 8 hours, greater than or equal to 1 hour and less than or equal to 6 hours, greater than or equal to 2 hours and less than or equal to 6 hours, greater than or equal to 4 hours and less than or equal to 6 hours, greater than or equal to 1 hour and less than or equal to 4 hours, greater than or equal to 2 hours and less than or equal to 4 hours, or greater than or equal to 1 hour and less than or equal to 2 hours. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0202] After the ion exchange process, it should be understood that the composition at the surface of the glass-ceramic may differ from that of the initially formed glass-ceramic (i.e., the glass-ceramic before the ion exchange process). This is due to the presence of an alkali metal ion (e.g., Li) in the initially formed glass-ceramic. + Or Na + ) are respectively subjected to larger alkali metal ions (e.g., Na) + or K +Replacement. However, in the embodiments, the composition of the glass-ceramic at or near the depth center will remain the same as that of the initially formed glass-ceramic. As used herein, the center of a glass-ceramic article refers to a portion of the glass-ceramic article at least 0.5 meters from each of its surfaces. t Any location where t The thickness of glass ceramics or glass ceramic products.
[0203] Unless otherwise specified, the mechanical properties of the glass-ceramics disclosed herein have been tested on strengthened glass-ceramic articles. By forming glass-ceramics having the compositions disclosed and described herein, and using the heat treatments and chemical strengthening methods disclosed and described herein, glass-ceramics with phase combinations that provide low haze and improved mechanical properties (described in detail below) can be obtained. Although described in individual paragraphs below, various mechanical properties exist in combination in the glass-ceramics of the examples. The balance of these mechanical properties provides durable, robust glass-ceramics that are difficult to achieve without sacrificing other mechanical properties. For example, and by way of example only, it is possible to achieve high compressive stress alone, but achieving high compressive stress and central tensile strength may be more difficult.
[0204] In the embodiments, the compression depths DOC and DOC' of each surface are respectively greater than or equal to 0.09t and less than or equal to 0.30t, greater than or equal to 0.10t and less than or equal to 0.30t, greater than or equal to 0.11t and less than or equal to 0.30t, greater than or equal to 0.12t and less than or equal to 0.30t, greater than or equal to 0.13t and less than or equal to 0.30t, greater than or equal to 0.14t and less than or equal to 0.30t, greater than or equal to 0.15t and less than or equal to 0.30t, greater than or equal to 0.16t and less than or equal to 0.30t, greater than or equal to 0.17t and less than or equal to 0.30t, greater than or equal to 0.18t and less than or equal to 0.30t, greater than or equal to... 0.19t and less than or equal to 0.30t, greater than or equal to 0.20t and less than or equal to 0.30t, greater than or equal to 0.21t and less than or equal to 0.30t, greater than or equal to 0.22t and less than or equal to 0.30t, greater than or equal to 0.23t and less than or equal to 0.30t, greater than or equal to 0.24t and less than or equal to 0.30t, greater than or equal to 0.09t and less than or equal to 0.25t, greater than or equal to 0.10t and less than or equal to 0.25t, greater than or equal to 0.11t and less than or equal to 0.25t, greater than or equal to 0.12t and less than or equal to 0.25t, greater than or equal to 0.13t and less than or equal to 0.25t, greater than or equal to 0.14t and less than The values are: or equal to 0.25t, greater than or equal to 0.15t and less than or equal to 0.25t, greater than or equal to 0.16t and less than or equal to 0.25t, greater than or equal to 0.17t and less than or equal to 0.25t, greater than or equal to 0.18t and less than or equal to 0.25t, greater than or equal to 0.19t and less than or equal to 0.25t, greater than or equal to 0.20t and less than or equal to 0.25t, greater than or equal to 0.21t and less than or equal to 0.25t, greater than or equal to 0.22t and less than or equal to 0.25t, greater than or equal to 0.23t and less than or equal to 0.25t, greater than or equal to 0.24t and less than or equal to 0.25t, and greater than or equal to 0.09t and less than or equal to 0.24. t, greater than or equal to 0.10t and less than or equal to 0.24t, greater than or equal to 0.11t and less than or equal to 0.24t, greater than or equal to 0.12t and less than or equal to 0.24t, greater than or equal to 0.13t and less than or equal to 0.24t, greater than or equal to 0.14t and less than or equal to 0.24t, greater than or equal to 0.15t and less than or equal to 0.24t, greater than or equal to 0.16t and less than or equal to 0.24t, greater than or equal to 0.17t and less than or equal to 0.24t, greater than or equal to 0.18t and less than or equal to 0.24t, greater than or equal to 0.19t and less than or equal to 0.24t, greater than or equal to 0.20t and less than or equal to 0.24t, greater than or equal to 0.21t and less than or equal to 0.24t, greater than or equal to 0.22t and less than or equal to 0.24t, greater than or equal to 0.23t and less than or equal to 0.24t, greater than or equal to 0.09t and less than or equal to 0.23t, greater than or equal to 0.10t and less than or equal to 0.23t, greater than or equal to 0.11t and less than or equal to 0.23t, greater than or equal to 0.12t and less than or equal to 0.23t, greater than or equal to 0.13t and less than or equal to 0.23t, greater than or equal to 0.14t and less than or equal to 0.23t, greater than or equal to 0.15t and less than or equal to 0.23t, greater than or equal to 0.16t and less than or equal to 0.23t, greater than or equal to 0.17t and less than or equal to 0.24t. The values are: 0.23t, greater than or equal to 0.18t and less than or equal to 0.23t, greater than or equal to 0.19t and less than or equal to 0.23t, greater than or equal to 0.20t and less than or equal to 0.23t, greater than or equal to 0.21t and less than or equal to 0.23t, greater than or equal to 0.22t and less than or equal to 0.23t, greater than or equal to 0.09t and less than or equal to 0.22t, greater than or equal to 0.10t and less than or equal to 0.22t, greater than or equal to 0.11t and less than or equal to 0.22t, greater than or equal to 0.12t and less than or equal to 0.22t, greater than or equal to 0.13t and less than or equal to 0.22t, greater than or equal to 0.14t and less than or equal to 0.22t, and greater than... The values are: 0.15t and less than or equal to 0.22t, greater than or equal to 0.16t and less than or equal to 0.22t, greater than or equal to 0.17t and less than or equal to 0.22t, greater than or equal to 0.18t and less than or equal to 0.22t, greater than or equal to 0.19t and less than or equal to 0.22t, greater than or equal to 0.20t and less than or equal to 0.22t, greater than or equal to 0.21t and less than or equal to 0.22t, greater than or equal to 0.09t and less than or equal to 0.21t, greater than or equal to 0.10t and less than or equal to 0.21t, greater than or equal to 0.11t and less than or equal to 0.21t, greater than or equal to 0.12t and less than or equal to 0.21t, and greater than or equal to 0.13. The values of t are ≤0.21t, ≥0.14t, ≥0.15t, ≥0.16t, ≥0.17t, ≥0.18t, ≥0.19t, ≥0.21t, ≥0.20t, ≥0.09t, ≥0.10t, ≥0.11t, and ≥0.12t.20t, greater than or equal to 0.13t and less than or equal to 0.20t, greater than or equal to 0.14t and less than or equal to 0.20t, greater than or equal to 0.15t and less than or equal to 0.20t, greater than or equal to 0.16t and less than or equal to 0.20t, greater than or equal to 0.17t and less than or equal to 0.20t, greater than or equal to 0.18t and less than or equal to 0.20t, greater than or equal to 0.19t and less than or equal to 0.20t, greater than or equal to 0.09t and less than or equal to 0.19t, greater than or equal to 0.10t and less than or equal to 0.19t, greater than or equal to 0.11t and less than or equal to 0.19t, greater than or equal to 0 0.12t and less than or equal to 0.19t, greater than or equal to 0.13t and less than or equal to 0.19t, greater than or equal to 0.14t and less than or equal to 0.19t, greater than or equal to 0.15t and less than or equal to 0.19t, greater than or equal to 0.16t and less than or equal to 0.19t, greater than or equal to 0.17t and less than or equal to 0.19t, greater than or equal to 0.18t and less than or equal to 0.19t, greater than or equal to 0.09t and less than or equal to 0.18t, greater than or equal to 0.10t and less than or equal to 0.18t, greater than or equal to 0.11t and less than or equal to 0.18t, greater than or equal to 0.12t and less than or equal to 0.19t. 0.18t, greater than or equal to 0.13t and less than or equal to 0.18t, greater than or equal to 0.14t and less than or equal to 0.18t, greater than or equal to 0.15t and less than or equal to 0.18t, greater than or equal to 0.16t and less than or equal to 0.18t, greater than or equal to 0.17t and less than or equal to 0.18t, greater than or equal to 0.09t and less than or equal to 0.17t, greater than or equal to 0.10t and less than or equal to 0.17t, greater than or equal to 0.11t and less than or equal to 0.17t, greater than or equal to 0.12t and less than or equal to 0.17t, greater than or equal to 0.13t and less than or equal to 0.17t, greater than or equal to... The thickness is defined as follows: 0.14t and less than or equal to 0.17t, greater than or equal to 0.15t and less than or equal to 0.17t, greater than or equal to 0.16t and less than or equal to 0.17t, greater than or equal to 0.09t and less than or equal to 0.16t, greater than or equal to 0.10t and less than or equal to 0.16t, greater than or equal to 0.11t and less than or equal to 0.16t, greater than or equal to 0.12t and less than or equal to 0.16t, greater than or equal to 0.13t and less than or equal to 0.16t, greater than or equal to 0.14t and less than or equal to 0.16t, or greater than or equal to 0.15t and less than or equal to 0.16t, where t is the thickness of the glass-ceramic product.
[0205] Still referencing Figure 2Furthermore, as noted herein, there exists a central tensile region 110 with central tension (CT) between DOC and DOC'. Therefore, the stress changes from compressive stress to tensile stress at DOC and DOC', which, as described above, are measured from the surface of the reinforced glass-ceramic article towards the centerline.
[0206] In embodiments, the surface compressive stress (CS) of the glass-ceramic article can be greater than or equal to 200 MPa and less than or equal to 650 MPa, for example, greater than or equal to 225 MPa and less than or equal to 650 MPa, greater than or equal to 250 MPa and less than or equal to 650 MPa, greater than or equal to 275 MPa and less than or equal to 650 MPa, greater than or equal to 300 MPa and less than or equal to 650 MPa, greater than or equal to 325 MPa and less than or equal to 650 MPa, greater than or equal to 350 MPa and less than or equal to 650 MPa, greater than or equal to 375 MPa and less than or equal to 650 MPa, greater than or equal to 400 MPa and less than or equal to 650 MPa, greater than or equal to 425 MPa and less than or equal to 650 MPa, greater than or equal to 450 MPa and less than or equal to 650 MPa, greater than or equal to 475 MPa and less than or equal to 650 MPa, greater than or equal to 500 MPa, less than or equal to 65 ...650 MPa, less than or equal to 650 MPa, less than or equal to The following pressures are considered acceptable: 525 MPa and less than or equal to 650 MPa, 550 MPa and less than or equal to 650 MPa, 575 MPa and less than or equal to 650 MPa, 600 MPa and less than or equal to 650 MPa, 625 MPa and less than or equal to 650 MPa, 200 MPa and less than or equal to 600 MPa, for example, 225 MPa and less than or equal to 600 MPa, 250 MPa and less than or equal to 600 MPa, 275 MPa and less than or equal to 600 MPa, 300 MPa and less than or equal to 600 MPa, 325 MPa and less than or equal to 600 MPa, 350 MPa and less than or equal to 600 MPa, 375 MPa and less than or equal to 600 MPa. MPa, greater than or equal to 400 MPa and less than or equal to 600 MPa, greater than or equal to 425 MPa and less than or equal to 600 MPa, greater than or equal to 450 MPa and less than or equal to 600 MPa, greater than or equal to 475 MPa and less than or equal to 600 MPa, greater than or equal to 500 MPa and less than or equal to 600 MPa, greater than or equal to 525 MPa and less than or equal to 600 MPa, greater than or equal to 550 MPa and less than or equal to 600 MPa, greater than or equal to 575 MPa and less than or equal to 600 MPa, greater than or equal to 200 MPa and less than or equal to 550 MPa,For example, greater than or equal to 225 MPa and less than or equal to 550 MPa, greater than or equal to 250 MPa and less than or equal to 550 MPa, greater than or equal to 275 MPa and less than or equal to 550 MPa, greater than or equal to 300 MPa and less than or equal to 550 MPa, greater than or equal to 325 MPa and less than or equal to 550 MPa, greater than or equal to 350 MPa and less than or equal to 550 MPa, greater than or equal to 375 MPa and less than or equal to 550 MPa, greater than or equal to 400 MPa and less than or equal to 550 MPa, greater than or equal to 425 MPa and less than or equal to 550 MPa, greater than or equal to 450 MPa and less than or equal to 550 MPa, greater than or equal to 475 MPa and less than or equal to 550 MPa, greater than or equal to 500 MPa and less than or equal to 550 MPa, greater than or equal to 525 MPa and less than or equal to 550 MPa, greater than or equal to 200 MPa, less than or equal to 550 MPa, less ...525 MPa and less than or equal to 550 MPa, less than or equal to 200 MPa, less than or equal to 550 MPa, less than or equal to 550 MPa, less than or equal The following are examples of pressure values: ≥225 MPa and ≤500 MPa, ≥250 MPa and ≤500 MPa, ≥275 MPa and ≤500 MPa, ≥300 MPa and ≤500 MPa, ≥325 MPa and ≤500 MPa, ≥350 MPa and ≤500 MPa, ≥375 MPa and ≤500 MPa, ≥400 MPa and ≤500 MPa, ≥425 MPa and ≤500 MPa, ≥450 MPa and ≤500 MPa, ≥475 MPa and ≤500 MPa, and ≥200 MPa and ≤475 MPa. For example, ≥225 MPa and ≤475 MPa. MPa, greater than or equal to 250 MPa and less than or equal to 475 MPa, greater than or equal to 275 MPa and less than or equal to 475 MPa, greater than or equal to 300 MPa and less than or equal to 475 MPa, greater than or equal to 325 MPa and less than or equal to 475 MPa, greater than or equal to 350 MPa and less than or equal to 475 MPa, greater than or equal to 375 MPa and less than or equal to 475 MPa, greater than or equal to 400 MPa and less than or equal to 475 MPa, greater than or equal to 425 MPa and less than or equal to 475 MPa, greater than or equal to 450 MPa and less than or equal to 475 MPa, greater than or equal to 200 MPa and less than or equal to 450 MPaFor example, greater than or equal to 225 MPa and less than or equal to 450 MPa, greater than or equal to 250 MPa and less than or equal to 450 MPa, greater than or equal to 275 MPa and less than or equal to 450 MPa, greater than or equal to 300 MPa and less than or equal to 450 MPa, greater than or equal to 325 MPa and less than or equal to 450 MPa, greater than or equal to 350 MPa and less than or equal to 450 MPa, greater than or equal to 375 MPa and less than or equal to 450 MPa, greater than or equal to 400 MPa and less than or equal to 450 MPa, greater than or equal to 425 MPa and less than or equal to 450 MPa, greater than or equal to 200 MPa and less than or equal to 425 MPa, greater than or equal to 225 MPa and less than or equal to 425 MPa, greater than or equal to 250 MPa and less than or equal to 425 MPa, greater than or equal to 275 MPa and less than or equal to 425 MPa, greater than or equal to 300 MPa and less than or equal to 450 ... MPa and less than or equal to 425 MPa, greater than or equal to 325 MPa and less than or equal to 425 MPa, greater than or equal to 350 MPa and less than or equal to 425 MPa, greater than or equal to 375 MPa and less than or equal to 425 MPa, greater than or equal to 400 MPa and less than or equal to 425 MPa, greater than or equal to 200 MPa and less than or equal to 400 MPaFor example, greater than or equal to 225 MPa and less than or equal to 400 MPa, greater than or equal to 250 MPa and less than or equal to 400 MPa, greater than or equal to 275 MPa and less than or equal to 400 MPa, greater than or equal to 300 MPa and less than or equal to 400 MPa, greater than or equal to 325 MPa and less than or equal to 400 MPa, greater than or equal to 350 MPa and less than or equal to 400 MPa, greater than or equal to 375 MPa and less than or equal to 400 MPa, greater than or equal to 200 MPa and less than or equal to 375 MPa, greater than or equal to 225 MPa and less than or equal to 375 MPa, greater than or equal to 250 MPa and less than or equal to 375 MPa, greater than or equal to 275 MPa and less than or equal to 375 MPa, greater than or equal to 300 MPa and less than or equal to 375 MPa, greater than or equal to 325 MPa and less than or equal to 375 MPa, greater than or equal to 350 MPa and less than or equal to 40 ... MPa and less than or equal to 375 MPa, greater than or equal to 200 MPa and less than or equal to 350 MPa, greater than or equal to 225 MPa and less than or equal to 350 MPa, greater than or equal to 250 MPa and less than or equal to 350 MPa, greater than or equal to 275 MPa and less than or equal to 350 MPa, greater than or equal to 300 MPa and less than or equal to 350 MPa, greater than or equal to 325 MPa and less than or equal to 350 MPa, greater than or equal to 200 MPa and less than or equal to 325 MPa, greater than or equal to 275 MPa and less than or equal to 325 MPa, greater than or equal to 300 MPa and less than or equal to 325 MPa, greater than or equal to 200 MPa and less than or equal to 300 MPa, greater than or equal to 225 MPa and less than or equal to 300 MPa. MPa, greater than or equal to 250 MPa and less than or equal to 300 MPa, greater than or equal to 275 MPa and less than or equal to 300 MPa, greater than or equal to 200 MPa and less than or equal to 275 MPa, greater than or equal to 225 MPa and less than or equal to 275 MPa, greater than or equal to 250 MPa and less than or equal to 275 MPa, greater than or equal to 200 MPa and less than or equal to 250 MPa, greater than or equal to 225 MPa and less than or equal to 250 MPa, or greater than or equal to 200 MPa and less than or equal to 225 MPa. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0207] In the embodiment, the compressive stress CS of the glass-ceramic article at a depth of 0.01t to 0.02t (where "t" is the thickness of the glass-ceramic article) from the surface of the glass-ceramic article is... D The compressive stress CS of the glass-ceramic article at a depth of 0.01t to 0.02t (where "t" is the thickness of the glass-ceramic article) from the surface of the glass-ceramic article is greater than or equal to 300 MPa, greater than or equal to 305 MPa, greater than or equal to 310 MPa, greater than or equal to 315 MPa, greater than or equal to 320 MPa, greater than or equal to 325 MPa, greater than or equal to 330 MPa, greater than or equal to 335 MPa, greater than or equal to 340 MPa, or even greater than or equal to 345 MPa. In the embodiment, the compressive stress CS of the glass-ceramic article at a depth of 0.01t to 0.02t (where "t" is the thickness of the glass-ceramic article) from the surface of the glass-ceramic article is greater than or equal to 300 MPa, greater than or equal to 305 MPa, greater than or equal to 310 MPa, greater than or equal to 315 MPa, greater than or equal to 320 MPa, greater than or equal to 325 MPa, greater than or equal to 330 MPa, greater than or equal to 335 MPa, greater than or equal to 340 MPa, or even greater than or equal to 345 MPa. D The pressure can be greater than or equal to 300 MPa and less than or equal to 500 MPa, greater than or equal to 305 MPa and less than or equal to 500 MPa, greater than or equal to 310 MPa and less than or equal to 500 MPa, greater than or equal to 315 MPa and less than or equal to 500 MPa, greater than or equal to 320 MPa and less than or equal to 500 MPa, greater than or equal to 325 MPa and less than or equal to 500 MPa, greater than or equal to 330 MPa and less than or equal to 500 MPa, greater than or equal to 335 MPa and less than or equal to 500 MPa, greater than or equal to 340 MPa and less than or equal to 500 MPa, or even greater than or equal to 345 MPa and less than or equal to 500 MPa. It should be understood that the above ranges include all sub-ranges within the explicitly disclosed range.
[0208] In the embodiments, the maximum central tensile strength (mCT) is greater than or equal to 130 MPa, greater than or equal to 140 MPa, greater than or equal to 150 MPa, greater than or equal to 160 MPa, greater than or equal to 170 MPa, greater than or equal to 180 MPa, greater than or equal to 190 MPa, greater than or equal to 200 MPa, greater than or equal to 210 MPa, greater than or equal to 220 MPa, greater than or equal to 230 MPa, greater than or equal to 240 MPa, greater than or equal to 250 MPa, greater than or equal to 260 MPa, greater than or equal to 270 MPa, greater than or equal to 280 MPa, greater than or equal to 290 MPa, or even greater than or equal to 300 MPa. In the embodiments, the maximum central tensile strength is greater than or equal to 130 MPa and less than or equal to 300 MPa, greater than or equal to 140 MPa and less than or equal to 300 MPa, greater than or equal to 150 MPa and less than or equal to 300 MPa, greater than or equal to 160 MPa and less than or equal to 300 MPa, greater than or equal to 170 MPa and less than or equal to 300 MPa, greater than or equal to 180 MPa and less than or equal to 300 MPa, greater than or equal to 190 MPa and less than or equal to 300 MPa, greater than or equal to 200 MPa and less than or equal to 300 MPa, greater than or equal to 210 MPa and less than or equal to 300 MPa, greater than or equal to 220 MPa and less than or equal to 300 MPa, 230 MPa and less than or equal to 300 MPa, greater than or equal to 240 MPa and less than or equal to 300 MPa, greater than or equal to 250 MPa and less than or equal to 300 MPa, greater than or equal to 260 MPa, and greater than or equal to 260 MPa. MPa and less than or equal to 300 MPa, greater than or equal to 270 MPa and less than or equal to 300 MPa, greater than or equal to 280 MPa and less than or equal to 300 MPa, greater than or equal to 290 MPa and less than or equal to 300 MPa, greater than or equal to 130 MPa and less than or equal to 290 MPa, greater than or equal to 140 MPa and less than or equal to 290 MPa, greater than or equal to 150 MPa and less than or equal to 290 MPa, greater than or equal to 160 MPa and less than or equal to 290 MPa, greater than or equal to 170 MPa and less than or equal to 290 MPa, greater than or equal to 180 MPa and less than or equal to 290 MPa, greater than or equal to 190 MPa and less than or equal to 290 MPa, greater than or equal to 200 MPa and less than or equal to 290 MPa, greater than or equal to 210 MPa and less than or equal to 290 MPa, greater than or equal to 220 MPa and less than or equal to 290 MPa MPa, 230 MPa and less than or equal to 290 MPa, greater than or equal to 240 MPa and less than or equal to 290 MPaMPa, greater than or equal to 250 MPa and less than or equal to 290 MPa, greater than or equal to 260 MPa and less than or equal to 290 MPa, greater than or equal to 270 MPa and less than or equal to 290 MPa, greater than or equal to 280 MPa and less than or equal to 290 MPa, greater than or equal to 130 MPa and less than or equal to 280 MPa, greater than or equal to 140 MPa and less than or equal to 280 MPa, greater than or equal to 150 MPa and less than or equal to 280 MPa, greater than or equal to 160 MPa and less than or equal to 280 MPa, greater than or equal to 170 MPa and less than or equal to 280 MPa, greater than or equal to 180 MPa and less than or equal to 280 MPa, greater than or equal to 190 MPa and less than or equal to 280 MPa, greater than or equal to 200 MPa and less than or equal to 280 MPa, greater than or equal to 210 MPa and less than or equal to 280 MPa, greater than or equal to 220 MPa MPa and less than or equal to 280 MPa, 230 MPa and less than or equal to 280 MPa, greater than or equal to 240 MPa and less than or equal to 280 MPa, greater than or equal to 250 MPa and less than or equal to 280 MPa, greater than or equal to 260 MPa and less than or equal to 280 MPa, greater than or equal to 270 MPa and less than or equal to 280 MPa, greater than or equal to 130 MPa and less than or equal to 270 MPa, greater than or equal to 140 MPa and less than or equal to 270 MPa, greater than or equal to 150 MPa and less than or equal to 270 MPa, greater than or equal to 160 MPa and less than or equal to 270 MPa, greater than or equal to 170 MPa and less than or equal to 270 MPa, greater than or equal to 180 MPa and less than or equal to 270 MPa, greater than or equal to 190 MPa and less than or equal to 270 MPa, greater than or equal to 200 MPa, less than or equal to 270 MPa, greater than or equal to 200 MPa, less than or equal to 270 MPa, less ... MPa and less than or equal to 270 MPa, greater than or equal to 210 MPa and less than or equal to 270 MPa, greater than or equal to 220 MPa and less than or equal to 270 MPa, 230 MPa and less than or equal to 270 MPa, greater than or equal to 240 MPa and less than or equal to 270 MPa, greater than or equal to 250 MPa and less than or equal to 270 MPa, greater than or equal to 260 MPa and less than or equal to 270 MPa, greater than or equal to 130 MPa and less than or equal to 260 MPa, greater than or equal to 140 MPa and less than or equal to 260 MPa, greater than or equal to 150 MPa and less than or equal to 260 MPa, greater than or equal to 160 MPa and less than or equal to 260 MPa, greater than or equal to 170 MPa and less than or equal to 260 MPa, greater than or equal to 180 MPa and less than or equal to 260 MPaMPa, greater than or equal to 190 MPa and less than or equal to 260 MPa, greater than or equal to 200 MPa and less than or equal to 260 MPa, greater than or equal to 210 MPa and less than or equal to 260 MPa, greater than or equal to 220 MPa and less than or equal to 260 MPa, 230 MPa and less than or equal to 260 MPa, greater than or equal to 240 MPa and less than or equal to 260 MPa, greater than or equal to 250 MPa and less than or equal to 260 MPa, greater than or equal to 130 MPa and less than or equal to 250 MPa, greater than or equal to 140 MPa and less than or equal to 250 MPa, greater than or equal to 150 MPa and less than or equal to 250 MPa, greater than or equal to 160 MPa and less than or equal to 250 MPa, greater than or equal to 170 MPa and less than or equal to 250 MPa, greater than or equal to 180 MPa and less than or equal to 250 MPa, greater than or equal to 190 MPa MPa and less than or equal to 250 MPa, greater than or equal to 200 MPa and less than or equal to 250 MPa, greater than or equal to 210 MPa and less than or equal to 250 MPa, greater than or equal to 220 MPa and less than or equal to 250 MPa, 230 MPa and less than or equal to 250 MPa, greater than or equal to 240 MPa and less than or equal to 250 MPa, greater than or equal to 130 MPa and less than or equal to 240 MPa, greater than or equal to 140 MPa and less than or equal to 240 MPa, greater than or equal to 150 MPa and less than or equal to 240 MPa, greater than or equal to 160 MPa and less than or equal to 240 MPa, greater than or equal to 170 MPa and less than or equal to 240 MPa, greater than or equal to 180 MPa and less than or equal to 240 MPa, greater than or equal to 190 MPa and less than or equal to 240 MPa, greater than or equal to 200 MPa and less than or equal to 240 MPa MPa, greater than or equal to 210 MPa and less than or equal to 240 MPa, greater than or equal to 220 MPa and less than or equal to 240 MPa, 230 MPa and less than or equal to 240 MPa, greater than or equal to 130 MPa and less than or equal to 230 MPa, greater than or equal to 140 MPa and less than or equal to 230 MPa, greater than or equal to 150 MPa and less than or equal to 230 MPa, greater than or equal to 160 MPa and less than or equal to 230 MPa, greater than or equal to 170 MPa and less than or equal to 230 MPa, greater than or equal to 180 MPa and less than or equal to 230 MPa, greater than or equal to 190 MPa and less than or equal to 230 MPa, greater than or equal to 200 MPa and less than or equal to 230 MPa, greater than or equal to 210 MPa and less than or equal to 230 MPa, greater than or equal to 220 MPa, greater than or equal to 220 MPa, greater than or equal to 230 MPa, less than or equal to 230 MPa, greater than or equal to 220 MPa, less than or equal to 23 ...MPa and less than or equal to 230 MPa, greater than or equal to 130 MPa and less than or equal to 220 MPa, greater than or equal to 140 MPa and less than or equal to 220 MPa, greater than or equal to 150 MPa and less than or equal to 220 MPa, greater than or equal to 160 MPa and less than or equal to 220 MPa, greater than or equal to 170 MPa and less than or equal to 220 MPa, greater than or equal to 180 MPa and less than or equal to 220 MPa, greater than or equal to 190 MPa and less than or equal to 220 MPa, greater than or equal to 200 MPa and less than or equal to 220 MPa, greater than or equal to 210 MPa and less than or equal to 220 MPa, greater than or equal to 130 MPa and less than or equal to 210 MPa, greater than or equal to 140 MPa and less than or equal to 210 MPa, greater than or equal to 150 MPa and less than or equal to 210 MPa, greater than or equal to 160 MPa and less than or equal to 210 MPa MPa, greater than or equal to 170 MPa and less than or equal to 210 MPa, greater than or equal to 180 MPa and less than or equal to 210 MPa, greater than or equal to 190 MPa and less than or equal to 210 MPa, or even greater than or equal to 200 MPa and less than or equal to 210 MPa. It should be understood that the above ranges include all sub-ranges within the explicitly disclosed range.
[0209] Relatively high maximum central tensile strength is associated with glass-ceramics having relatively high stored strain energy. In the embodiments, the stored strain energy of the glass-ceramic article is greater than or equal to 30 J / m. 2 And less than or equal to 75 J / m 2 ≥30J / m 2 And less than or equal to 70 J / m 2 ≥30 J / m 2 And less than or equal to 65 J / m 2 ≥30 J / m 2 And less than or equal to 60 J / m 2 ≥30 J / m 2 And less than or equal to 55 J / m 2 ≥30 J / m 2 And less than or equal to 50 J / m 2 ≥30 J / m 2 And less than or equal to 45 J / m 2 or even greater than or equal to 30 J / m 2 And less than or equal to 40 J / m 2 It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0210] In the embodiments, the Knoop hardness of the non-chemically strengthened (i.e., non-ion-exchange) glass-ceramic article is greater than or equal to 650 kgf / mm². 2 And less than or equal to 700 kgf / mm 2 ≥655 kgf / mm 2 And less than or equal to 700 kgf / mm 2 ≥660 kgf / mm 2 And less than or equal to 700 kgf / mm 2 ≥665 kgf / mm 2 And less than or equal to 700 kgf / mm 2 ≥670 kgf / mm 2 And less than or equal to 700 kgf / mm 2 or even greater than or equal to 675 kgf / mm 2 And less than or equal to 700 kgf / mm 2 It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0211] In the embodiments, the Knoop hardness of the chemically strengthened (i.e., ion-exchange) glass-ceramic article is greater than or equal to 680 kgf / mm². 2 And less than or equal to 750 kgf / mm 2 ≥685 kgf / mm 2 And less than or equal to 750 kgf / mm 2 ≥690 kgf / mm 2 And less than or equal to 750 kgf / mm 2 ≥695 kgf / mm 2 And less than or equal to 750 kgf / mm 2 ≥700 kgf / mm 2 And less than or equal to 750 kgf / mm 2 ≥705 kgf / mm 2 And less than or equal to 750 kgf / mm 2 ≥710 kgf / mm 2 And less than or equal to 750 kgf / mm 2 ≥715 kgf / mm 2 And less than or equal to 750 kgf / mm 2 or even greater than or equal to 720 kgf / mm 2 And less than or equal to 750 kgf / mm 2It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0212] Using Al2O3 sandpaper of a specified grit, after introducing defects using a pendulum impactor apparatus, the failure stress is measured in a four-point bending test. Specifically, damage is introduced using an apparatus comprising a simple pendulum-type testing device, wherein a glass-ceramic specimen (e.g., a glass-ceramic plate) is mounted to the measuring hammer of the pendulum, and then the measuring hammer is used to bring the specimen into contact with a roughened impact surface. The apparatus is described in detail in U.S. Patent No. 11,131,611, entitled “Impact Testing Apparatus and Method,” which is hereby incorporated by reference in its entirety. For the test, the sample is loaded onto a support attached to the measuring hammer of the pendulum and then pulled back and released from the pendulum's equilibrium position to generate a dynamic impact on the impact surface.
[0213] After a defect is introduced into a glass-ceramic article using the pendulum impactor device described herein, the failure stress of the glass-ceramic article according to the embodiments described herein is measured in a four-point bending test on non-ion-exchanged and ion-exchanged glass-ceramic articles with a thickness t of 0.5 mm. As described herein, the load applied at failure is converted into stress (i.e., failure stress). For defects introduced using 180-mesh Al2O3 sandpaper, the failure stress of the non-ion-exchanged glass-ceramic article can be greater than or equal to 110 MPa, greater than or equal to 115 MPa, or even greater than or equal to 120 MPa. In the embodiments, for defects introduced using 180-mesh Al2O3 sandpaper, the failure stress can be greater than or equal to 110 MPa and less than or equal to 200 MPa, greater than or equal to 115 MPa and less than or equal to 200 MPa, or even greater than or equal to 120 MPa and less than or equal to 200 MPa. For defects introduced by using 80-mesh Al2O3 sandpaper, the failure stress of non-ion-exchange glass-ceramic products can be greater than or equal to 90 MPa, greater than or equal to 100 MPa, or even greater than or equal to 105 MPa. For defects introduced by using 80-mesh Al2O3 sandpaper, the failure stress of non-ion-exchange glass-ceramic products can be greater than or equal to 90 MPa and less than or equal to 150 MPa, greater than or equal to 100 MPa and less than or equal to 200 MPa, or even greater than or equal to 105 MPa and less than or equal to 150 MPa. For defects introduced by using 30-mesh Al2O3 sandpaper, the failure stress of non-ion-exchange glass-ceramic products can be greater than or equal to 80 MPa, greater than or equal to 85 MPa, or even greater than or equal to 90 MPa. For defects introduced by using 30-mesh Al2O3 sandpaper, the failure stress of non-ion-exchange glass-ceramic articles can be greater than or equal to 80 MPa and less than or equal to 120 MPa, greater than or equal to 85 MPa and less than or equal to 120 MPa, or even greater than or equal to 90 MPa and less than or equal to 150 MPa. In embodiments, for defects introduced by using Al2O3 sandpaper with a mesh size greater than or equal to 30, the failure stress of non-ion-exchange glass-ceramic articles in four-point bending can be greater than or equal to 80 MPa, greater than or equal to 85 MPa, greater than or equal to 90 MPa, greater than or equal to 95 MPa, greater than or equal to 100 MPa, greater than or equal to 110 MPa, greater than or equal to 120 MPa, greater than or equal to 130 MPa, or even greater than or equal to 140 MPa. It should be understood that the above ranges include all sub-ranges within the explicitly disclosed range.
[0214] In the embodiments of the glass-ceramic articles described herein, the glass-ceramic articles are more resistant to damage introduction, such that when defects are introduced by means such as the pendulum impactor device described herein, the defects in the glass-ceramic articles extend to a shallower depth compared to other glass-ceramic materials. In the embodiments, defects introduced in non-ion-exchanged glass-ceramic articles using the pendulum impactor device and 180-mesh Al2O3 sandpaper have an average defect depth of less than or equal to 70 µm, less than or equal to 65 µm, less than or equal to 60 µm, less than or equal to 55 µm, or even less than or equal to 50 µm. In the embodiments, defects introduced in non-ion-exchanged glass-ceramic articles using the pendulum impactor device and 80-mesh Al2O3 sandpaper have an average defect depth of less than or equal to 120 µm, less than or equal to 110 µm, less than or equal to 100 µm, less than or equal to 95 µm, or even less than or equal to 90 µm. In the embodiments, defects introduced in non-ion-exchange glass-ceramic articles using a pendulum impactor device and 30-mesh Al2O3 sandpaper include average defect depths of less than or equal to 170 µm, less than or equal to 160 µm, less than or equal to 150 µm, less than or equal to 140 µm, or even less than or equal to 130 µm. It should be understood that the above ranges include all sub-ranges within the explicitly disclosed range. In these embodiments, it should be understood that defects are introduced into the glass-ceramic articles using a pendulum impactor device and Al2O3 sandpaper of a specified mesh size. Subsequently, the glass-ceramic articles fail in a four-point bend as described herein, and images of the fracture surface of the glass-ceramic articles are acquired and analyzed using image analysis software to determine the average depth of the defects introduced using the pendulum impactor device.
[0215] In these embodiments, defects introduced into ion-exchange glass-ceramic articles using a pendulum impactor device and 80-mesh Al2O3 sandpaper include average defect depths of less than or equal to 120 µm, less than or equal to 110 µm, less than or equal to 100 µm, less than or equal to 90 µm, or even less than or equal to 80 µm. In these embodiments, it should be understood that defects are introduced into the glass-ceramic articles using a pendulum impactor device and Al2O3 sandpaper of a specified mesh size. Subsequently, the glass-ceramic articles fail in a four-point bending test as described herein, and images of the fracture surface of the glass-ceramic articles are acquired and analyzed using image analysis software to determine the average depth of the defects introduced using the pendulum impactor device. In an embodiment, after impact with a pendulum impactor and 80-mesh Al₂O₃ sandpaper, the fracture stress of an ion-exchange glass-ceramic with a thickness t of 0.5 mm can be greater than or equal to 250 MPa, greater than or equal to 275 MPa, greater than or equal to 300 MPa, greater than or equal to 325 MPa, greater than or equal to 350 MPa, greater than or equal to 375 MPa, greater than or equal to 400 MPa, greater than or equal to 425 MPa, or even greater than or equal to 450 MPa. It should be understood that the above ranges include all sub-ranges within the explicitly disclosed range.
[0216] In the embodiments, the fracture toughness of the non-chemically strengthened glass-ceramic products is greater than or equal to 1.1 MPa√m and less than or equal to 2.0 MPa√m, greater than or equal to 1.2 MPa√m and less than or equal to 2.0 MPa√m, greater than or equal to 1.4 MPa√m and less than or equal to 2.0 MPa√m, greater than or equal to 1.1 MPa√m and less than or equal to 1.8 MPa√m, greater than or equal to 1.2 MPa√m and less than or equal to 1.8 MPa√m, greater than or equal to 1.3 MPa√m and less than or equal to 1.8 MPa√m, greater than or equal to 1.4 MPa√m and less than or equal to 1.8 MPa√m, greater than or equal to 1.1 MPa√m and less than or equal to 1.6 MPa√m, greater than or equal to 1.2 MPa√m and less than or equal to 1.6 MPa√m, greater than or equal to 1.3 MPa√m and less than or equal to 1.6 MPa√m, and greater than or equal to 1.4 MPa√m. MPa√m and less than or equal to 1.6 MPa√m, greater than or equal to 1.5 MPa√m and less than or equal to 1.6 MPa√m, greater than or equal to 1.1 MPa√m and less than or equal to 1.5 MPa√m, greater than or equal to 1.2 MPa√m and less than or equal to 1.5 MPa√m, greater than or equal to 1.3 MPa√m and less than or equal to 1.5 MPa√m, greater than or equal to 1.4 MPa√m and less than or equal to 1.5 MPa√m, greater than or equal to 1.1 MPa√m and less than or equal to 1.4 MPa√m, greater than or equal to 1.2 MPa√m and less than or equal to 1.4 MPa√m, greater than or equal to 1.1 MPa√m and less than or equal to 1.3 MPa√m, or even greater than or equal to 1.2 MPa√m and less than or equal to 1.3 MPa√m. It should be understood that the above ranges include all sub-ranges within the explicitly disclosed range.
[0217] The glass-ceramics described herein, after being strengthened by ion exchange, are able to withstand mechanical damage from defects in the glass-ceramic surface without catastrophic failure (i.e., without fracture) and subsequently maintain relatively high strength (i.e., relatively high retained strength). For example, in an embodiment, after damage is introduced by pressurized gas, the retained strength of the glass-ceramic (also referred to herein as “failure stress”) is greater than or equal to 100 MPa for an average defect depth of less than or equal to 150 µm. In the embodiments, after damage is introduced by pressurized gas method, the retained strength of glass ceramic can be greater than or equal to 125 MPa for an average defect depth of less than or equal to 150 µm, greater than or equal to 150 MPa for an average defect depth of less than or equal to 150 µm, greater than or equal to 175 MPa for an average defect depth of less than or equal to 150 µm, greater than or equal to 200 MPa for an average defect depth of less than or equal to 150 µm, greater than or equal to 225 MPa for an average defect depth of less than or equal to 150 µm, or even greater than or equal to 250 MPa for an average defect depth of less than or equal to 150 µm. After damage is introduced via pressurized gas, the retained strength of the glass-ceramic can be greater than or equal to 200 MPa for an average defect depth of 100 µm or less, greater than or equal to 250 MPa for an average defect depth of 100 µm or less, greater than or equal to 275 MPa for an average defect depth of 100 µm or less, greater than or equal to 300 MPa for an average defect depth of 100 µm or less, greater than or equal to 325 MPa for an average defect depth of 100 µm or less, or even greater than or equal to 350 MPa for an average defect depth of 100 µm or less. After damage is introduced via pressurized gas, the retained strength of the glass-ceramic can be greater than or equal to 350 MPa for an average defect depth of 50 µm or less, greater than or equal to 375 MPa for an average defect depth of 50 µm or less, greater than or equal to 400 MPa for an average defect depth of 50 µm or less, or even greater than or equal to 425 MPa for an average defect depth of 50 µm or less. After damage is introduced via pressurized gas, the retained strength of the glass-ceramic can be greater than or equal to 450 MPa for an average defect depth of less than or equal to 25 µm, greater than or equal to 475 MPa for an average defect depth of less than or equal to 25 µm, or even greater than or equal to 500 MPa for an average defect depth of less than or equal to 25 µm. After damage is introduced via pressurized gas, the retained strength of the glass-ceramic can be greater than or equal to 500 MPa for an average defect depth of less than or equal to 10 µm, or even greater than or equal to 525 MPa for an average defect depth of less than or equal to 10 µm.It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0218] Drop testing methods are used to determine the maximum height from which a precursor glass or glass-ceramic article can be dropped without catastrophic failure (i.e., drop height). Drop testing methods involve performing a surface drop test on a positioning disk to which the precursor glass or glass-ceramic article is attached. The thickness of the precursor glass or glass-ceramic article to be tested is similar to or equal to the thickness to be used in a given handheld consumer electronics device. The positioning disk refers to a structure designed to mimic the size, shape, and weight distribution of a given device, such as a mobile phone. In the following text, the term "positioning disk" refers to a structure weighing 126.0 grams, with a length of 133.1 mm, a width of 68.2 mm, and a height of 9.4 mm.
[0219] A drop tester, an exemplary device for conducting drop testing methods, is available. Figure 18 The figure is shown with reference numeral 10. The drop mechanism 10 includes a chuck 12 with chuck jaws 14. A positioning disc 16 is placed in the chuck jaws 14, on which a glass or glass-ceramic article is attached, face down. The chuck 12 is prepared to drop from, for example, an electromagnetic chuck lifter. Reference is now made to... Figure 19 The chuck 12 is released, and during its descent, the chuck jaws 14 are triggered to open by, for example, a proximity sensor. When the chuck jaws 14 open, the positioning disk 16 is released. (See now for further details.) Figure 20 The falling positioning disc 16 impacts the drop surface 18. The drop surface 18 can be sandpaper of a specified grit. If the precursor glass or glass-ceramic product attached to the positioning disc withstands the drop (i.e., does not break), then the chuck 12 is set at an increased height and the test is repeated. The failure height is the lowest height at which the positioning disc, including the precursor glass or glass-ceramic product, fails after a drop.
[0220] In the embodiments, the drop height of a 0.6 mm thick glass-ceramic article on 80-grit SiC sandpaper is greater than or equal to 180 cm, greater than or equal to 190 cm, or even greater than or equal to 200 cm. In the embodiments, the drop height of a 0.6 mm thick glass-ceramic article on 80-grit SiC sandpaper is greater than or equal to 180 cm and less than or equal to 220 cm, greater than or equal to 190 cm and less than or equal to 220 cm, or even greater than or equal to 200 cm and less than or equal to 220 cm. It should be understood that the above ranges include all sub-ranges within the explicitly disclosed range.
[0221] In the embodiments, the drop height of a 0.5 mm thick glass-ceramic product on 80-grit SiC sandpaper is greater than or equal to 130 cm, greater than or equal to 140 cm, greater than or equal to 150 cm, greater than or equal to 160 cm, greater than or equal to 170 cm, greater than or equal to 180 cm, greater than or equal to 190 cm, greater than or equal to 200 cm, greater than or equal to 130 cm, greater than or equal to 140 cm, greater than or equal to 150 cm, greater than or equal to 160 cm, greater than or equal to 170 cm, greater than or equal to 180 cm, or even greater than or equal to 190 cm. In the embodiments, the drop heights of 0.5 mm thick glass-ceramic products on 80-grit SiC sandpaper are greater than or equal to 130 cm and less than or equal to 220 cm, greater than or equal to 140 cm and less than or equal to 220 cm, greater than or equal to 150 cm and less than or equal to 220 cm, greater than or equal to 160 cm and less than or equal to 220 cm, greater than or equal to 170 cm and less than or equal to 220 cm, greater than or equal to 180 cm and less than or equal to 220 cm, greater than or equal to 190 cm and less than or equal to 220 cm, greater than or equal to 200 cm and less than or equal to 220 cm, greater than or equal to 130 cm and less than or equal to 210 cm, greater than or equal to 140 cm and less than or equal to 210 cm, greater than or equal to 150 cm and less than or equal to 210 cm, greater than or equal to 160 cm and less than or equal to 210 cm, greater than or equal to 170 cm and less than or equal to 210 cm, and greater than or equal to 180 cm and less than or equal to 210 cm. cm, greater than or equal to 190 cm and less than or equal to 210 cm, greater than or equal to 200 cm and less than or equal to 210 cm, greater than or equal to 130 cm and less than or equal to 200 cm, greater than or equal to 140 cm and less than or equal to 200 cm, greater than or equal to 150 cm and less than or equal to 200 cm, greater than or equal to 160 cm and less than or equal to 200 cm, greater than or equal to 170 cm and less than or equal to 200 cm, greater than or equal to 180 cm and less than or equal to 200 cm, or even greater than or equal to 190 cm and less than or equal to 200 cm. It should be understood that the above ranges include all sub-ranges within the explicitly disclosed range.
[0222] In the embodiments, the drop height of a 0.55 mm thick glass-ceramic product on 80-grit SiC sandpaper is greater than or equal to 160 cm, greater than or equal to 170 cm, greater than or equal to 180 cm, greater than or equal to 190 cm, greater than or equal to 200 cm, greater than or equal to 160 cm, greater than or equal to 170 cm, greater than or equal to 180 cm, greater than or equal to 190 cm, or even greater than or equal to 190 cm. In the embodiments, the drop height of a 0.55 mm thick glass-ceramic product on 80-grit SiC sandpaper is greater than or equal to 160 cm and less than or equal to 220 cm, greater than or equal to 170 cm and less than or equal to 220 cm, greater than or equal to 180 cm and less than or equal to 220 cm, greater than or equal to 190 cm and less than or equal to 220 cm, greater than or equal to 200 cm and less than or equal to 220 cm, greater than or equal to 160 cm and less than or equal to 210 cm, greater than or equal to 170 cm and less than or equal to 210 cm, greater than or equal to 180 cm and less than or equal to 210 cm, greater than or equal to 190 cm and less than or equal to 210 cm, greater than or equal to 200 cm and less than or equal to 210 cm, greater than or equal to 160 cm and less than or equal to 200 cm, greater than or equal to 170 cm and less than or equal to 200 cm, greater than or equal to 180 cm and less than or equal to 200 cm, or even greater than or equal to 190 cm. cm and less than or equal to 200 cm. It should be understood that the above range includes all sub-ranges within the explicitly disclosed range.
[0223] In the embodiments, the drop height of a 0.6 mm thick glass-ceramic product on 60-mesh Al2O3 sandpaper is greater than or equal to 160 cm, greater than or equal to 170 cm, greater than or equal to 180 cm, greater than or equal to 190 cm, greater than or equal to 200 cm, greater than or equal to 160 cm, greater than or equal to 170 cm, greater than or equal to 180 cm, or even greater than or equal to 190 cm. In the embodiments, the drop height of a 0.6 mm thick glass-ceramic product on 60-grit Al2O3 sandpaper is greater than or equal to 160 cm and less than or equal to 220 cm, greater than or equal to 170 cm and less than or equal to 220 cm, greater than or equal to 180 cm and less than or equal to 220 cm, greater than or equal to 190 cm and less than or equal to 220 cm, greater than or equal to 200 cm and less than or equal to 220 cm, greater than or equal to 160 cm and less than or equal to 210 cm, greater than or equal to 170 cm and less than or equal to 220 cm, greater than or equal to 180 cm and less than or equal to 210 cm, greater than or equal to 190 cm and less than or equal to 210 cm, greater than or equal to 190 cm and less than or equal to 210 cm, greater than or equal to 160 cm and less than or equal to 200 cm, greater than or equal to 170 cm and less than or equal to 200 cm, greater than or equal to 180 cm and less than or equal to 200 cm, or even greater than or equal to 190 cm. cm and less than or equal to 200 cm. It should be understood that the above range includes all sub-ranges within the explicitly disclosed range.
[0224] In the embodiments, the drop height of a 0.55 mm thick glass-ceramic product on 36-grit Al2O3 sandpaper is greater than or equal to 45 cm, greater than or equal to 50 cm, greater than or equal to 55 cm, greater than or equal to 60 cm, greater than or equal to 65 cm, greater than or equal to 70 cm, greater than or equal to 75 cm, greater than or equal to 80 cm, greater than or equal to 85 cm, 90 cm, greater than or equal to 95 cm, 45 cm, greater than or equal to 50 cm, greater than or equal to 55 cm, greater than or equal to 60 cm, greater than or equal to 65 cm, greater than or equal to 70 cm, greater than or equal to 75 cm, greater than or equal to 80 cm, greater than or equal to 85 cm, 45 cm, greater than or equal to 50 cm, greater than or equal to 55 cm, greater than or equal to 55 cm, greater than or equal to 60 cm, greater than or equal to 65 cm, greater than or equal to 70 cm, greater than or equal to 75 cm, greater than or equal to 80 cm, greater than or equal to 85 cm, 45 cm, greater than or equal to 50 cm, greater than or equal to 55 cm. cm, greater than or equal to 60 cm, greater than or equal to 65 cm, greater than or equal to 70 cm, greater than or equal to 75 cm, greater than or equal to 80 cm, 45 cm, greater than or equal to 50 cm, greater than or equal to 55 cm, greater than or equal to 60 cm, greater than or equal to 65 cm, greater than or equal to 70 cm, or even greater than or equal to 75 cm. In the embodiments, the drop heights of 0.55 mm thick glass-ceramic products on 36-grit Al2O3 sandpaper are greater than or equal to 45 cm and less than or equal to 100 cm, greater than or equal to 50 cm and less than or equal to 100 cm, greater than or equal to 55 cm and less than or equal to 100 cm, greater than or equal to 60 cm and less than or equal to 100 cm, greater than or equal to 65 cm and less than or equal to 100 cm, greater than or equal to 70 cm and less than or equal to 100 cm, greater than or equal to 75 cm and less than or equal to 100 cm, greater than or equal to 80 cm and less than or equal to 100 cm, greater than or equal to 85 cm and less than or equal to 100 cm, 90 cm and less than or equal to 100 cm, greater than or equal to 95 cm and less than or equal to 100 cm, 45 cm and less than or equal to 95 cm, greater than or equal to 50 cm and less than or equal to 95 cm, greater than or equal to 55 cm and less than or equal to 95 cm, and greater than or equal to 60 cm and less than or equal to 95 cm. cm, greater than or equal to 65 cm and less than or equal to 95 cm, greater than or equal to 70 cm and less than or equal to 95 cm, greater than or equal to 75 cm and less than or equal to 95 cm, greater than or equal to 80 cm and less than or equal to 95 cm, greater than or equal to 85 cm and less than or equal to 95 cm, 90 cm and less than or equal to 95 cmcm, 45 cm and less than or equal to 90 cm, greater than or equal to 50 cm and less than or equal to 90 cm, greater than or equal to 55 cm and less than or equal to 90 cm, greater than or equal to 60 cm and less than or equal to 90 cm, greater than or equal to 65 cm and less than or equal to 90 cm, greater than or equal to 70 cm and less than or equal to 90 cm, greater than or equal to 75 cm and less than or equal to 90 cm, greater than or equal to 80 cm and less than or equal to 90 cm, greater than or equal to 85 cm and less than or equal to 90 cm, 45 cm and less than or equal to 85 cm, greater than or equal to 50 cm and less than or equal to 85 cm, greater than or equal to 55 cm and less than or equal to 85 cm, greater than or equal to 60 cm and less than or equal to 85 cm, greater than or equal to 65 cm and less than or equal to 85 cm, greater than or equal to 70 cm and less than or equal to 85 cm, greater than or equal to 75 cm and less than or equal to 85 cm, greater than or equal to 80 cm and less than or equal to 85 cm, 45 cm and less than or equal to 80 cm cm, greater than or equal to 50 cm and less than or equal to 80 cm, greater than or equal to 55 cm and less than or equal to 80 cm, greater than or equal to 60 cm and less than or equal to 80 cm, greater than or equal to 65 cm and less than or equal to 80 cm, greater than or equal to 70 cm and less than or equal to 80 cm, or even greater than or equal to 75 cm and less than or equal to 80 cm. It should be understood that the above range includes all sub-ranges within the explicitly disclosed range.
[0225] In the embodiments, the drop height of a 0.60 mm thick glass-ceramic product on 36-grit Al2O3 sandpaper is greater than or equal to 45 cm, greater than or equal to 50 cm, greater than or equal to 55 cm, greater than or equal to 60 cm, greater than or equal to 65 cm, greater than or equal to 70 cm, greater than or equal to 75 cm, greater than or equal to 80 cm, greater than or equal to 85 cm, 90 cm, greater than or equal to 95 cm, 45 cm, greater than or equal to 50 cm, greater than or equal to 55 cm, greater than or equal to 60 cm, greater than or equal to 65 cm, greater than or equal to 70 cm, greater than or equal to 75 cm, greater than or equal to 80 cm, greater than or equal to 85 cm, 45 cm, greater than or equal to 50 cm, greater than or equal to 55 cm, greater than or equal to 55 cm, greater than or equal to 60 cm, greater than or equal to 65 cm, greater than or equal to 70 cm, greater than or equal to 75 cm, greater than or equal to 80 cm, greater than or equal to 85 cm, 45 cm, greater than or equal to 50 cm, greater than or equal to 55 cm. cm, greater than or equal to 60 cm, greater than or equal to 65 cm, greater than or equal to 70 cm, greater than or equal to 75 cm, greater than or equal to 80 cm, greater than or equal to 45 cm, greater than or equal to 50 cm, greater than or equal to 55 cm, greater than or equal to 60 cm, greater than or equal to 65 cm, greater than or equal to 70 cm, or even greater than or equal to 75 cm. In the embodiments, the drop heights of 0.60 mm thick glass-ceramic products on 36-grit Al2O3 sandpaper are as follows: greater than or equal to 45 cm and less than or equal to 100 cm, greater than or equal to 50 cm and less than or equal to 100 cm, greater than or equal to 55 cm and less than or equal to 100 cm, greater than or equal to 60 cm and less than or equal to 100 cm, greater than or equal to 65 cm and less than or equal to 100 cm, greater than or equal to 70 cm and less than or equal to 100 cm, greater than or equal to 75 cm and less than or equal to 100 cm, greater than or equal to 80 cm and less than or equal to 100 cm, greater than or equal to 85 cm and less than or equal to 100 cm, 90 cm and less than or equal to 100 cm, greater than or equal to 95 cm and less than or equal to 100 cm, 45 cm and less than or equal to 95 cm, greater than or equal to 50 cm and less than or equal to 95 cm, greater than or equal to 55 cm and less than or equal to 95 cm, and greater than or equal to 60 cm and less than or equal to 95 cm. cm, greater than or equal to 65 cm and less than or equal to 95 cm, greater than or equal to 70 cm and less than or equal to 95 cm, greater than or equal to 75 cm and less than or equal to 95 cm, greater than or equal to 80 cm and less than or equal to 95 cm, greater than or equal to 85 cm and less than or equal to 95 cm, 90 cm and less than or equal to 95 cmcm, 45 cm and less than or equal to 90 cm, greater than or equal to 50 cm and less than or equal to 90 cm, greater than or equal to 55 cm and less than or equal to 90 cm, greater than or equal to 60 cm and less than or equal to 90 cm, greater than or equal to 65 cm and less than or equal to 90 cm, greater than or equal to 70 cm and less than or equal to 90 cm, greater than or equal to 75 cm and less than or equal to 90 cm, greater than or equal to 80 cm and less than or equal to 90 cm, greater than or equal to 85 cm and less than or equal to 90 cm, 45 cm and less than or equal to 85 cm, greater than or equal to 50 cm and less than or equal to 85 cm, greater than or equal to 55 cm and less than or equal to 85 cm, greater than or equal to 60 cm and less than or equal to 85 cm, greater than or equal to 65 cm and less than or equal to 85 cm, greater than or equal to 70 cm and less than or equal to 85 cm, greater than or equal to 75 cm and less than or equal to 85 cm, greater than or equal to 80 cm and less than or equal to 85 cm, 45 cm and less than or equal to 80 cm cm, greater than or equal to 50 cm and less than or equal to 80 cm, greater than or equal to 55 cm and less than or equal to 80 cm, greater than or equal to 60 cm and less than or equal to 80 cm, greater than or equal to 65 cm and less than or equal to 80 cm, greater than or equal to 70 cm and less than or equal to 80 cm, or even greater than or equal to 75 cm and less than or equal to 80 cm. It should be understood that the above range includes all sub-ranges within the explicitly disclosed range.
[0226] In the embodiments, the Young's modulus (also known as the elastic modulus) of the non-chemically strengthened glass-ceramic articles is greater than or equal to 100 GPa and less than or equal to 130 GPa, greater than or equal to 105 GPa and less than or equal to 130 GPa, greater than or equal to 100 GPa and less than or equal to 120 GPa, greater than or equal to 105 GPa and less than or equal to 120 GPa, greater than or equal to 100 GPa and less than or equal to 115 GPa, greater than or equal to 105 GPa and less than or equal to 115 GPa, or greater than or equal to 110 GPa and less than or equal to 115 GPa. It should be understood that the above ranges include all sub-ranges within the explicitly disclosed range.
[0227] In the embodiments, the Poisson's ratio of the non-chemically strengthened glass-ceramic articles is greater than or equal to 0.20 and less than or equal to 0.25, greater than or equal to 0.21 and less than or equal to 0.25, greater than or equal to 0.22 and less than or equal to 0.25, greater than or equal to 0.23 and less than or equal to 0.25, greater than or equal to 0.20 and less than or equal to 0.23, greater than or equal to 0.21 and less than or equal to 0.23, or even greater than or equal to 0.20 and less than or equal to 0.22. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0228] In the embodiments, the shear modulus of the non-chemically strengthened glass-ceramic articles is greater than or equal to 40 GPa and less than or equal to 50 GPa, greater than or equal to 41 GPa and less than or equal to 50 GPa, greater than or equal to 42 GPa and less than or equal to 50 GPa, greater than or equal to 40 GPa and less than or equal to 48 GPa, greater than or equal to 41 GPa and less than or equal to 48 GPa, greater than or equal to 42 GPa and less than or equal to 48 GPa, or even greater than or equal to 43 GPa and less than or equal to 46 GPa. It should be understood that the above ranges include all sub-ranges within the explicitly disclosed range.
[0229] According to embodiments, the refractive index of the glass-ceramic (measured at a wavelength of 589.3 nm) is greater than or equal to 1.500 and less than or equal to 1.600, greater than or equal to 1.520 and less than or equal to 1.600, greater than or equal to 1.540 and less than or equal to 1.600, greater than or equal to 1.550 and less than or equal to 1.600, greater than or equal to 1.560 and less than or equal to 1.600, greater than or equal to 1.570 and less than or equal to 1.600, greater than or equal to 1.500 and less than or equal to 1.580, greater than or equal to 1.520 and less than or equal to 1.580, greater than or equal to 1.540 and less than or equal to 1.580, and greater than or equal to 1.550 and less than or equal to 1.580. It should be understood that the above scope includes all sub-scopes within the explicitly disclosed scope.
[0230] The stress optical coefficient (measured at a wavelength of 546 nm) of the glass-ceramic according to the embodiment is greater than or equal to 2.40 nm / mm / MPa and less than or equal to 2.50 nm / mm / MPa. It should be understood that the above range includes all sub-ranges within the explicitly disclosed range.
[0231] In some embodiments, the glass described herein can be made compatible with the float glass process by adjusting the liquidus viscosity. In some embodiments, the liquidus viscosity of the glass may be greater than or equal to 0.1 kpoll (kP) to less than or equal to 2 kP, greater than or equal to 0.1 kP to less than or equal to 1.5 kP, greater than or equal to 0.1 kP to less than or equal to 1.25 kP, greater than or equal to 0.2 kP to less than or equal to 2 kP, greater than or equal to 0.2 kP to less than or equal to 1.5 kP, greater than or equal to 0.2 kP to less than or equal to 1.25 kP, greater than or equal to 0.3 kpoll (kP) to less than or equal to 2 kP, greater than or equal to 0.3 kP to less than or equal to 1.5 kP, greater than or equal to 0.3 kP to less than or equal to 1.25 kP, greater than or equal to 0.4 kpoll (kP) to less than or equal to 2 kP, greater than or equal to 0.4 kP to less than or equal to 1.5 kP, or greater than or equal to 0.4 kP to less than or equal to 1.25 kP. kP, greater than or equal to 0.5 kP to less than or equal to 2 kP, greater than or equal to 0.5 kP to less than or equal to 1.5 kP, or even greater than or equal to 0.5 kP to less than or equal to 1.25 kP.
[0232] Based on the foregoing, it has been discovered that the glass disclosed herein can be ceramicized to form lithium disilicate-based glass-ceramics, which possess improved mechanical and optical properties, particularly haze and optical transmittance. Specifically, prior to the discovery of the glass and glass-ceramics described herein, it was difficult to simultaneously achieve the desired mechanical and optical properties in lithium disilicate-based glass-ceramics, making them suitable for applications requiring both, such as cover and housing materials for mobile electronic devices. That is, previous lithium disilicate-based glass-ceramics might possess either the desired mechanical or optical properties, but not both simultaneously. In this regard, the lithium disilicate-based glass-ceramics described herein have the following combination: Young's modulus greater than or equal to 100 GPa, fracture toughness greater than or equal to 1.10 MPa·m. 1 / 2 It exhibits a transmittance greater than 88% and a haze value less than 1.0% for light with wavelengths greater than or equal to 400 nm and less than or equal to 750 nm, while also possessing excellent mechanical and optical properties, making it suitable for a variety of applications, including handheld electronic devices and other end-use applications. In one or more embodiments, the glass-ceramic exhibits the aforementioned transmittance and haze when its thickness is less than or equal to 0.6 mm.
[0233] In an embodiment, the glass-ceramic article formed from glass may be in the form of a strip, bar, rod or ingot, from which a substrate or sheet may be cut. In embodiments, the glass-ceramic article formed from glass can be in the form of a substrate or plate, with a thickness t greater than or equal to 0.1 mm and less than or equal to 3.5 mm, greater than or equal to 0.3 mm and less than or equal to 3.5 mm, greater than or equal to 0.5 mm and less than or equal to 3.5 mm, greater than or equal to 0.8 mm and less than or equal to 3.5 mm, greater than or equal to 1.0 mm and less than or equal to 3.5 mm, greater than or equal to 1.3 mm and less than or equal to 3.5 mm, greater than or equal to 1.5 mm and less than or equal to 3.5 mm, greater than or equal to 1.8 mm and less than or equal to 3.5 mm, greater than or equal to 2.0 mm and less than or equal to 3.5 mm, greater than or equal to 2.2 mm and less than or equal to 3.5 mm, greater than or equal to 2.4 mm and less than or equal to 3.5 mm, greater than or equal to 2.6 mm and less than or equal to 3.5 mm, greater than or equal to 2.8 mm and less than or equal to 3.5 mm, and greater than or equal to 3.0 mm and less than or equal to 3.5 mm. mm, greater than or equal to 3.2 mm and less than or equal to 3.5 mm, greater than or equal to 0.1 mm and less than or equal to 3.2 mm, greater than or equal to 0.3 mm and less than or equal to 3.2 mm, greater than or equal to 0.5 mm and less than or equal to 3.2 mm, greater than or equal to 0.8 mm and less than or equal to 3.2 mm, greater than or equal t...
Claims
1. A glass-ceramic product comprising: The composition comprises the following weight percentages (wt%) based on oxides: Greater than or equal to 55% by weight and less than or equal to 80% by weight of SiO2; Al2O3 greater than or equal to 0% by weight and less than or equal to 6% by weight; Li₂O with a weight of 7% or more and a weight of 20% or less; P2O5 greater than or equal to 1% by weight and less than or equal to 8% by weight; Greater than 0.5% by weight and less than or equal to 20% by weight of ZrO2; Greater than or equal to 0% by weight and less than or equal to 5.0% by weight of Na2O; as well as K2O greater than or equal to 0% by weight and less than or equal to 5.0% by weight; The phase combination comprises lithium disilicate (Li₂Si₂O₅) as the main crystalline phase and a residual amorphous glass phase. The Rietwald parameter of the lithium disilicate (Li2Si2O5) is greater than or equal to 20 and less than or equal to 90. Lithium phosphate (Li3PO4) with a Rietwald parameter greater than or equal to 0 and less than or equal to 10. Lithium metasilicate (Li₂SiO₃) with a Rietwald parameter greater than or equal to 0 and less than or equal to 10; and Lithium perlite (LiAlSi4O4) with a Ritwald parameter greater than or equal to 0 and less than 5 10 ); For light with wavelengths greater than or equal to 400 nm and less than or equal to 750 nm, the transmittance is greater than 88%; and Haze less than 1%; and Thickness less than 1.6 mm.
2. The glass-ceramic article according to claim 1, wherein the phase composition is substantially free of lepidolite crystal phase; and wherein the haze is less than 0.2%.
3. The glass-ceramic article according to claim 2, comprising: Greater than or equal to 55% by weight and less than or equal to 80% by weight of SiO2; Li₂O with a weight of 7% or more and a weight of 20% or less; ZrO2 greater than 4% by weight and less than or equal to 15% by weight; P2O5 greater than or equal to 1% by weight and less than or equal to 8% by weight; Greater than or equal to 0.1% by weight and less than or equal to 5% by weight of Na₂O; and Less than 1% by weight of K2O.
4. The glass-ceramic product according to claim 3, wherein: The Li₂O content is greater than or equal to 12.0% by weight. The ZrO2 is greater than or equal to 8.0% by weight. The Na₂O is greater than or equal to 0.5% by weight; and The P2O5 is greater than or equal to 3.0 by weight.
5. The glass-ceramic article according to claim 4, wherein the composition further comprises: HfO2 greater than 0% by weight and less than or equal to 3.0% by weight; and SnO2 greater than 0% by weight and less than or equal to 3% by weight.
6. The glass-ceramic article according to claim 5, wherein the lithium disilicate (Li2Si2O5) included in the phase combination has a Rietwald parameter greater than or equal to 55 and less than or equal to 65.
7. The glass-ceramic article according to claim 2, which retains the following strength after damage is introduced by pressurized gas method: For an average defect depth of less than or equal to 150 µm, the pressure is greater than or equal to 100 MPa. For an average defect depth of less than or equal to 100 µm, the pressure is greater than or equal to 200 MPa. For an average defect depth of less than or equal to 50 µm, the pressure is greater than or equal to 350 MPa. For an average defect depth of 25 µm or less, the pressure is greater than or equal to 450 MPa. as well as For an average defect depth of less than or equal to 10 µm, the pressure is greater than or equal to 500 MPa.
8. The glass-ceramic article according to claim 2, wherein the ratio of Li2O (wt%) to ZrO2 (wt%) in the glass-ceramic is greater than or equal to 1.10 and less than or equal to 5.
0.
9. The glass-ceramic article according to claim 2, further comprising: A compressive stress layer, the compressive stress layer extending from the surface of the glass-ceramic to the compression depth; and Maximum center tension, wherein the maximum center tension is greater than 130 MPa.
10. The glass-ceramic article according to claim 9, wherein the compressive stress layer contains a surface compressive stress greater than or equal to 200 MPa and less than or equal to 650 MPa.
11. The glass-ceramic article according to claim 9, comprising: Young's modulus is greater than or equal to 100 GPa and less than or equal to 130 GPa; and Before ion exchange strengthening, the fracture toughness is greater than or equal to 1.10 MPa·m. 1 / 2 And less than or equal to 2.00 MPa·m 1 / 2 .
12. An electronic device comprising a cover substrate comprising the glass-ceramic article of claim 2.
13. The glass-ceramic article according to claim 2, wherein the composition further comprises more than 0% by weight to less than 8% by weight of CaO.
14. The glass-ceramic article according to claim 2, wherein the composition comprises an Al2O3 (wt%) to Li2O (wt%) ratio greater than or equal to 0 and less than 0.
50.
15. The glass-ceramic product according to claim 1, The ZrO2 is greater than 4% by weight and less than or equal to 15% by weight. The Na₂O content is greater than or equal to 0.1% by weight and less than or equal to 5% by weight; and The K2O is greater than or equal to 0% by weight and less than 1% by weight; and The phase combination described therein is essentially free of the lithium feldspar crystal phase.
16. The glass-ceramic article according to claim 15, further comprising: A compressive stress layer, the compressive stress layer extending from the surface of the glass-ceramic to the compression depth; and Maximum center tension, wherein the maximum center tension is greater than 130 MPa.
17. The glass-ceramic article of claim 16, wherein the compressive stress layer comprises a surface compressive stress greater than or equal to 200 MPa and less than or equal to 650 MPa.
18. The glass-ceramic article according to claim 1, wherein the lithium disilicate (Li2Si2O5) included in the phase combination has a Rietwald parameter greater than or equal to 55 and less than or equal to 65.
19. The glass-ceramic article according to claim 1, wherein the ratio of Li2O (wt%) to ZrO2 (wt%) in the glass-ceramic is greater than or equal to 1.10 and less than or equal to 5.0.
Citation Information
Patent Citations
Impact testing apparatus and methods
US11131611B2
Hybrid systems and methods for characterizing stress in chemically strengthened transparent substrates
US20200300615A1